Fabric softener sheet composition for laundry dryer and manufacturing method thereof
Patent Information
- Application Number
- KR1020250166549
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-11-06
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2045-11-06
Abstract
Description
Technology Field
[0001] The following examples relate to a fabric softener sheet composition for a laundry dryer and a method for manufacturing the same. Background Technology
[0002] The present invention relates to a fabric softener sheet composition for a laundry dryer and a method for manufacturing the same, and more specifically, to a fabric softener sheet composition for a laundry dryer and a method for manufacturing the same that improves product stability and fragrance longevity by applying a multi-stage purified water treatment process and a step-by-step raw material input method.
[0003] Generally, fabric softener sheets for laundry dryers are products that are added to clothes when drying them in a dryer to provide flexibility, prevent static electricity, and impart fragrance. They are manufactured by impregnating a fabric softener composition, primarily composed of cationic surfactants, into the fabric. In the high-temperature environment of the dryer, the fabric softener composition volatilizes and is uniformly coated on the surface of the clothes, providing a soft touch and fragrance along with an antistatic effect.
[0004] Conventional methods for manufacturing fabric softener sheets for laundry dryers have primarily involved dissolving a liquid cationic surfactant in water, mixing it with various additives to produce a fabric softener composition, and impregnating the fabric with it. However, these conventional technologies had the following problems.
[0005] First, in conventional technology, the use of water that has undergone only general purification treatment resulted in a problem where trace amounts of metal ions, organic matter, and microorganisms remaining in the water reduced product stability. In particular, metal ions such as iron, calcium, and magnesium reacted with cationic surfactants to form precipitates or reduced emulsion stability, causing the deterioration of the product's appearance and performance. Additionally, residual microorganisms in the water caused product spoilage during long-term storage, leading to a problem of shortened shelf life.
[0006] Second, conventional technology used a method of dissolving citric acid by adding it to water all at once. However, this resulted in the citric acid becoming locally supersaturated, slowing down the dissolution rate and causing problems with undissolved particles remaining. In particular, when citric acid is added all at once, the pH of the mixture drops rapidly, causing subsequent additions of sodium benzoate or protein-derived surfactants to precipitate or denature. This lowered the transparency of the final product and hindered the uniform dispersion of ingredients, causing non-uniformity in product quality.
[0007] Third, conventional technology utilized a method of directly adding polydimethylsiloxane-based defoaming agents into an aqueous mixture. However, due to the hydrophobic nature of the defoaming agents, their dispersibility in water was low, leading to aggregation into large particles. Consequently, the defoaming effect was uneven, and excessive distribution of the agent in specific areas resulted in issues such as reduced product texture or the formation of stains. Furthermore, the uneven dispersion of the defoaming agent failed to effectively suppress excessive foaming during the manufacturing process, causing a decrease in production efficiency.
[0008] Fourth, conventional technology used a method of adding moisturizers and thickeners such as glycerin, propylene glycol, hexanediol, and sorbitol all at once. However, this caused a problem where the viscosity of the mixture increased rapidly, making it difficult to uniformly mix subsequent raw materials. In particular, when additional raw materials were added while the viscosity was high, localized high-concentration regions were formed, and it was observed that complete homogenization was not achieved even with stirring for a sufficient amount of time. This caused quality variation between batches of the product and reduced reproducibility.
[0009] Fifth, conventional technology used a method of adding cationic surfactants all at once; however, if temperature control was not properly maintained, problems such as uneven dispersion or aggregation of the surfactants occurred. In particular, liquid cationic surfactants such as dialkyl ester ammonium methosulfate exhibit a characteristic where viscosity changes significantly with temperature; therefore, if added without proper temperature management, coacervate formation was incomplete, leading to a decrease in softening effects and fragrance encapsulation efficiency.
[0010] Sixth, conventional technology did not specifically specify a process for removing volatile organic compounds generated during the ethanol mixing process, posing a risk of skin irritation caused by residual ethanol in the final product, along with safety issues in the working environment. Additionally, it has been pointed out that the accumulation of volatile ethanol within manufacturing facilities increases the risk of fire or explosion.
[0011] Seventh, conventional technology used methods of mixing fragrances at room temperature or high temperatures; however, this resulted in the loss of volatile components during the mixing process, leading to a decrease in the fragrance intensity of the final product. In particular, given that the heat resistance and persistence of the fragrance are critical for products used in the high-temperature environment of dryers, a significant amount of fragrance components were already lost during the manufacturing process, often causing the product's fragrance longevity to fall short of expectations.
[0012] Eighth, in the prior art, a process for removing static electricity from the fabric before impregnating the fabric with the composition was not specified, so there was a problem in that the absorption rate and dispersion uniformity of the composition were reduced due to static electricity remaining on the surface of the fabric. In particular, in the case of fabrics containing viscose fibers or synthetic fibers, static electricity is easily generated, and a phenomenon was observed in which the composition was excessively concentrated in specific areas or impregnation was uneven.
[0013] To address the problems of conventional technology, some prior art has proposed methods such as adjusting the composition ratio of specific components or adding additives; however, sufficient solutions have not been presented to fundamentally resolve the issues through improvements in the manufacturing process itself. In particular, research on comprehensive manufacturing methods that simultaneously enhance product stability, fragrance longevity, and flexibility by systematically optimizing process variables—such as water quality control, the order and method of raw material input, and the stepwise control of temperature and stirring conditions—has been insufficient.
[0014] Therefore, in the technical field of the present invention, there is an urgent need to develop an improved manufacturing method that uses high-purity purified water, sets the optimal input sequence and conditions considering the physicochemical characteristics of each raw material, precisely controls the temperature and stirring speed at each stage, and minimizes flavor loss while ensuring environmental safety. Prior art literature
[0015] Korean Registered Patent 10-12671264 Korean Published Patent 10-2023-0097908 Korean Registered Patent 10-2856557 Korean Published Patent 10-2008-0086328 The problem to be solved
[0016] The method for manufacturing a fabric softener sheet composition for a laundry dryer according to the present invention provides the following significant effects.
[0017] First, the present invention can produce high-purity purified water with an electrical conductivity of 5 to 15 μS / cm and a total dissolved solids content of 5 to 20 ppm or less, measured at 25°C, by applying a five-step purified water manufacturing process that sequentially passes through a mesh filter of 210 mesh or more, an activated carbon filter, an ultraviolet sterilization filter, a membrane filter, and a final line filter made of SUS316. The use of such high-purity purified water prevents the formation of precipitates of cationic surfactants by metal ions and suppresses product deterioration caused by microbial contamination, thereby providing the effect of improving the long-term storage stability of the final product by 40 to 60% compared to conventional technology.
[0018] Second, the present invention applies an indirect heating method using a double-jacketed heating tank to precisely control the heating speed to 1 to 3°C per minute during the preheating stage and 0.5 to 2°C per minute during the main heating stage, thereby preventing local overheating of the purified water and maintaining the temperature deviation inside the heating tank within ±1.5°C. In addition, by bubbling nitrogen gas with a purity of 99.9% or higher at a flow rate of 0.1 to 0.5 L / min for 5 to 15 minutes to reduce the dissolved oxygen concentration to 5 ppm or less, oxidation of subsequently added citric acid, glycerin, fragrances, etc. is prevented, thereby providing the effect of improving the color stability and fragrance stability of the product by 35 to 50% compared to conventional technology.
[0019] Third, the present invention applies a method of adding citric acid in two stages, wherein 30 to 50% by weight of the total amount is added in the first stage and mixed for 3 to 8 minutes, and the remaining amount is added gradually over 2 to 5 minutes in the second stage, and the stirring speed is gradually increased from 50 to 80 rpm to 100 to 200 rpm. This method improves the dissolution rate of citric acid by 20 to 40% compared to the batch addition method and reduces the residue of undissolved particles by more than 90%. In addition, by preventing a rapid decrease in pH and effectively suppressing the denaturation or precipitation of subsequently added sodium benzoate, antistatic agent, and glycerin, the invention provides the effect of stably producing a transparent aqueous citric acid solution with a light transmittance of 85% or more at a wavelength of 600 nm.
[0020] Fourth, the present invention applies a method of introducing sodium benzoate and D-sorbitol in the form of an aqueous solution pre-dissolved in purified water preheated to 35–45°C at a concentration of 10–20% by weight or 20–40% by weight, instead of directly introducing them in powder form, thereby shortening the dissolution time by 30–50% and preventing particle aggregation by more than 80%. This not only improves manufacturing efficiency but also provides the effect of significantly improving product quality reproducibility between batches by ensuring that each component is uniformly dispersed within a deviation of ±3% relative to the target concentration.
[0021] Fifth, the present invention applies a method of introducing a polydimethylsiloxane-based defoamer in the form of a defoamer emulsion, which is pre-emulsified with propylene glycol in a weight ratio of 1:2 to 1:5, thereby improving the dispersibility of the defoamer in an aqueous mixture by 2 to 4 times compared to that which is not pre-emulsified, and enabling the droplet size to be fined to 5㎛ or less. Through this, foam generated during the manufacturing process is effectively suppressed, thereby improving production efficiency by 15 to 25%, and the defoamer is uniformly distributed in the final product, providing the effect of solving problems such as stain formation on clothing or reduced texture by more than 90%.
[0022] Sixth, the present invention applies a method of adding glycerin in two stages, wherein 60 to 80 weight percent of the total amount is added in the first stage to gradually increase the viscosity of the mixture to 50 to 150 cp, followed by adding the remaining amount of propylene glycol and then adding the remaining amount of glycerin in the second stage to adjust the viscosity to 200 to 400 cp. This prevents the rapid increase in viscosity that occurs in a batch adding method and enables uniform mixing of the subsequently added 1,2-hexanediol and D-sorbitol. Through this, the incidence of mixing defects is reduced by more than 70%, and the viscosity deviation measured in the upper, middle, and lower layers of the product can be controlled within ±5%.
[0023] Seventh, the present invention applies a sequential addition order in which 1,2-hexanediol is added first and D-sorbitol is added later, but optimizes the addition order by considering the hydrophobic and hydrophilic characteristics of each component, thereby ensuring the stability of the emulsion interface and preventing phase separation. Experimental results show that emulsion stability is improved by 40–55% compared to the case where addition is made in reverse order, and provides the effect of manufacturing a stable product that does not experience phase separation or precipitation even during long-term storage of more than 3 months.
[0024] Eighth, the present invention prepares a second mixture by sufficiently mixing a dialkyl ester ammonium methosulfate cationic surfactant at a temperature of 40 to 50°C for 2 to 5 hours, and then adds an amphoteric surfactant, such as lauramidopropyl betaine or cocamidopropyl betaine, so that the weight ratio of the cationic surfactant to the amphoteric surfactant is 1:1.5 to 1:4, thereby optimizing the formation of coacervates through electrostatic interactions between the two surfactants. Through this, the encapsulation efficiency of the fragrance is improved by 30 to 45% compared to conventional technology, and the loss of fragrance components is reduced by 40 to 55% even in a high-temperature environment of 60 to 80°C in a dryer, thereby providing the effect of imparting a continuous and strong fragrance to the laundry.
[0025] Ninth, the present invention ensures worker safety by maintaining the ethanol concentration in the working environment below the exposure limit under the Occupational Safety and Health Act, by removing volatile organic compounds generated during the ethanol mixing process with a collection efficiency of 85% or more using a HEPA filter or an activated carbon adsorption dust collector. In addition, it provides the effect of reducing the risk of skin irritation by more than 60% by lowering the residual ethanol concentration of the final product to a range of 5 to 8 parts by weight, and reducing the risk of fire and explosion in the manufacturing facility by more than 70%.
[0026] Tenth, the present invention can reduce the loss of volatile components of fragrance by 35–50% compared to room temperature mixing by applying a low-temperature mixing process in which fragrance is mixed at a low temperature of 3–10°C for 5–20 minutes. In addition, by sufficiently allowing the interaction between each component to proceed through a subsequent low-temperature aging process (10–30 hours at 3–10°C) and ensuring that the fragrance is stably encapsulated within a coacervate structure, the invention provides the effect of increasing the fragrance intensity of the final product by 25–40% and improving fragrance persistence by 30–50%.
[0027] Eleventh, the present invention can remove static electricity from the surface of a fabric by more than 95% by applying a pretreatment process using an ionizer after grounding a fabric composed of 30 to 90% by weight of natural pulp and 10 to 70% by weight of viscose fiber, with a basis weight of 40 to 80 g / m². This allows for an improvement in the absorption rate of the composition by 40 to 60% compared to when static electricity is not removed. Through this, the composition is uniformly impregnated into the fabric, thereby reducing the product defect rate caused by uneven impregnation by more than 65% and providing a uniform softening effect and fragrance to the laundry when using a dryer.
[0028] Twelfth, the present invention includes quality verification steps that measure quality indicators such as temperature, pH, viscosity, permeability, electrical conductivity, and dissolved oxygen concentration in real time at each manufacturing stage and transfer only intermediate products that satisfy quality standards to the next stage, thereby reducing the quality deviation of the final product by 55–70% and the defect rate by 50–70% compared to conventional technology. This provides an economic effect of reducing manufacturing costs by 10–20% by improving production yield and reducing rework costs.
[0029] Thirteenth, the present invention can produce a fabric softener composition having a viscosity in the range of 2,500 to 6,000 cp, measured at 25°C with a Brookfield viscometer at a shear rate of 60 rpm through the optimized manufacturing process described above. This viscosity range corresponds to an optimal range where impregnation into fabric is easy, while preventing leakage of the composition during storage and transportation. Furthermore, it provides the effect of providing a stable product in which the viscosity change rate is maintained within ±10% even during long-term storage of more than six months, and phase separation, precipitation, and discoloration do not occur.
[0030] Fourteenth, when the fabric softener sheet manufactured by the manufacturing method according to the present invention is used in a high-temperature environment of 60 to 80°C in a dryer, 0.5 to 2g of the composition is effectively delivered per 1kg of laundry, exhibiting an excellent softening effect, suppressing static electricity generation by more than 80%, increasing fragrance intensity by 25 to 40% compared to conventional products, and improving fragrance longevity by 30 to 50%, thereby providing the effect of maintaining a lingering fragrance on clothing even after 48 hours or more have passed since washing.
[0031] Fifteenth, the present invention can reduce the total manufacturing time by 15 to 25% compared to conventional technology by optimizing the input order and conditions of each raw material and precisely controlling the temperature and stirring speed at each stage, which provides the effect of reducing manufacturing costs by improving production efficiency and reducing energy consumption. In particular, improved processes such as the divided input of citric acid, pre-dissolution of sodium benzoate and D-sorbitol, pre-emulsification of antifoaming agents, and divided input of glycerin each provide a time reduction effect of 5 to 15%, thereby enabling high overall productivity.
[0032] Sixteenth, the manufacturing method according to the present invention minimizes quality deviations caused by the skill level or experience of workers by presenting standardized quality indicators and clear process conditions, and facilitates the introduction of automation systems, thereby providing the effect of stably producing products of consistent quality even during mass production. This leads to the effect of improving product reliability and increasing consumer satisfaction.
[0033] Seventeenth, the present invention provides the effect of preventing air pollution by effectively capturing and removing ethanol volatile substances through an environmentally friendly and safe manufacturing process, ensuring safety in the working environment, and minimizing wastewater generation to comply with environmental regulations. In addition, the use of fabrics made primarily of natural pulp and viscose fibers provides the effect of reducing the environmental burden by improving the biodegradability of the product.
[0034] As described above, the present invention provides significant effects that simultaneously improve product stability, fragrance persistence, flexibility, and manufacturing efficiency through comprehensive process improvements such as multi-stage purified water treatment, stepwise divided input of raw materials, precise control of temperature and stirring conditions, real-time monitoring of quality indicators, and ensuring environmental safety. These effects stem from the unique technical features of the present invention, which are difficult to achieve with prior art. means of solving the problem
[0035] The present invention relates to a method for manufacturing a fabric softener sheet composition for a laundry dryer, comprising: a. a step of producing purified water by sequentially passing raw water through a first mesh filter with a mesh size of 210 or larger, a second activated carbon filter with an activated carbon particle size of 0.5 to 2.0 mm, a third ultraviolet sterilization filter emitting ultraviolet rays with a wavelength of 254 nm, a fourth membrane filter with a pore size of 0.0001 to 0.01 μm, and a fifth final line filter made of SUS316 material with a pore size of 5 to 10 μm, thereby producing purified water having an electrical conductivity of 5 to 15 μS / cm and a total dissolved solid content of 5 to 20 ppm or less as measured at 25°C; b. A step of preparing heated purified water, wherein the purified water is introduced into a double-jacketed heating tank made of SUS304 or SUS316 stainless steel with a capacity of 50 to 500 liters, and the purified water is heated to 40 to 50°C by an indirect heating method by circulating hot water at 60 to 95°C through the double jacket, and then nitrogen gas with a purity of 99.9% or higher and an oxygen content of 10 ppm or less is bubbled at a flow rate of 0.1 to 0.5 L / min for 5 to 15 minutes to prepare heated purified water with a dissolved oxygen concentration of 5 ppm or less as measured by an electrochemical dissolved oxygen meter; c. A step for preparing an aqueous citric acid solution, wherein, while stirring the heated purified water at a speed of 50 to 80 rpm, anhydrous crystalline citric acid powder having a particle diameter in the range of 40 to 75 μm, a moisture content of 0.5 wt% or less, and a purity of 99.5% or more, which has passed through a sieve of 200 to 400 mesh or larger, is added in two stages, wherein in the first stage, 30 to 50 wt% of the total amount of citric acid to be added is added and mixed for 3 to 8 minutes, and in the second stage, the remaining citric acid is slowly added over 2 to 5 minutes while increasing the stirring speed to 100 to 200 rpm and mixed for 8 to 15 minutes to produce an aqueous citric acid solution having a light transmittance of 85% or more at a wavelength of 600 nm measured by a UV-Vis spectrophotometer using a quartz cell with a path length of 10 mm and a pH in the range of 3.0 to 4.0; d.While stirring the above aqueous citric acid solution at a speed of 40 to 60 rpm, a sodium benzoate solution dissolved at a concentration of 10 to 20 wt% in purified water preheated to 35 to 45°C is added over a period of 2 to 8 minutes; an antistatic agent having 80 wt% or more of laurylpyridium chloride as the main component is added; a defoaming agent emulsion, prepared by pre-emulsifying a polydimethylsiloxane-based defoaming agent with a viscosity of 100 to 1,000 cSt measured at 25°C and a molecular weight of 10,000 to 100,000 with propylene glycol in a weight ratio of 1:2 to 1:5, is added; then 60 to 80 wt% of the total amount of glycerin is added as a first step, followed by the remaining amount of propylene glycol, and then the remaining amount of glycerin is added as a second step; and 1,2-hexanediol is added and dissolved at a concentration of 20 to 40 wt% in purified water preheated to 40 to 45°C. A first mixture preparation step of preparing a first mixture by adding a D-sorbitol solution, wherein the viscosity measured at 25°C with a Brookfield viscometer at a shear rate of 60 rpm is 300–600 cp and the pH is in the range of 4.0–5.5; e. A second mixture preparation step of preparing a second mixture by adding a liquid-type dialkyl ester ammonium methosulfate cationic surfactant having two alkyl groups having 12–22 carbon atoms to the first mixture and mixing at 40–50°C for 2–5 hours; f.: A step for preparing a third mixture, wherein an amphoteric surfactant, such as lauramidopropyl betaine or cocamidopropyl betaine, is added to the second mixture, followed by the addition of ethanol and mixing at a speed of 40 to 70 rpm for 0.5 to 4 hours, wherein ethanol volatile substances generated during the mixing process are removed with a collection efficiency of 85% or higher using a HEPA filter or an activated carbon adsorption type dust collector; g. A step for preparing a third mixture, wherein a fragrance is added to the third mixture and low-temperature mixed at 3 to 10°C for 5 to 20 minutes to prepare a fourth mixture; h.A maturation and cooling step of preparing a fabric softener composition having a viscosity of 2,500 to 6,000 cp measured at a shear rate of 60 rpm using a Brookfield viscometer at 25°C by maturing the above-mentioned fourth mixture at 3 to 10°C for 10 to 30 hours and then cooling at 0 to 5°C for 2 to 6 hours; and i. A fabric impregnation step comprising: grounding a fabric composed of 30-90% by weight of natural pulp and 10-70% by weight of viscose fiber, having a basis weight of 40-80 g / m², removing static electricity with an ionizer, applying the fabric softener composition to a thickness of 0.05-2 mm to the surface of the fabric from which static electricity has been removed, and then impregnating it by pressing using a roll laminating method; wherein, based on 100 parts by weight of the total composition, the fabric softener composition comprises 3-12 parts by weight of a liquid dialkyl ester ammonium methosulfate cationic surfactant having two alkyl groups with 12-22 carbon atoms, 10-18 parts by weight of an amphoteric surfactant being lauramidopropyl betaine or cocamidopropyl betaine, 0.5-2.5 parts by weight of propylene glycol, 1-6 parts by weight of citric anhydride, 5-10 parts by weight of glycerin, and 1,2-hexanediol The present invention provides a method for manufacturing a fabric softener sheet composition for a laundry dryer, comprising a total of 100 parts by weight including 0.05 to 0.5 parts by weight of D-sorbitol, 0.2 to 0.8 parts by weight of sodium benzoate, 0.3 to 5 parts by weight of an antistatic agent having 80% or more by weight of laurylpyridium chloride as the main component, 0.05 to 0.8 parts by weight of a polydimethylsiloxane-based defoamer having a viscosity of 100 to 1,000 cSt measured at 25°C, 5 to 8 parts by weight of ethanol, 12 to 18 parts by weight of a fragrance, and the remainder being purified water, wherein the weight ratio of the cationic surfactant to the amphoteric surfactant is 1:1.5 to 1:4.
[0036] At this time, the above a. purified water manufacturing step comprises: a1. a first filtration step in which raw water is passed through a first mesh filter with a pore size of 60 to 75 μm corresponding to 210 to 250 mesh (number of teeth / inch) at a flow rate of 50 to 150 liters per minute to remove suspended solids, rust, and sand larger than 10 μm; a2. a second adsorption filtration step in which the water that has undergone the first filtration step is passed through a second activated carbon filter with an activated carbon particle size of 0.5 to 2.0 mm to adsorb and remove residual chlorine, organic compounds, odor substances, and color substances, wherein the contact time in the second activated carbon filter is maintained at 5 to 15 minutes and the flow rate is adjusted to 30 to 100 liters per minute; a3. a4. A third sterilization step in which the water obtained from the second adsorption filtration step is passed through a third ultraviolet sterilization filter emitting ultraviolet rays of a wavelength of 254 nm to sterilize bacteria, viruses, and microorganisms, wherein the irradiation intensity of the third ultraviolet sterilization filter is maintained at 30~60 mJ / cm², the exposure time is controlled to 3~10 seconds, and the flow rate is controlled to 20~80 liters per minute; a5. A fourth precision filtration step in which the water obtained from the third sterilization step is passed through a fourth membrane filter of a reverse osmosis or ultrafiltration method with a pore size of 0.0001~0.01 μm to remove heavy metal ions, fine impurities, and dissolved solids, wherein the operating pressure of the fourth membrane filter is maintained at 3~8 bar, the flow rate is controlled to 10~50 liters per minute, and the electrical conductivity of the permeate measured at 25°C is 10 μS / cm or less; a6. A fifth final filtration step in which the water that has undergone the above fourth precision filtration step is passed through a fifth final line filter composed of SUS316 material with pores of 5 to 10 μm to finally remove residual fine particles, while controlling the flow rate to 20 to 60 liters per minute; and a6. The electrical conductivity of the purified water that has undergone the above fifth final filtration step, measured at 25°C, is in the range of 5 to 15 μS / cm, the total dissolved solids are 5 to 20 ppm or less, and the pH is 6.5 to 7.5. A quality verification step for selecting only purified water that satisfies quality standards by measuring in real time whether it is within the range; wherein the total manufacturing time of purified water from the first mesh filter to the fifth final line filter is 15 to 40 minutes, and the purified water is stored in a stainless steel storage tank at 3 to 10℃ after manufacturing and then introduced into the b. heated purified water preparation step within 24 hours.
[0037] At this time, the above b. step of preparing heated purified water comprises: b1. a preheating step in which the purified water is introduced into a double-jacketed heating tank made of SUS304 or SUS316 stainless steel with a capacity of 50 to 500 liters, and hot water at 60 to 80°C is circulated inside the double jacket to preheat the purified water to 20 to 30°C by an indirect heating method, while controlling the heating speed at 1 to 3°C per minute; b2. a main heating step in which the purified water that has undergone the preheating step is stirred with a stirrer at a speed of 50 to 100 rpm, and the temperature of the hot water in the double jacket is raised to 80 to 95°C to main heat the purified water to 35 to 45°C, while controlling the heating speed at 0.5 to 2°C per minute and maintaining the temperature deviation inside the heating tank within ±1.5°C; b3. b4. A temperature stabilization step in which the purified water that has undergone the above-mentioned main heating step is continuously stirred while the hot water temperature of the double jacket is finely adjusted to reach a target temperature of 40~50℃, and then the temperature of the purified water is maintained within the target temperature range of ±0.5℃ for 5~15 minutes; b5. A deoxygenation step in which food-grade nitrogen gas with a purity of 99.9% or higher and an oxygen content of 10 ppm or less is bubbled into the heated purified water that has undergone the above-mentioned temperature stabilization step at a flow rate of 0.1~0.5 L / min for 5~15 minutes to reduce the dissolved oxygen concentration measured by an electrochemical dissolved oxygen meter to 5 ppm or less, while maintaining the temperature of the heated purified water within the range of 40~50℃ even during the bubbling; b5. A temperature equalization step in which the heated purified water that has undergone the above deoxygenation step is stirred with the above stirrer at a speed of 80 to 150 rpm for 3 to 10 minutes to equalize the temperature difference of the upper, middle, and lower layers inside the heating tank to within ±0.3℃; and b6.The method includes a heated water quality verification step in which only heated purified water that satisfies quality standards is transferred to the next step by measuring whether the temperature of the heated purified water that has undergone the temperature homogenization step is in the range of 42 to 48°C, the dissolved oxygen concentration measured by an electrochemical dissolved oxygen meter is in the range of 3 to 5 ppm, and the electrical conductivity measured at 25°C is in the range of 5 to 15 μS / cm; wherein the total heating time from the preheating step to the heated water quality verification step is 20 to 50 minutes, and the heated purified water is introduced into the c. citric acid aqueous solution manufacturing step within 1 hour after manufacturing, and the indirect heating method prevents local overheating of the purified water compared to the direct heating method to suppress the precipitation of dissolved minerals, and the deoxygenation treatment by nitrogen gas bubbling prevents oxidation of the subsequently introduced citric acid, glycerin, and fragrance, thereby improving product stability.
[0038] At this time, the above c. step of preparing an aqueous citric acid solution comprises: c1. a citric acid preparation step in which anhydrous crystalline citric acid powder is passed through a 200-400 mesh (number of meshes / inch) sieve to classify the particle diameter to a range of 40-75㎛, and fine citric acid powder having a moisture content of 0.5% by weight or less and a purity of 99.5% or more is selected; c2. a first citric acid dissolution step in which a first citric acid corresponding to 30-50% by weight of the total amount of citric acid to be added is uniformly sprayed onto the surface of the heated purified water while stirring the heated purified water at a speed of 50-80 rpm, and then mixed for 3-8 minutes while increasing the stirring speed to 80-120 rpm so that the solubility of the first citric acid reaches 70-85%; c3. c4. A second citric acid addition step in which, after confirming that the pH of the mixture obtained from the first citric acid dissolution step has decreased to a range of 3.5 to 4.5 by measuring the pH of the mixture using a glass electrode pH meter, a second citric acid corresponding to the remaining amount of 50 to 70% by weight is slowly added over 2 to 5 minutes while maintaining a stirring speed of 100 to 150 rpm to prevent a sudden change in pH; c4. A high-speed stirring dissolution step in which the temperature of the mixture obtained from the second citric acid addition step is raised to 45 to 52°C while increasing the stirring speed to 150 to 200 rpm and vigorously stirring for 8 to 15 minutes, wherein a vortex is formed on the surface of the mixture to cause undissolved particles at the bottom to float, thereby ensuring that the solubility of the citric acid reaches 95% or more; c5. A solubility verification step in which, after reducing the stirring speed of the mixture that has undergone the high-speed stirring dissolution step above to 60~100 rpm, the light transmittance at a wavelength of 600 nm is measured using a UV-Vis spectrophotometer with a quartz cell having an optical path length of 10 mm and confirmed that the transmittance is 85% or higher, no suspended particles are observed upon visual inspection, and the pH measured by a glass electrode pH meter is in the range of 3.0~4.0; c6.A citric acid aqueous solution filtration step in which the citric acid aqueous solution obtained from the above solubility verification step is passed through a stainless mesh filter with pores of 10 to 30 μm to remove undissolved citric acid particles and impurities, while controlling the filtration speed to 20 to 60 liters per minute; and c7. A citric acid aqueous solution quality verification step in which only the citric acid aqueous solution that satisfies quality standards is transferred to the next step by measuring whether the pH of the citric acid aqueous solution obtained from the above citric acid aqueous solution filtration step is in the range of 3.0 to 4.0 using a glass electrode type pH meter, the citric acid concentration measured by titration is in the range of 1 to 8 weight%, the light transmittance at a wavelength of 600 nm measured by a UV-Vis spectrophotometer using a quartz cell with an optical path length of 10 mm is 90% or more, and the temperature is in the range of 42 to 50℃; The method includes, wherein the two-stage divided input method of the citric acid prevents the subsequent denaturation of sodium benzoate, antistatic agent, and glycerin due to a rapid decrease in pH compared to the batch input method, and the method of micronizing the citric acid particles to 200 to 400 mesh reduces manufacturing costs compared to micronizing them to more than 400 mesh while improving the dissolution speed by 20 to 40% compared to the batch input method, the total manufacturing time from the citric acid preparation step to the citric acid aqueous solution quality verification step is 20 to 40 minutes, and the citric acid aqueous solution is introduced into the d. first mixture manufacturing step within 30 minutes after manufacturing.
[0039] At this time, the above d. first mixture preparation step comprises: d1. a sodium benzoate solution prepared by dissolving sodium benzoate powder in purified water preheated to 35~45℃ at a concentration of 10~20% by weight, and then slowly adding the sodium benzoate solution over 2~8 minutes while stirring the aqueous citric acid solution at a speed of 40~60 rpm so that the pH measured by a glass electrode pH meter rises to a range of 3.5~4.5, while maintaining the temperature of the aqueous citric acid solution in a range of 40~48℃ during addition; d2. An antistatic agent dispersion step in which the temperature of the mixture obtained from the sodium benzoate addition step is adjusted to 42~50℃, an antistatic agent having 80% by weight or more of laurylpyridium chloride as the main component is added to the mixture and stirred at a speed of 50~80 rpm for 5~12 minutes, wherein the antistatic agent is uniformly dispersed throughout the mixture so that the light transmittance at a wavelength of 600nm measured by a UV-Vis spectrophotometer using a quartz cell with a path length of 10mm reaches 80% or more; d3. A defoaming agent emulsification and dispersion step in which a polydimethylsiloxane-based defoaming agent, having a viscosity of 100 to 1,000 cSt measured at 25°C and a molecular weight of 10,000 to 100,000, is pre-mixed with propylene glycol in a weight ratio of 1:2 to 1:5 and emulsified to the mixture obtained from the above antistatic agent dispersion step, and stirred at a speed of 60 to 90 rpm for 3 to 8 minutes so that the defoaming agent emulsification step is dispersed into fine droplets of 5 μm or less; d4. A first glycerin input step in which, after reducing the stirring speed of the mixture obtained from the above defoaming agent emulsification dispersion step to 45 to 65 rpm, a first glycerin corresponding to 60 to 80 weight percent of the total glycerin input amount is continuously input over 1 to 4 minutes, and the viscosity of the mixture measured at 25°C with a Brookfield viscometer at a shear rate of 60 rpm is confirmed to rise to 50 to 150 cp; d5.A glycol mixing and injection step in which the remaining amount of propylene glycol is added to the mixture obtained from the first glycerin injection step over a period of 2 to 6 minutes while stirring at a speed of 50 to 75 rpm, and a second glycerin corresponding to the remaining amount of 20 to 40 weight% is additionally added so that the viscosity of the mixture, measured at 25°C with a Brookfield viscometer at a shear rate of 60 rpm, increases to 200 to 400 cp, while maintaining the temperature of the mixture in the range of 43 to 51°C during the injection; d6. A polyalcohol addition step in which 1,2-hexanediol is first added to the mixture obtained from the glycol addition step above and stirred at a speed of 55 to 85 rpm for 3 to 7 minutes, then a D-sorbitol solution prepared by dissolving D-sorbitol powder in purified water preheated to 40 to 45°C at a concentration of 20 to 40 wt% is added and stirred at a speed of 60 to 90 rpm for 5 to 10 minutes to ensure that the D-sorbitol is completely dispersed; d7. A final homogenization stirring step in which the stirring speed of the mixture obtained from the polyalcohol addition step above is increased to 80 to 120 rpm and the temperature of the mixture is adjusted to 45 to 52°C, and then vigorously stirred for 10 to 20 minutes to homogenize the mixture so that the viscosity deviation measured at a shear rate of 60 rpm using a Brookfield viscometer at 25°C of samples taken from the upper, middle, and lower layers of the mixture is within ±5%; and d8. The pH of the first mixture, which has undergone the final homogenization stirring step, measured by a glass electrode pH meter is 4.0 to 5.A first mixture quality verification step in which only the first mixture satisfying quality standards is transferred to the next step by measuring whether sodium benzoate, antistatic agent, defoamer, glycerin, propylene glycol, 1,2-hexanediol, and D-sorbitol are uniformly dispersed within a deviation of ±3% relative to their respective target concentrations, wherein the viscosity measured with a Brookfield viscometer at a shear rate of 60 rpm at 25℃ is in the range of 5, the light transmittance at a wavelength of 600 nm measured with a UV-Vis spectrophotometer using a quartz cell with an optical path length of 10 mm is 70% or higher, the temperature is in the range of 43~50℃; Including, pre-dissolving the sodium benzoate and D-sorbitol in an aqueous solution with a concentration of 10 to 40 wt% reduces the dissolution time by 30 to 50% compared to direct input in powder form and prevents particle aggregation; pre-emulsifying the defoamer with propylene glycol in a weight ratio of 1:2 to 1:5 improves dispersibility in an aqueous mixture by 2 to 4 times compared to when not pre-emulsified and refines the defoamer droplet size to 5㎛ or less, thereby increasing the efficiency of suppressing foam generation; the two-stage split input method of the glycerin involves adding 60 to 80 wt% in the first stage to gradually increase the viscosity to 50 to 150 cp, and then adding the remaining amount in the second stage to adjust the viscosity to 200 to 400 cp, thereby preventing a rapid increase in viscosity compared to the batch input method and enabling uniform mixing of the subsequently added 1,2-hexanediol and D-sorbitol; and adding the 1,2-hexanediol first and the D-sorbitol The sequential addition order that follows is optimized for interfacial stability by considering the hydrophobic properties of the 1,2-hexanediol and the hydrophilic properties of the D-sorbitol, and the total manufacturing time from the sodium benzoate addition step to the first mixture quality verification step is 35 to 75 minutes, and the first mixture is added to the e. second mixture manufacturing step within 1 hour after manufacturing. Effects of the invention
[0040] The method for manufacturing kimchi using anchovy salted fish paste complex broth according to the present invention exhibits the following significant effects.
[0041] First, the present invention has the effect of achieving a significantly superior flavor compared to conventional kimchi made using only anchovy broth or salted anchovies, by preparing a complex broth using anchovy salted anchovies, anchovies, and vegetables together, thereby harmonizing the deep umami derived from the fermentation of the salted anchovies with the natural sweetness and aroma of the vegetables. As a result of sensory evaluation, the kimchi according to the present invention received an average score more than 25% higher than kimchi made by conventional methods in terms of umami, depth of flavor, and overall taste harmony.
[0042] Second, the present invention allows for the maximum utilization of umami components, such as free amino acids, nucleic acid components, and taurine, which are abundantly contained in the heads and intestines of anchovies, by using anchovies without removing their heads and intestines. At the same time, by omitting the task of cleaning the anchovies, the process time can be shortened by approximately 30% and productivity can be improved. In addition, by heating at 100°C or higher for 20 minutes or more, off-flavors that may occur in the heads and intestines of anchovies can be effectively removed, thereby achieving a clean taste.
[0043] Third, the present invention applies a two-stage temperature extraction method in which radish, green onion, and onion are first extracted at a low temperature of 65°C to 75°C for 12 to 14 minutes in the vegetable extraction stage, and then anchovies and anchovy salted fish paste are extracted by raising the temperature to 100°C to 105°C for 22 to 28 minutes in the high-temperature heating stage. This allows heat-sensitive sugar components and water-soluble vitamins of vegetables to be preserved and extracted at low temperatures, while umami components of anchovies can be effectively extracted at high temperatures, thereby maximizing both the nutritional value and flavor of the complex broth.
[0044] Fourth, the present invention ensures food safety by effectively killing microorganisms such as general bacteria, coliforms, yeast, and mold by heating at a temperature of 100°C to 105°C for 22 to 28 minutes when preparing complex broth, and accordingly, the refrigerated storage period of the complex broth is extended by more than 2 times compared to conventional methods, and the quality can be maintained for more than 7 days when refrigerated at 4°C from room temperature.
[0045] Fifth, the present invention includes a process of first cooling the complex broth to remove oil components and solid precipitates, and then harmonizing it at a medium temperature of 48°C to 52°C for 55 to 65 minutes. This allows the fermented umami components derived from anchovy paste and the sugar and vitamin components extracted from vegetables to combine and stabilize, thereby making the flavor of the complex broth deeper and more harmonious, and removing off-flavors to achieve a clean aftertaste. It was confirmed that the complex broth that has undergone this medium-temperature harmonizing aging step has a free glutamic acid content that increases by about 15% and an inosinic acid content that increases by about 20% compared to a broth that has not undergone this process.
[0046] Sixth, the present invention has the effect of imparting umami to the cabbage itself and improving the harmony of flavors between the cabbage and the seasoning, thereby making the overall flavor of the kimchi uniform and deep, by using a complex broth pickling liquid mixed with sun-dried salt when pickling cabbage and immersing it at 17°C to 21°C for 6 to 7 hours and 30 minutes, fermented components derived from anchovy fish sauce, enzyme components derived from radish, and free amino acids penetrate into the tissue of the pickled cabbage.
[0047] Seventh, the present invention adopts a stepwise addition method in which, when preparing kimchi seasoning, 45 to 55 parts by weight of complex broth are added first to extract the pigment and capsaicin components of red pepper powder and impart umami to the basic seasoning mixture, glutinous rice paste or wheat flour paste is added, and then 25 to 32 parts by weight of complex broth are added secondarily to adjust the viscosity to 11 Pa·s to 15 Pa·s, thereby simultaneously optimizing the umami and viscosity of the seasoning, resulting in excellent adhesion to the cabbage, even distribution of the seasoning, and the effect of preventing the seasoning from flowing down during the fermentation process.
[0048] Eighth, since the present invention already contains anchovy fish sauce in the complex broth and sufficient fermented umami components are extracted from it, a deep and rich umami flavor can be achieved without adding separate fish sauce or fish sauce when making seasoning, thereby reducing raw material costs by about 20% and reducing sodium content by about 15% compared to conventional methods, thus enabling the production of health-oriented kimchi.
[0049] Ninth, it was confirmed that the number of lactic acid bacteria in kimchi produced according to the present invention increased by about 1.3 to 1.6 times compared to kimchi produced by the conventional method after 3 days of fermentation, indicating that fermentation proceeds more actively. This is believed to be because the enzyme components derived from radish and the fermentation components derived from anchovy salted fish sauce contained in the complex broth promote the proliferation of lactic acid bacteria. In addition, after 7 days of fermentation, the pH is stably maintained in the range of 4.2 to 4.5, which has the effect of extending the quality of the optimal ripening period by about 2 days compared to the conventional method.
[0050] Tenth, the present invention can achieve a unique flavor that harmonizes the sweet and sour taste characteristic of fermented kimchi with a deep umami taste by combining the umami components of the complex broth with organic acids produced by lactic acid bacteria during the fermentation process of kimchi to produce a synergistic effect, and this flavor is stably maintained for up to 10 days of fermentation, thereby extending the optimal consumption period of kimchi.
[0051] Eleventh, the manufacturing method of the present invention does not require special facilities or expensive equipment and can be easily applied in general kimchi manufacturing facilities, thus having very high industrial feasibility. Furthermore, since the temperature and time conditions of each process are clearly set even during mass production, quality uniformity can be maintained, and high-quality kimchi can be produced stably regardless of season or region.
[0052] Twelfth, the present invention has the effect of significantly contributing to the development of the kimchi industry in that it enables the production of high-quality kimchi with a deep and rich umami taste and harmonious flavor—which could not be achieved with conventional kimchi manufacturing methods—and with uniform fermentation and excellent shelf life, by organically combining a series of processes including the optimal preparation of the complex broth as described above, stepwise cooling and harmonious aging, pickling of cabbage using the complex broth pickling liquid, and stepwise addition to the seasoning. Specific details for implementing the invention
[0053] Hereinafter, embodiments are described in detail with reference to the attached drawings. However, various modifications may be made to the embodiments, and thus the scope of the patent application is not limited or restricted by these embodiments. It should be understood that all modifications, equivalents, and substitutions to the embodiments are included within the scope of the rights.
[0054] Specific structural or functional descriptions of the embodiments are disclosed for illustrative purposes only and may be modified and implemented in various forms. Accordingly, the embodiments are not limited to the specific disclosed forms, and the scope of this specification includes modifications, equivalents, or substitutions that fall within the technical concept.
[0055] Terms such as "first" or "second" may be used to describe various components, but these terms should be interpreted solely for the purpose of distinguishing one component from another. For example, the first component may be named the second component, and similarly, the second component may be named the first component.
[0056] When it is stated that a component is "connected" to another component, it should be understood that it may be directly connected to or coupled with that other component, or that there may be other components in between.
[0057] The terms used in the embodiments are for illustrative purposes only and should not be interpreted as intended to be limiting. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as "comprising" or "having" are intended to indicate the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0058] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the embodiments pertain. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0059] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims.
[0060] In the embodiments of the present invention, unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in the embodiments of the present invention.
[0061] The shapes, sizes, ratios, angles, numbers, etc. disclosed in the drawings for explaining embodiments of the present invention are exemplary, and therefore the present invention is not limited to the depicted details. Furthermore, in describing the present invention, if it is determined that a detailed description of related known technology may unnecessarily obscure the essence of the present invention, such detailed description is omitted. Where terms such as "includes," "has," or "is made up" are used in this specification, other parts may be added unless "only" is used. Where a component is expressed in the singular, it includes cases where it includes the plural unless specifically stated otherwise.
[0062] In interpreting the components, they are interpreted to include a margin of error even in the absence of a separate explicit statement.
[0063] The size and thickness of each component shown in the drawings are illustrated for convenience of explanation, and the present invention is not necessarily limited to the size and thickness of the illustrated components.
[0064] The features of each of the various embodiments of the present invention may be combined or combined with one another, either partially or wholly, and as will be fully understood by those skilled in the art, various technical interlocking and operation are possible, and each embodiment may be implemented independently of one another or together in an interlocking relationship.
[0065] The present invention relates to a method for manufacturing a fabric softener sheet composition for a laundry dryer, comprising: a. a step of producing purified water by sequentially passing raw water through a first mesh filter with a mesh size of 210 or larger, a second activated carbon filter with an activated carbon particle size of 0.5 to 2.0 mm, a third ultraviolet sterilization filter emitting ultraviolet rays with a wavelength of 254 nm, a fourth membrane filter with a pore size of 0.0001 to 0.01 μm, and a fifth final line filter made of SUS316 material with a pore size of 5 to 10 μm, thereby producing purified water having an electrical conductivity of 5 to 15 μS / cm and a total dissolved solid content of 5 to 20 ppm or less as measured at 25°C; b. A step of preparing heated purified water, wherein the purified water is introduced into a double-jacketed heating tank made of SUS304 or SUS316 stainless steel with a capacity of 50 to 500 liters, and the purified water is heated to 40 to 50°C by an indirect heating method by circulating hot water at 60 to 95°C through the double jacket, and then nitrogen gas with a purity of 99.9% or higher and an oxygen content of 10 ppm or less is bubbled at a flow rate of 0.1 to 0.5 L / min for 5 to 15 minutes to prepare heated purified water with a dissolved oxygen concentration of 5 ppm or less as measured by an electrochemical dissolved oxygen meter; c. A step for preparing an aqueous citric acid solution, wherein, while stirring the heated purified water at a speed of 50 to 80 rpm, anhydrous crystalline citric acid powder having a particle diameter in the range of 40 to 75 μm, a moisture content of 0.5 wt% or less, and a purity of 99.5% or more, which has passed through a sieve of 200 to 400 mesh or larger, is added in two stages, wherein in the first stage, 30 to 50 wt% of the total amount of citric acid to be added is added and mixed for 3 to 8 minutes, and in the second stage, the remaining citric acid is slowly added over 2 to 5 minutes while increasing the stirring speed to 100 to 200 rpm and mixed for 8 to 15 minutes to produce an aqueous citric acid solution having a light transmittance of 85% or more at a wavelength of 600 nm measured by a UV-Vis spectrophotometer using a quartz cell with a path length of 10 mm and a pH in the range of 3.0 to 4.0; d.While stirring the above aqueous citric acid solution at a speed of 40 to 60 rpm, a sodium benzoate solution dissolved at a concentration of 10 to 20 wt% in purified water preheated to 35 to 45°C is added over a period of 2 to 8 minutes; an antistatic agent having 80 wt% or more of laurylpyridium chloride as the main component is added; a defoaming agent emulsion, prepared by pre-emulsifying a polydimethylsiloxane-based defoaming agent with a viscosity of 100 to 1,000 cSt measured at 25°C and a molecular weight of 10,000 to 100,000 with propylene glycol in a weight ratio of 1:2 to 1:5, is added; then 60 to 80 wt% of the total amount of glycerin is added as a first step, followed by the remaining amount of propylene glycol, and then the remaining amount of glycerin is added as a second step; and 1,2-hexanediol is added and dissolved at a concentration of 20 to 40 wt% in purified water preheated to 40 to 45°C. A first mixture preparation step of preparing a first mixture by adding a D-sorbitol solution, wherein the viscosity measured at 25°C with a Brookfield viscometer at a shear rate of 60 rpm is 300–600 cp and the pH is in the range of 4.0–5.5; e. A second mixture preparation step of preparing a second mixture by adding a liquid-type dialkyl ester ammonium methosulfate cationic surfactant having two alkyl groups having 12–22 carbon atoms to the first mixture and mixing at 40–50°C for 2–5 hours; f.: A step for preparing a third mixture, wherein an amphoteric surfactant, such as lauramidopropyl betaine or cocamidopropyl betaine, is added to the second mixture, followed by the addition of ethanol and mixing at a speed of 40 to 70 rpm for 0.5 to 4 hours, wherein ethanol volatile substances generated during the mixing process are removed with a collection efficiency of 85% or higher using a HEPA filter or an activated carbon adsorption type dust collector; g. A step for preparing a third mixture, wherein a fragrance is added to the third mixture and low-temperature mixed at 3 to 10°C for 5 to 20 minutes to prepare a fourth mixture; h.A maturation and cooling step of preparing a fabric softener composition having a viscosity of 2,500 to 6,000 cp measured at a shear rate of 60 rpm using a Brookfield viscometer at 25°C by maturing the above-mentioned fourth mixture at 3 to 10°C for 10 to 30 hours and then cooling at 0 to 5°C for 2 to 6 hours; and i. A fabric impregnation step comprising: grounding a fabric composed of 30-90% by weight of natural pulp and 10-70% by weight of viscose fiber, having a basis weight of 40-80 g / m², removing static electricity with an ionizer, applying the fabric softener composition to a thickness of 0.05-2 mm to the surface of the fabric from which static electricity has been removed, and then impregnating it by pressing using a roll laminating method; wherein, based on 100 parts by weight of the total composition, the fabric softener composition comprises 3-12 parts by weight of a liquid dialkyl ester ammonium methosulfate cationic surfactant having two alkyl groups with 12-22 carbon atoms, 10-18 parts by weight of an amphoteric surfactant being lauramidopropyl betaine or cocamidopropyl betaine, 0.5-2.5 parts by weight of propylene glycol, 1-6 parts by weight of citric anhydride, 5-10 parts by weight of glycerin, and 1,2-hexanediol The present invention provides a method for manufacturing a fabric softener sheet composition for a laundry dryer, comprising a total of 100 parts by weight including 0.05 to 0.5 parts by weight of D-sorbitol, 0.2 to 0.8 parts by weight of sodium benzoate, 0.3 to 5 parts by weight of an antistatic agent having 80% or more by weight of laurylpyridium chloride as the main component, 0.05 to 0.8 parts by weight of a polydimethylsiloxane-based defoamer having a viscosity of 100 to 1,000 cSt measured at 25°C, 5 to 8 parts by weight of ethanol, 12 to 18 parts by weight of a fragrance, and the remainder being purified water, wherein the weight ratio of the cationic surfactant to the amphoteric surfactant is 1:1.5 to 1:4.
[0066] At this time, the above a. purified water manufacturing step comprises: a1. a first filtration step in which raw water is passed through a first mesh filter with a pore size of 60 to 75 μm corresponding to 210 to 250 mesh (number of teeth / inch) at a flow rate of 50 to 150 liters per minute to remove suspended solids, rust, and sand larger than 10 μm; a2. a second adsorption filtration step in which the water that has undergone the first filtration step is passed through a second activated carbon filter with an activated carbon particle size of 0.5 to 2.0 mm to adsorb and remove residual chlorine, organic compounds, odor substances, and color substances, wherein the contact time in the second activated carbon filter is maintained at 5 to 15 minutes and the flow rate is adjusted to 30 to 100 liters per minute; a3. a4. A third sterilization step in which the water obtained from the second adsorption filtration step is passed through a third ultraviolet sterilization filter emitting ultraviolet rays of a wavelength of 254 nm to sterilize bacteria, viruses, and microorganisms, wherein the irradiation intensity of the third ultraviolet sterilization filter is maintained at 30~60 mJ / cm², the exposure time is controlled to 3~10 seconds, and the flow rate is controlled to 20~80 liters per minute; a5. A fourth precision filtration step in which the water obtained from the third sterilization step is passed through a fourth membrane filter of a reverse osmosis or ultrafiltration method with a pore size of 0.0001~0.01 μm to remove heavy metal ions, fine impurities, and dissolved solids, wherein the operating pressure of the fourth membrane filter is maintained at 3~8 bar, the flow rate is controlled to 10~50 liters per minute, and the electrical conductivity of the permeate measured at 25°C is 10 μS / cm or less; a6. A fifth final filtration step in which the water that has undergone the above fourth precision filtration step is passed through a fifth final line filter composed of SUS316 material with pores of 5 to 10 μm to finally remove residual fine particles, while controlling the flow rate to 20 to 60 liters per minute; and a6. The electrical conductivity of the purified water that has undergone the above fifth final filtration step, measured at 25°C, is in the range of 5 to 15 μS / cm, the total dissolved solids are 5 to 20 ppm or less, and the pH is 6.5 to 7.5. A quality verification step for selecting only purified water that satisfies quality standards by measuring in real time whether it is within the range; wherein the total manufacturing time of purified water from the first mesh filter to the fifth final line filter is 15 to 40 minutes, and the purified water is stored in a stainless steel storage tank at 3 to 10℃ after manufacturing and then introduced into the b. heated purified water preparation step within 24 hours.
[0067] At this time, the above b. step of preparing heated purified water comprises: b1. a preheating step in which the purified water is introduced into a double-jacketed heating tank made of SUS304 or SUS316 stainless steel with a capacity of 50 to 500 liters, and hot water at 60 to 80°C is circulated inside the double jacket to preheat the purified water to 20 to 30°C by an indirect heating method, while controlling the heating speed at 1 to 3°C per minute; b2. a main heating step in which the purified water that has undergone the preheating step is stirred with a stirrer at a speed of 50 to 100 rpm, and the temperature of the hot water in the double jacket is raised to 80 to 95°C to main heat the purified water to 35 to 45°C, while controlling the heating speed at 0.5 to 2°C per minute and maintaining the temperature deviation inside the heating tank within ±1.5°C; b3. b4. A temperature stabilization step in which the purified water that has undergone the above-mentioned main heating step is continuously stirred while the hot water temperature of the double jacket is finely adjusted to reach a target temperature of 40~50℃, and then the temperature of the purified water is maintained within the target temperature range of ±0.5℃ for 5~15 minutes; b5. A deoxygenation step in which food-grade nitrogen gas with a purity of 99.9% or higher and an oxygen content of 10 ppm or less is bubbled into the heated purified water that has undergone the above-mentioned temperature stabilization step at a flow rate of 0.1~0.5 L / min for 5~15 minutes to reduce the dissolved oxygen concentration measured by an electrochemical dissolved oxygen meter to 5 ppm or less, while maintaining the temperature of the heated purified water within the range of 40~50℃ even during the bubbling; b5. A temperature equalization step in which the heated purified water that has undergone the above deoxygenation step is stirred with the above stirrer at a speed of 80 to 150 rpm for 3 to 10 minutes to equalize the temperature difference of the upper, middle, and lower layers inside the heating tank to within ±0.3℃; and b6.The method includes a heated water quality verification step in which only heated purified water that satisfies quality standards is transferred to the next step by measuring whether the temperature of the heated purified water that has undergone the temperature homogenization step is in the range of 42 to 48°C, the dissolved oxygen concentration measured by an electrochemical dissolved oxygen meter is in the range of 3 to 5 ppm, and the electrical conductivity measured at 25°C is in the range of 5 to 15 μS / cm; wherein the total heating time from the preheating step to the heated water quality verification step is 20 to 50 minutes, and the heated purified water is introduced into the c. citric acid aqueous solution manufacturing step within 1 hour after manufacturing, and the indirect heating method prevents local overheating of the purified water compared to the direct heating method to suppress the precipitation of dissolved minerals, and the deoxygenation treatment by nitrogen gas bubbling prevents oxidation of the subsequently introduced citric acid, glycerin, and fragrance, thereby improving product stability.
[0068] At this time, the above c. step of preparing an aqueous citric acid solution comprises: c1. a citric acid preparation step in which anhydrous crystalline citric acid powder is passed through a 200-400 mesh (number of meshes / inch) sieve to classify the particle diameter to a range of 40-75㎛, and fine citric acid powder having a moisture content of 0.5% by weight or less and a purity of 99.5% or more is selected; c2. a first citric acid dissolution step in which a first citric acid corresponding to 30-50% by weight of the total amount of citric acid to be added is uniformly sprayed onto the surface of the heated purified water while stirring the heated purified water at a speed of 50-80 rpm, and then mixed for 3-8 minutes while increasing the stirring speed to 80-120 rpm so that the solubility of the first citric acid reaches 70-85%; c3. c4. A second citric acid addition step in which, after confirming that the pH of the mixture obtained from the first citric acid dissolution step has decreased to a range of 3.5 to 4.5 by measuring the pH of the mixture using a glass electrode pH meter, a second citric acid corresponding to the remaining amount of 50 to 70% by weight is slowly added over 2 to 5 minutes while maintaining a stirring speed of 100 to 150 rpm to prevent a sudden change in pH; c4. A high-speed stirring dissolution step in which the temperature of the mixture obtained from the second citric acid addition step is raised to 45 to 52°C while increasing the stirring speed to 150 to 200 rpm and vigorously stirring for 8 to 15 minutes, wherein a vortex is formed on the surface of the mixture to cause undissolved particles at the bottom to float, thereby ensuring that the solubility of the citric acid reaches 95% or more; c5. A solubility verification step in which, after reducing the stirring speed of the mixture that has undergone the high-speed stirring dissolution step above to 60~100 rpm, the light transmittance at a wavelength of 600 nm is measured using a UV-Vis spectrophotometer with a quartz cell having an optical path length of 10 mm and confirmed that the transmittance is 85% or higher, no suspended particles are observed upon visual inspection, and the pH measured by a glass electrode pH meter is in the range of 3.0~4.0; c6.A citric acid aqueous solution filtration step in which the citric acid aqueous solution obtained from the above solubility verification step is passed through a stainless mesh filter with pores of 10 to 30 μm to remove undissolved citric acid particles and impurities, while controlling the filtration speed to 20 to 60 liters per minute; and c7. A citric acid aqueous solution quality verification step in which only the citric acid aqueous solution that satisfies quality standards is transferred to the next step by measuring whether the pH of the citric acid aqueous solution obtained from the above citric acid aqueous solution filtration step is in the range of 3.0 to 4.0 using a glass electrode type pH meter, the citric acid concentration measured by titration is in the range of 1 to 8 weight%, the light transmittance at a wavelength of 600 nm measured by a UV-Vis spectrophotometer using a quartz cell with an optical path length of 10 mm is 90% or more, and the temperature is in the range of 42 to 50℃; The method includes, wherein the two-stage divided input method of the citric acid prevents the subsequent denaturation of sodium benzoate, antistatic agent, and glycerin due to a rapid decrease in pH compared to the batch input method, and the method of micronizing the citric acid particles to 200 to 400 mesh reduces manufacturing costs compared to micronizing them to more than 400 mesh while improving the dissolution speed by 20 to 40% compared to the batch input method, the total manufacturing time from the citric acid preparation step to the citric acid aqueous solution quality verification step is 20 to 40 minutes, and the citric acid aqueous solution is introduced into the d. first mixture manufacturing step within 30 minutes after manufacturing.
[0069] At this time, the above d. first mixture preparation step comprises: d1. a sodium benzoate solution prepared by dissolving sodium benzoate powder in purified water preheated to 35~45℃ at a concentration of 10~20% by weight, and then slowly adding the sodium benzoate solution over 2~8 minutes while stirring the aqueous citric acid solution at a speed of 40~60 rpm so that the pH measured by a glass electrode pH meter rises to a range of 3.5~4.5, while maintaining the temperature of the aqueous citric acid solution in a range of 40~48℃ during addition; d2. An antistatic agent dispersion step in which the temperature of the mixture obtained from the sodium benzoate addition step is adjusted to 42~50℃, an antistatic agent having 80% by weight or more of laurylpyridium chloride as the main component is added to the mixture and stirred at a speed of 50~80 rpm for 5~12 minutes, wherein the antistatic agent is uniformly dispersed throughout the mixture so that the light transmittance at a wavelength of 600nm measured by a UV-Vis spectrophotometer using a quartz cell with a path length of 10mm reaches 80% or more; d3. A defoaming agent emulsification and dispersion step in which a polydimethylsiloxane-based defoaming agent, having a viscosity of 100 to 1,000 cSt measured at 25°C and a molecular weight of 10,000 to 100,000, is pre-mixed with propylene glycol in a weight ratio of 1:2 to 1:5 and emulsified to the mixture obtained from the above antistatic agent dispersion step, and stirred at a speed of 60 to 90 rpm for 3 to 8 minutes so that the defoaming agent emulsification step is dispersed into fine droplets of 5 μm or less; d4. A first glycerin input step in which, after reducing the stirring speed of the mixture obtained from the above defoaming agent emulsification dispersion step to 45 to 65 rpm, a first glycerin corresponding to 60 to 80 weight percent of the total glycerin input amount is continuously input over 1 to 4 minutes, and the viscosity of the mixture measured at 25°C with a Brookfield viscometer at a shear rate of 60 rpm is confirmed to rise to 50 to 150 cp; d5.A glycol mixing and injection step in which the remaining amount of propylene glycol is added to the mixture obtained from the first glycerin injection step over a period of 2 to 6 minutes while stirring at a speed of 50 to 75 rpm, and a second glycerin corresponding to the remaining amount of 20 to 40 weight% is additionally added so that the viscosity of the mixture, measured at 25°C with a Brookfield viscometer at a shear rate of 60 rpm, increases to 200 to 400 cp, while maintaining the temperature of the mixture in the range of 43 to 51°C during the injection; d6. A polyalcohol addition step in which 1,2-hexanediol is first added to the mixture obtained from the glycol addition step above and stirred at a speed of 55 to 85 rpm for 3 to 7 minutes, then a D-sorbitol solution prepared by dissolving D-sorbitol powder in purified water preheated to 40 to 45°C at a concentration of 20 to 40 wt% is added and stirred at a speed of 60 to 90 rpm for 5 to 10 minutes to ensure that the D-sorbitol is completely dispersed; d7. A final homogenization stirring step in which the stirring speed of the mixture obtained from the polyalcohol addition step above is increased to 80 to 120 rpm and the temperature of the mixture is adjusted to 45 to 52°C, and then vigorously stirred for 10 to 20 minutes to homogenize the mixture so that the viscosity deviation measured at a shear rate of 60 rpm using a Brookfield viscometer at 25°C of samples taken from the upper, middle, and lower layers of the mixture is within ±5%; and d8. The pH of the first mixture, which has undergone the final homogenization stirring step, measured by a glass electrode pH meter is 4.0 to 5.A first mixture quality verification step in which only the first mixture satisfying quality standards is transferred to the next step by measuring whether sodium benzoate, antistatic agent, defoamer, glycerin, propylene glycol, 1,2-hexanediol, and D-sorbitol are uniformly dispersed within a deviation of ±3% relative to their respective target concentrations, wherein the viscosity measured with a Brookfield viscometer at a shear rate of 60 rpm at 25℃ is in the range of 5, the light transmittance at a wavelength of 600 nm measured with a UV-Vis spectrophotometer using a quartz cell with an optical path length of 10 mm is 70% or higher, the temperature is in the range of 43~50℃; Including, pre-dissolving the sodium benzoate and D-sorbitol in an aqueous solution with a concentration of 10 to 40 wt% reduces the dissolution time by 30 to 50% compared to direct input in powder form and prevents particle aggregation; pre-emulsifying the defoamer with propylene glycol in a weight ratio of 1:2 to 1:5 improves dispersibility in an aqueous mixture by 2 to 4 times compared to when not pre-emulsified and refines the defoamer droplet size to 5㎛ or less, thereby increasing the efficiency of suppressing foam generation; the two-stage split input method of the glycerin involves adding 60 to 80 wt% in the first stage to gradually increase the viscosity to 50 to 150 cp, and then adding the remaining amount in the second stage to adjust the viscosity to 200 to 400 cp, thereby preventing a rapid increase in viscosity compared to the batch input method and enabling uniform mixing of the subsequently added 1,2-hexanediol and D-sorbitol; and adding the 1,2-hexanediol first and the D-sorbitol The sequential addition order that follows is optimized for interfacial stability by considering the hydrophobic properties of the 1,2-hexanediol and the hydrophilic properties of the D-sorbitol, and the total manufacturing time from the sodium benzoate addition step to the first mixture quality verification step is 35 to 75 minutes, and the first mixture is added to the e. second mixture manufacturing step within 1 hour after manufacturing.
[0070] Reasons for selecting each material and technical significance
[0071] Each material constituting the fabric softener sheet composition for a laundry dryer according to the present invention was carefully selected by comprehensively considering its physicochemical properties and functions in order to optimize product performance, ensure stability, and guarantee user safety. The reasons for selecting each material and its technical significance are explained in detail as follows.
[0072] 1. Reason for Selecting Purified Water and Technical Significance
[0073] In the present invention, instead of ordinary tap water or simple purified water, high-purity purified water that has undergone a five-stage multi-stage filtering process, has an electrical conductivity of 5 to 15 μS / cm and a total dissolved solid content of 5 to 20 ppm or less, is used as the remaining component of the overall composition. The purified water serves as the basic medium of the composition to dissolve or disperse each component and is a major component accounting for about 40 to 60 parts by weight of the final product.
[0074] The first reason for selecting purified water is to prevent the formation of precipitates of cationic surfactants caused by metal ions. Ordinary tap water contains divalent or trivalent metal ions, such as calcium, magnesium, and iron, at levels ranging from tens to hundreds of ppm. These metal ions undergo electrostatic reactions with cationic surfactants, such as dialkyl ester ammonium methosulfate, to form insoluble salts. These precipitates not only cloud the appearance of the product and reduce its softening effect but can also clog nozzles or rollers during fabric impregnation, potentially causing problems in the production process. The high-purity purified water of the present invention has a metal ion concentration controlled to 1 ppm or less, thereby fundamentally preventing these problems.
[0075] The second reason for selecting purified water is to prevent product spoilage caused by microbial contamination. Although ordinary tap water has undergone chlorine treatment, residual bacteria or spores may remain at a certain level. In particular, if the storage temperature is high or the product is stored for a long period, these microorganisms may multiply, leading to discoloration, foul odors, and changes in pH of the product. In this invention, microbiological stability is ensured by sterilizing bacteria, viruses, and microorganisms using a 254nm wavelength ultraviolet sterilization filter. An ultraviolet irradiation intensity of 30–60 mJ / cm² is a level that inactivates more than 99.9% of most pathogenic microorganisms and is a proven sterilization method widely used in the manufacture of food and pharmaceuticals.
[0076] The third reason for selecting purified water is to ensure the transparency and color stability of the product by removing organic matter and color substances. Ordinary tap water may contain natural organic substances such as humic acid and humic acid, as well as pigment substances derived from algae; these substances can cause the product's appearance to turn yellowish-brown and distort the scent of the fragrance. In this invention, colorless and odorless purified water was secured by adsorbing and removing organic compounds, odor substances, and color substances using an activated carbon filter with a particle size of 0.5 to 2.0 mm. Setting the activated carbon contact time to 5 to 15 minutes is the optimal condition to ensure sufficient time to reach adsorption equilibrium while preventing a decrease in productivity caused by excessive retention.
[0077] The fourth reason for selecting purified water is to remove fine impurities and dissolved solids to prevent nozzle clogging during fabric impregnation and to ensure product uniformity. In this invention, a membrane filter with a pore size of 0.0001 to 0.01 μm is used to remove colloidal particles, fine impurities, and dissolved solids, thereby reducing the total dissolved solids to 5 to 20 ppm or less. Purified water of this level is of high purity comparable to semiconductor cleaning water or injectable water, and since clogging does not occur even during the process of spraying the composition onto the fabric through a fine nozzle, production stability can be ensured.
[0078] The reason the content of purified water is set as the remainder is to ensure that the total weight of the composition always remains 100 parts by weight by filling the remainder with purified water after optimizing the concentrations of all other active ingredients. The actual content of purified water varies depending on the sum of the other ingredients, but generally falls within the range of 40 to 60 parts by weight; this is the optimal range that ensures the concentration of each active ingredient is sufficient to exert its effect while maintaining the composition's appropriate viscosity.
[0079] In addition, the present invention prevents microbial re-contamination during storage or changes in pH caused by the dissolution of carbon dioxide in the air by stipulating that purified water be stored in a stainless steel storage tank at 3 to 10°C after production and used within 24 hours. Low-temperature storage is an effective method for inhibiting the growth of microorganisms and maintaining chemical stability, and the regulation to use within 24 hours ensures that the produced purified water is used in product manufacturing before its quality deteriorates.
[0080] 2. Reasons for Selecting Anhydrous Citric Acid and Technical Significance
[0081] In the present invention, anhydrous crystalline citric acid is used as a pH adjuster in a ratio of 1 to 6 parts by weight based on 100 parts by weight of the total composition. Citric acid is a weakly acidic organic acid with three carboxyl groups, with the chemical name 2-hydroxy-1,2,3-propanetricarboxylic acid, and is a substance whose safety has been verified in the fields of food, pharmaceuticals, and cosmetics.
[0082] The first reason for selecting citric acid is to optimize the stability of cationic surfactants by adjusting the pH of the composition to a weakly acidic range. Cationic surfactants with ester bonds, such as dialkyl ester ammonium methosulfate, undergo hydrolysis under strong alkaline conditions, which reduces their effectiveness, whereas at excessively low pH, some additives may precipitate or denature. In the present invention, optimal conditions were secured in which all components remain stable by using citric acid to adjust the pH of the final composition to a range of 4.5 to 5.5. A citric acid concentration of 1 to 6 parts by weight is the appropriate concentration for achieving this pH range, as confirmed experimentally.
[0083] The second reason for selecting citric acid is to inactivate trace amounts of residual metal ions by forming chelate complexes with them. Even when using high-purity purified water, there is a possibility that minute amounts of metal ions may leach from stainless steel pipes or tanks during the manufacturing process, and some raw materials themselves may contain metal ions as impurities. Citric acid forms stable, water-soluble chelate complexes with metal ions such as calcium, magnesium, and iron through its three carboxyl groups and one hydroxyl group, thereby preventing these metal ions from reacting with cationic surfactants. This chelating effect plays a crucial role in improving the long-term stability of the product and preventing discoloration or precipitation.
[0084] The third reason for selecting citric acid is to prevent abrupt changes in pH by providing buffering capacity. Citric acid has a three-step dissociation equilibrium with pKa values of 3.13, 4.76, and 6.40, and exhibits excellent buffering capacity within the pH range of 4.5 to 5.5 of the composition of the present invention. This prevents abrupt changes in pH when various ingredients are added during the manufacturing process and ensures that the pH remains stable even if trace amounts of acid or base are mixed in during storage. pH stability is an essential factor in maintaining product quality consistency.
[0085] The fourth reason for selecting citric acid is that it is suitable for use in products that come into contact with clothing due to its excellent skin compatibility and safety. Citric acid is a naturally occurring component in citrus fruits and is widely used as a food additive; it is also widely used in cosmetics and detergents due to its very low skin irritation and toxicity. Since the product of the present invention comes into direct contact with clothing in a dryer, skin safety is particularly important, and citric acid perfectly meets these requirements.
[0086] The reason for selecting the anhydrous crystalline form is that it has a low moisture content of 0.5% by weight or less, so it does not add unnecessary moisture to the composition, and it has high solubility and excellent stability. Compared to monohydrate citric acid, anhydrous citric acid provides more citric acid on an equal weight basis, allowing for precise pH control, and it also has excellent storage stability due to its low hygroscopicity. The classification into particle diameters ranging from 40 to 75㎛ is intended to optimize the dissolution rate and prevent scattering when added to heated purified water; excessively fine particles can scatter and impair the working environment, while excessively large particles have a slow dissolution rate, which can extend the manufacturing time.
[0087] The reason for adopting a two-stage divided injection method for citric acid is to prevent the denaturation of subsequent components caused by a rapid decrease in pH and to improve dissolution efficiency. The method of adding 30–50% by weight of the total amount in the first stage to adjust the pH to approximately 4.0, and then adding the remaining amount in the second stage to lower the final pH to the range of 3.0–4.0, ensures sufficient time for the citric acid to dissolve at each stage while preventing excessive local acidification. This stepwise approach contributes to securing a transparent appearance by increasing the transmittance of the final aqueous citric acid solution to over 85%.
[0088] 3. Reasons for Selecting Sodium Benzoate and Technical Significance
[0089] In the present invention, sodium benzoate is used as a preservative in a ratio of 0.3 to 5 parts by weight based on 100 parts by weight of the total composition. Sodium benzoate, with the chemical name sodium benzoate, is a sodium salt of benzoic acid and is one of the most widely used preservatives in the fields of food, pharmaceuticals, and cosmetics.
[0090] The first reason for selecting sodium benzoate is that it exhibits excellent antibacterial effects under acidic conditions. Sodium benzoate dissociates in aqueous solution to produce benzoate ions and sodium ions, and under acidic conditions with a pH of 4.5 or lower, some of it exists as undissociated benzoic acid. Undissociated benzoic acid passes through the cell membrane of microorganisms, penetrates into the cell, lowers the intracellular pH, and disrupts metabolic processes, thereby exhibiting an antibacterial effect. Since the composition of the present invention maintains the pH within the range of 4.0 to 5.5 by means of citric acid, it provides optimal conditions for sodium benzoate to function effectively.
[0091] The second reason for selecting sodium benzoate is that it has a broad antimicrobial spectrum and is effective against various microorganisms. Sodium benzoate exhibits growth inhibitory effects not only on bacteria but also on yeasts and molds, and shows strong activity, particularly against aerobic bacteria and fungi. Since fabric softener compositions contain organic components and moisture, there is a risk of microbial contamination; therefore, the use of a preservative with a broad antimicrobial effect is essential. A sodium benzoate concentration of 0.3 to 5 parts by weight is an appropriate range that effectively inhibits microbial growth while minimizing the risk of skin irritation caused by excessive use.
[0092] The third reason for selecting sodium benzoate is its excellent thermal and pH stability, which allows it to remain stable without decomposing during manufacturing processes and storage conditions. In the manufacturing process of the present invention, temperatures of 40 to 50°C are applied at some stages, and the final product must be stored at room temperature for an extended period. Since sodium benzoate does not decompose at temperatures below 100°C and exists stably within a pH range of 3 to 7, it is suitable for the manufacturing and storage conditions of the present invention. This ensures a continuous preservative effect throughout the shelf life of the product.
[0093] The fourth reason for selecting sodium benzoate is that it is a substance with guaranteed skin safety and approved by regulatory agencies. Sodium benzoate is authorized worldwide for use as a food additive and cosmetic ingredient, and at appropriate concentrations, the likelihood of skin irritation or allergy induction is very low. Since the product of this invention comes into indirect contact with the skin through clothing, the use of a preservative with verified safety is important. As sodium benzoate is a substance whose safety has been proven through decades of usage history, it can secure consumer trust.
[0094] The reason for adopting the method of pre-dissolving sodium benzoate in purified water preheated to 35–45°C at a concentration of 10–20% by weight before adding it is to shorten the dissolution time and achieve uniform dispersion. The solubility of sodium benzoate in water increases with temperature, exhibiting a solubility of approximately 50g / 100mL at around 40°C. The pre-dissolution method reduces the dissolution time by 30–50% compared to directly adding the powder and prevents the phenomenon of powder particles aggregating to form lumps. A concentration of 10–20% by weight is the optimal concentration that allows for complete dissolution to form a transparent solution without being excessively diluted, thereby minimizing unnecessary moisture in the composition.
[0095] The reason the sodium benzoate content was set to 0.3 to 5 parts by weight is to consider the minimum effective concentration and the maximum allowable concentration. Below 0.3 parts by weight, the inhibitory effect on microbial growth is insufficient, so the preservation stability of the product cannot be guaranteed, and above 5 parts by weight, the risk of skin irritation increases and there is a possibility of allergic reactions in some consumers. Preferably, using it within the range of 0.5 to 3 parts by weight best achieves a balance between efficacy and safety.
[0096] 4. Reasons for Selecting Laurylpyridium Chloride Antistatic Agent and Technical Significance
[0097] In the present invention, an antistatic agent having 80% or more by weight of laurylpyridium chloride as the main component is used in a ratio of 0.2 to 3 parts by weight based on 100 parts by weight of the total composition. Laurylpyridium chloride is a quaternary ammonium compound and a cationic surfactant, and is a multifunctional substance that simultaneously exhibits bactericidal and antistatic effects.
[0098] The first reason for selecting Laurylpyridium Chloride is that it provides excellent antistatic effects. Static electricity is generated due to friction between fibers when drying clothes in a dryer, which can cause garments to stick together or induce unpleasant electric shocks when worn. Laurylpyridium Chloride neutralizes surface charges by adsorbing cationic head groups onto negatively charged areas on the fiber surface, while hydrophobic hydrocarbon chains form a thin film on the fiber surface to suppress charge generation during friction. Additionally, it enhances hygroscopicity, forming a fine layer of moisture on the fiber surface to provide a pathway for releasing static electricity into the air.
[0099] The second reason for selecting laurylpyridium chloride is that it provides an antimicrobial effect, exhibiting a synergistic effect with sodium benzoate. Laurylpyridium chloride has a quaternary ammonium structure, and its positively charged nitrogen atoms exert an antimicrobial effect by destroying the cell membrane through electrostatic interactions with the negatively charged cell membrane of bacteria. Since this mechanism of action differs from the metabolic inhibition mechanism of sodium benzoate, the combined use of the two substances can achieve a more powerful and broad-spectrum preservative effect. In particular, it can establish an effective dual defense system even against some resistant microorganisms.
[0100] The third reason for selecting laurylpyridium chloride is its excellent compatibility with dialkyl ester ammonium methosulfate, a cationic surfactant. Since both substances are cationic, electrostatic repulsion may occur when mixed; however, by limiting the content of laurylpyridium chloride to 0.2 to 3 parts by weight, additional antistatic and antibacterial effects can be provided without impairing the function of the main surfactant. Experimental results confirmed that within this concentration range, the two substances mix stably without precipitation or phase separation.
[0101] The fourth reason for selecting laurylpyridium chloride is that its structural characteristics are optimized. The lauryl group is a straight-chain alkyl group with 12 carbon atoms, providing an appropriate balance of adsorption to fibers and the ability to form a hydrophobic film. If the number of carbon atoms is too short, hydrophobicity is insufficient, resulting in a weak antistatic effect; if it is too long, solubility in water decreases, compromising product stability. Pyridinium cations have less steric hindrance than quaternary ammonium cations, allowing them to be efficiently arranged on the fiber surface. This enables effective antistatic performance with a smaller amount.
[0102] The reason for using an antistatic agent with 80% by weight or more of laurylpyridium chloride as the main component is to secure high-purity active ingredients. Commercially available laurylpyridium chloride products are generally supplied in the form of aqueous solutions or powders with a concentration of 80–95%, with the remainder consisting of stabilizers or solvents. By requiring a purity of 80% by weight or more, it is possible to ensure a sufficient concentration of active ingredients to exhibit an antistatic effect while minimizing side effects caused by impurities.
[0103] The reason for setting the content of laurylpyridium chloride to 0.2 to 3 parts by weight is to strike a balance between antistatic effect and skin safety. Below 0.2 parts by weight, the antistatic effect is insufficient, which may cause consumers to experience discomfort due to static electricity; above 3 parts by weight, the excessive amount of cationic substances increases the likelihood of skin irritation or allergic reactions in some consumers. Preferably, using it within the range of 0.5 to 2 parts by weight provides optimal performance and safety.
[0104] 5. Reasons for Selection and Technical Significance of Polydimethylsiloxane-based Antifoaming Agents
[0105] In the present invention, a polydimethylsiloxane-based defoaming agent having a viscosity of 100 to 1,000 cSt measured at 25°C and a molecular weight of 10,000 to 100,000 is used as a defoaming agent in a ratio of 0.05 to 0.8 parts by weight based on 100 parts by weight of the total composition. Polydimethylsiloxane is also known as silicone oil and is a synthetic polymer having a structure in which methyl groups are bonded to a main chain formed by Si-O bonds.
[0106] The primary reason for selecting polydimethylsiloxane-based defoaming agents is their excellent defoaming efficiency. During the manufacturing process of fabric softener compositions, foam is prone to form due to the mixing of surfactants and various additives; in particular, excessive foam can be generated during high-speed stirring stages, leading to inefficient tank volume utilization and hindering accurate metering. Polydimethylsiloxane possesses very low surface tension, allowing it to penetrate the foam film and locally reduce surface tension, thereby inducing the rupture of the foam film. Additionally, its strong hydrophobicity repels moisture from the foam film, thereby reducing foam stability.
[0107] The second reason for selecting a polydimethylsiloxane-based defoamer is its excellent chemical stability and its non-reaction with other components. The Si-O bond is a very stable bond that is resistant to acids, bases, and oxidizing agents, and it does not react with citric acid, cationic surfactants, alcohols, etc., included in the composition of the present invention. This means that the effectiveness of the defoamer is maintained even during long-term storage and does not affect the stability of other components. It also has excellent thermal stability, so it does not decompose or deteriorate even under the temperature conditions of 40 to 50°C in the manufacturing process.
[0108] The third reason for selecting a polydimethylsiloxane-based defoamer is its excellent skin safety and biocompatibility. Polydimethylsiloxane is a substance whose safety has been verified to the extent that it is used in medical implants, cosmetics, and food additives, and it has a very low potential for skin irritation or allergy induction. Since the product of this invention comes into indirect contact with the skin through clothing, the use of a defoamer with guaranteed safety is essential. Furthermore, because polydimethylsiloxane is colorless and odorless, it does not affect the appearance or scent of the product.
[0109] The reason for limiting the viscosity to the range of 100 to 1,000 cSt is to balance defoaming efficiency and dispersibility. Low-viscosity polydimethylsiloxanes with a viscosity of less than 100 cSt are too fluid, so while they penetrate the foam film quickly, their sustained defoaming effect is weak. Conversely, high-viscosity products exceeding 1,000 cSt have excellent defoaming effects but are difficult to disperse in aqueous mixtures and may form large droplets, leading to uneven distribution. The range of 100 to 1,000 cSt is the optimal range for achieving effective defoaming performance while maintaining appropriate fluidity.
[0110] The reason for limiting the molecular weight to the range of 10,000 to 100,000 is to optimize physical properties and stability. Low molecular weight polydimethylsiloxanes with a molecular weight of less than 10,000 have high volatility and may be lost during manufacturing and storage, while high molecular weight products exceeding 100,000 have excessively high viscosity, making them difficult to handle and emulsify. The range of 10,000 to 100,000 is a range that ensures long-term stability without volatile loss while maintaining appropriate viscosity.
[0111] The reason for adopting a method in which a polydimethylsiloxane-based defoamer is pre-emulsified with propylene glycol at a weight ratio of 1:2 to 1:5 before addition is to improve dispersibility in aqueous mixtures. Since polydimethylsiloxane possesses strong hydrophobicity, direct addition to water causes it to aggregate into large droplets for uneven distribution, with some floating to the surface and failing to exert its effect. Propylene glycol is an amphiphilic solvent possessing both water-soluble and oil-soluble properties; therefore, pre-mixing it with polydimethylsiloxane allows for a certain level of emulsification to be achieved without the need for surfactants. The weight ratio of 1:2 to 1:5 is the optimal ratio that ensures sufficient dissolution or dispersion of polydimethylsiloxane in propylene glycol without a decrease in effectiveness due to excessive dilution. When this defoamer emulsion is added to an aqueous mixture, it disperses into fine droplets of 5㎛ or less, providing a uniform defoaming effect.
[0112] The reason the content of the polydimethylsiloxane-based defoamer was set to 0.05 to 0.8 parts by weight is to account for the minimum effective concentration and side effects caused by excessive use. Less than 0.05 parts by weight makes it difficult to effectively suppress foam generated during the manufacturing process, while exceeding 0.8 parts by weight can affect the texture of the final product, resulting in a slippery or greasy feeling. Preferably, using it within the range of 0.1 to 0.5 parts by weight best achieves a balance between effectiveness and texture.
[0113] 6. Reasons for Selecting Propylene Glycol and Technical Significance
[0114] In the present invention, propylene glycol is used as a moisturizer and solvent in a ratio of 0.5 to 2.5 parts by weight based on 100 parts by weight of the total composition. Propylene glycol is an alcohol with two hydroxyl groups, with the chemical name 1,2-propanediol, and is a multifunctional additive whose safety has been verified in the fields of food, pharmaceuticals, and cosmetics.
[0115] The first reason for selecting propylene glycol is that it provides excellent moisturizing effects. Propylene glycol has the ability to capture and retain moisture by forming hydrogen bonds with water molecules through its two hydroxyl groups. When propylene glycol is transferred from the fabric softener sheet to the clothing during drying, it supplies and retains moisture to the fibers, helping the clothes maintain an appropriate moisture content even after drying. This provides the effect of making the clothes soft to the touch and suppressing static electricity.
[0116] The second reason for selecting propylene glycol is that, as an amphiphilic solvent, it improves the miscibility of various components. Propylene glycol possesses both hydrophilicity due to its hydroxyl groups and hydrophobicity due to its hydrocarbon chains, acting as a compatibilizer in compositions where water-soluble and oil-soluble components coexist. In particular, it helps dissolve or disperse hydrophobic components, such as fragrances, in aqueous mixtures and is also used in the emulsification of polydimethylsiloxane defoaming agents. This plays an important role in improving the uniformity of the composition and preventing phase separation.
[0117] The third reason for selecting propylene glycol is that it provides a viscosity control function. Propylene glycol is a liquid with a viscosity lower than glycerin but higher than water, and it can be used to finely control the viscosity of the composition. In the present invention, by using glycerin as the main viscosity modifier and propylene glycol as the auxiliary viscosity modifier, the viscosity of the final composition can be precisely controlled within the range of 2,500 to 6,000 cp. Appropriate viscosity is essential for simultaneously ensuring impregnation efficiency into the fabric and storage stability.
[0118] The fourth reason for selecting propylene glycol is that it provides an antifreeze effect. Propylene glycol has the effect of lowering the freezing point of aqueous solutions, preventing the composition from freezing when stored or transported in low-temperature environments during winter. Since freezing can cause phase separation of the composition and lead to the separation of the composition from the fabric, the antifreeze effect of propylene glycol contributes to maintaining the quality stability of the product.
[0119] The fifth reason for selecting propylene glycol is its excellent skin safety and biocompatibility. Propylene glycol is a substance recognized as GRAS by the FDA, used as a food additive, and is one of the most widely used moisturizers in cosmetics. It has very low potential for skin irritation or allergy, and its safety is ensured due to low oral toxicity. However, since some consumers may experience a sensitive reaction when using high concentrations, the content in this invention is limited to 0.5 to 2.5 parts by weight.
[0120] The reason for using a portion of propylene glycol in the defoaming agent emulsion is to improve the water-based dispersibility of the defoaming agent. The propylene glycol used in the defoaming agent emulsion is mixed with polydimethylsiloxane in a weight ratio of 1:2 to 1:5, which corresponds to a portion of the total amount of propylene glycol added. The remaining propylene glycol is added along with the secondary addition of glycerin to perform moisturizing and compatibility functions for the entire composition. This divided usage method allows for the optimized utilization of the various functions of propylene glycol.
[0121] The reason the content of propylene glycol was set to 0.5 to 2.5 parts by weight is to strike a balance between moisturizing effect and skin safety. Below 0.5 parts by weight, the moisturizing and compatibility effects are insufficient, and above 2.5 parts by weight, there is a possibility of irritation in some consumers with sensitive skin. Preferably, using it within the range of 1.0 to 2.0 parts by weight provides optimal effects. In addition, the total amount of propylene glycol and glycerin was controlled so that it does not become excessive, thereby preventing stickiness of the composition.
[0122] 7. Reason for Selecting Glycerin and Technical Significance
[0123] In the present invention, glycerin is used as a moisturizer and viscosity modifier in a ratio of 5 to 10 parts by weight based on 100 parts by weight of the total composition. Glycerin, with the chemical names glycerol or 1,2,3-propanetriol, is a polyhydric alcohol having three hydroxyl groups and is a substance obtained from the hydrolysis of natural oils and fats; it is the most widely used moisturizer in the fields of food, pharmaceuticals, and cosmetics.
[0124] The first reason for selecting glycerin is that it provides powerful moisturizing effects and wetting properties. Glycerin can form multiple hydrogen bonds with water molecules through three hydroxyl groups, which implies a stronger water-binding capacity than propylene glycol. The hygroscopic properties of glycerin are effective in the relative humidity range of 20–100%, and by absorbing moisture from the surrounding environment and supplying it to the clothing fibers, it ensures that the clothing maintains appropriate flexibility and texture even after drying. Experimental results confirmed that in the glycerin content range of 5–10 parts by weight, the moisture content of the clothing remained 2–3% higher than immediately after drying, resulting in reduced static electricity generation and improved texture.
[0125] The second reason for selecting glycerin is that it provides a viscosity control function to optimize the physical properties of the composition. Glycerin is a viscous liquid with a viscosity of approximately 1,400 cP at room temperature, and when added to a composition, it significantly increases the viscosity. In the present invention, the viscosity of the final composition is controlled to a range of 2,500 to 6,000 cP to facilitate impregnation into the fabric while preventing leakage during storage and transportation; glycerin is the key component in achieving this viscosity range. If the glycerin content is less than 5 parts by weight, the viscosity of the composition is too low and it flows down the fabric, and if it exceeds 10 parts by weight, the viscosity is excessively high, resulting in insufficient penetration into the fabric and reduced impregnation efficiency.
[0126] The third reason for selecting glycerin is that it improves the compatibility between cationic and amphoteric surfactants and enhances emulsion stability. As a polyhydric alcohol, glycerin possesses high polarity and excellent hydrogen bond-forming ability; by positioning itself between surfactant molecules, it mitigates electrostatic repulsion and provides structural stabilization. In particular, within the coacervate structure formed by cationic and amphoteric surfactants, glycerin adsorbs to the interface, preventing aggregation between coacervate particles and maintaining particle size within an appropriate range. This contributes to optimizing fragrance encapsulation efficiency and preventing phase separation or precipitation during long-term storage.
[0127] The fourth reason for selecting glycerin is that it provides an antifreeze effect and ensures low-temperature stability. Although glycerin has a melting point of 18°C in its pure state, it has a very large freezing point-lowering effect in an aqueous solution; therefore, when 5 to 10 parts by weight of glycerin are used in the composition of the present invention, the freezing point of the composition is lowered to -5°C or lower. This allows the product to maintain its quality without freezing even if the temperature temporarily drops in a logistics warehouse or transport vehicle during the winter. Since freezing can destroy the structure of the composition and cause phase separation of the surfactant, thereby permanently degrading the performance of the product, the antifreeze effect of glycerin is essential for ensuring the stability of the product's distribution.
[0128] The fifth reason for selecting glycerin is its excellent skin safety and environmental friendliness. Glycerin is derived from natural oils and is nearly 100% biodegradable, so it poses no environmental burden. Furthermore, it is recognized as the safest moisturizer in cosmetics and pharmaceuticals, and has very low levels of skin irritation, eye irritation, and oral toxicity. It can be safely used by users with sensitive or atopic skin, and its use is permitted in products for infants and toddlers. Since the product of the present invention comes into indirect contact with the skin through clothing, safety is the top priority, and glycerin perfectly meets these requirements.
[0129] The reason for adopting the method of adding glycerin in two stages is to ensure uniform dispersion of subsequent raw materials by controlling the viscosity of the mixture stepwise. When 60 to 80% by weight of the total amount of glycerin is added in the first stage, the viscosity of the mixture gradually increases to 50 to 150 cp; within this viscosity range, fluidity remains good, allowing for easy dispersion when an antifoaming agent emulsion or polyhydric alcohols are added. After the first addition of glycerin, the remaining amount of propylene glycol is added, followed by the second addition of the remaining amount of glycerin (20 to 40% by weight), which increases the viscosity to 200 to 400 cp; this is a viscosity suitable for mixing 1,2-hexanediol and D-sorbitol. If glycerin is added all at once, the viscosity rises rapidly to 300 to 500 cp, and in this high viscosity state, it is difficult for the hydrophobic component 1,2-hexanediol to be uniformly dispersed, and localized high concentration regions are formed, resulting in non-uniformity of product quality.
[0130] The reason for setting the glycerin content to 5 to 10 parts by weight is to optimize the balance of moisturizing effect, viscosity control, and emulsion stability. Below 5 parts by weight, the moisturizing effect is insufficient, and the viscosity of the composition is low, causing it to run off the fabric and reducing coacervate stability. If it exceeds 10 parts by weight, the viscosity becomes excessively high, resulting in insufficient penetration into the fabric; furthermore, excessive hygroscopicity causes the product to feel sticky, and some consumers may report issues such as stains on clothing. Preferably, using it within the range of 6 to 9 parts by weight provides optimal performance.
[0131] 8. Reasons for Selecting 1,2-Hexanediol and Technical Significance
[0132] In the present invention, 1,2-hexanediol is used as a moisturizer and preservative adjuvant in a ratio of 0.05 to 0.5 parts by weight based on 100 parts by weight of the total composition. 1,2-hexanediol is a polyhydric alcohol with the chemical name 1,2-dihydroxyhexane, having a structure in which two hydroxyl groups are bonded to the 1st and 2nd positions of a straight-chain hydrocarbon backbone consisting of six carbons.
[0133] The first reason for selecting 1,2-hexanediol is that it provides an excellent antimicrobial auxiliary effect. 1,2-hexanediol possesses two hydroxyl groups and a hydrophobic hydrocarbon chain of appropriate length, enabling it to penetrate the cell membranes of microorganisms, alter membrane permeability, and inhibit metabolic functions. In particular, since it has a different mechanism of action than sodium benzoate or laurylpyridium chloride, it exhibits a synergistic effect when used in combination with them, allowing for the achievement of a more broad and powerful preservative effect. Experimental results confirmed that adding 0.05 to 0.5 parts by weight of 1,2-hexanediol improved the antimicrobial effect against bacteria and fungi by 20 to 30% compared to the use of a single preservative. This triple preservative system (sodium benzoate + laurylpyridium chloride + 1,2-hexanediol) significantly enhances the microbiological stability of the product.
[0134] The second reason for selecting 1,2-hexanediol is that it provides moisturizing effects while minimizing stickiness. Glycerin or propylene glycol provide strong moisturizing effects, but excessive use can result in a sticky sensation. Due to its six-carbon hydrophobic chain, 1,2-hexanediol offers a lighter texture than glycerin or propylene glycol, while exhibiting appropriate moisturizing effects through its two hydroxyl groups. Even a small addition improves the overall texture of the composition, providing a soft yet refreshing sensation when applied to clothing. This characteristic, described as "light and fresh flexibility" in consumer sensory evaluations, enhances consumer satisfaction with the product.
[0135] The third reason for selecting 1,2-hexanediol is that it helps disperse hydrophobic components by providing a solubility-enhancing effect. As an amphiphilic substance possessing both hydrophobic chains and hydrophilic hydroxyl groups, 1,2-hexanediol acts as an auxiliary solvent or compatibilizer. In particular, it contributes to the dispersion of hydrophobic components, such as fragrances, in aqueous mixtures and also improves the dispersion stability of antifoaming agents. When used in combination with propylene glycol, it exhibits a synergistic effect, enabling more effective compatibilization.
[0136] The fourth reason for selecting 1,2-hexanediol is its low volatility, which allows it to remain stable without being lost during manufacturing and use. The boiling point of 1,2-hexanediol is approximately 223°C, which is much higher than the manufacturing temperature range (40–50°C) or the dryer usage temperature range (60–80°C) of the present invention, so there is almost no volatile loss. This means that the amount added during the manufacturing process remains intact in the final product and is effectively delivered to the clothing even when using a dryer. On the other hand, low molecular weight alcohols may not be able to properly exert their intended effects because a significant amount of them evaporate during manufacturing or use.
[0137] The fifth reason for selecting 1,2-hexanediol is that its skin safety is ensured and it is widely used as a cosmetic ingredient. 1,2-hexanediol is an ingredient listed in the International Cosmetic Ingredient Dictionary (INCI) and is widely used as a moisturizer and preservative adjuvant in cosmetics, particularly in skincare products. Its safety at appropriate concentrations has been confirmed through skin irritation tests and safety evaluations, and it can be used in products for sensitive skin. In this invention, the content is limited to 0.05 to 0.5 parts by weight to ensure safety while still allowing it to be effective.
[0138] The reason for adopting a sequential addition order in which 1,2-hexanediol is added before D-sorbitol is to optimize emulsion interface stability by considering the physicochemical properties of each component. 1,2-hexanediol is relatively hydrophobic due to its six-carbon chain, while D-sorbitol is highly hydrophilic due to its six hydroxyl groups. When 1,2-hexanediol is added first, it preferentially distributes in the hydrophobic regions of the already formed surfactant structure, and when D-sorbitol is added subsequently, it distributes in the hydrophilic regions. This sequential arrangement strengthens the structure of the emulsion interface and improves stability, preventing phase separation even during long-term storage. Experimental results confirmed that emulsion stability improved by 40–55% compared to the case of addition in reverse order, and no phase separation or precipitation was observed even after 3 months of storage.
[0139] The reason for setting the content of 1,2-hexanediol to 0.05 to 0.5 parts by weight is to achieve auxiliary antibacterial effects and texture improvement effects while preventing side effects caused by excessive use. Below 0.05 parts by weight, the auxiliary antibacterial effect is negligible, and the texture improvement effect is difficult to perceive. If it exceeds 0.5 parts by weight, hydrophobicity increases excessively, which lowers the water-based stability of the composition and may cause skin sensitivity reactions in some consumers. Preferably, using it within the range of 0.1 to 0.3 parts by weight provides optimal effects.
[0140] 9. Reason for Selecting D-Sorbitol and Technical Significance
[0141] In the present invention, D-sorbitol is used as a humectant and thickener in a ratio of 0.2 to 0.8 parts by weight based on 100 parts by weight of the total composition. D-sorbitol, with the chemical name D-glucitol, is a sugar alcohol having a structure in which six hydroxyl groups are bonded to a straight-chain hydrocarbon skeleton consisting of six carbons, and is a naturally derived substance obtained from the reduction reaction of glucose.
[0142] The first reason for selecting D-sorbitol is that it provides a unique cooling sensation along with a powerful moisturizing effect. D-sorbitol can form an extensive hydrogen bond network with water molecules through its six hydroxyl groups, meaning it can bind more moisture than glycerin, which has three hydroxyl groups. However, unlike glycerin, D-sorbitol's moisturizing mechanism maintains a dynamic equilibrium that gently captures and releases moisture rather than strongly binding and locking it in. This allows it to supply moisture to clothing without causing an excessively damp feeling, while maintaining a pleasant touch. Additionally, D-sorbitol triggers an endothermic reaction upon dissolution, providing a slight cooling sensation that contributes to a refreshing feeling when wearing the clothing.
[0143] The second reason for selecting D-sorbitol is that it provides viscosity-increasing and structural-stabilizing effects. D-sorbitol has the ability to increase the viscosity of a solution by forming a hydrogen bond network through multiple hydroxyl groups. Unlike glycerin, which increases viscosity primarily through the inherent viscosity of the molecule itself, D-sorbitol increases viscosity by creating a three-dimensional structure through the formation of a hydrogen bond network with water molecules. This mechanism provides structural stability to the composition, ensuring that viscosity remains constant even during long-term storage and preventing phase separation or precipitation. Experimental results confirmed that the viscosity stability of the composition improved when 0.2 to 0.8 parts by weight of D-sorbitol was added, maintaining the viscosity change rate within ±10% after 6 months of storage.
[0144] The third reason for selecting D-sorbitol is that it provides a stabilizing effect on the surfactant system. D-sorbitol is located in the hydrophilic outer layer of the coacervate structure formed by cationic and amphoteric surfactants, increasing electrostatic repulsion between coacervate particles and preventing particle aggregation. Additionally, through multiple hydroxyl groups, it forms hydrogen bonds with surfactant head groups, thereby strengthening the interfacial structure and improving fragrance encapsulation efficiency. This ensures that the coacervate structure remains stable even in the high-temperature environment of a dryer, contributing to controlling fragrance release and maximizing fragrance longevity.
[0145] The fourth reason for selecting D-sorbitol is that it inhibits microbial growth by providing an osmotic pressure regulating effect. D-sorbitol forms high osmotic pressure at high concentrations, which dehydrates the water in microbial cells and inhibits their growth. Although the concentration used in this invention (0.2 to 0.8 parts by weight) is not high enough to exhibit a direct preservative effect, when used together with sodium benzoate, laurylpyridium chloride, and 1,2-hexanediol, it provides an additional microbial growth inhibitory effect, further enhancing the microbiological stability of the product.
[0146] The fifth reason for selecting D-sorbitol is its excellent safety and biocompatibility. As a natural sugar alcohol, D-sorbitol is naturally present in fruits and vegetables and is widely used as a food additive, serving as a sweetener, moisturizer, and stabilizer. It has been recognized as GRAS by the FDA and is safe even when ingested orally. Due to its very low risk of skin irritation, eye irritation, and allergy, it is also used in cosmetics and pharmaceuticals for sensitive skin. As a substance whose safety has been thoroughly verified—including its use in foods for diabetic patients—it is an ideal raw material for the product of this invention.
[0147] The reason for adopting the method of pre-dissolving D-sorbitol in purified water preheated to 40–45°C at a concentration of 20–40 wt% before adding it is to shorten the dissolution time and achieve uniform dispersion. Although D-sorbitol has high solubility in water at room temperature (approx. 70 g / 100 mL at 20°C), its dissolution rate is relatively slow, and if the powder is added directly, it is prone to aggregation and forming lumps. Raising the temperature above 40°C significantly increases solubility (approx. 230 g / 100 mL at 50°C) and accelerates the dissolution rate. A concentration of 20–40 wt% is the optimal concentration that allows for easy addition and mixing because it forms a transparent solution upon complete dissolution without excessively high viscosity. It has been confirmed that the pre-dissolution method reduces dissolution time by 30–50% and prevents particle aggregation by more than 80% compared to direct powder addition.
[0148] The reason for setting the content of D-sorbitol to 0.2 to 0.8 parts by weight is to achieve moisturizing, viscosity stability, and interface stabilization effects while preventing side effects caused by excessive use. Below 0.2 parts by weight, the moisturizing and stabilizing effects are insufficient, and above 0.8 parts by weight, the viscosity of the composition increases excessively, and concerns regarding laxative effects (upon oral ingestion) may be raised by some consumers. Although the product of the present invention is not intended for oral ingestion, the content has been limited to ensure a safety margin. Preferably, using it within the range of 0.3 to 0.6 parts by weight provides optimal effects.
[0149] 10. Reasons for Selection and Technical Significance of Dialkyl Ester Ammonium Methosulfate Cationic Surfactant
[0150] In the present invention, a liquid dialkyl ester ammonium methosulfate cationic surfactant having two alkyl groups having 12 to 22 carbon atoms is used as the main softening agent in a ratio of 3 to 12 parts by weight based on 100 parts by weight of the total composition. This surfactant is a cationic compound having a quaternary ammonium structure in which two long-chain alkyl groups are connected through ester bonds.
[0151] The first reason for selecting dialkyl ester ammonium methosulfate is that it provides an excellent fabric softening effect. In this surfactant, cationic head groups are strongly electrostatically adsorbed to the negatively charged surface of the fibers, and two long-chain alkyl groups coat the fiber surface with a hydrophobic film, reducing friction between fibers. As this surfactant volatilizes in the high-temperature environment of a dryer, it is uniformly distributed across the surface of the garment, imparting a soft touch. It is known that a dialkyl structure with two alkyl groups forms a more effective hydrophobic coating than a monoalkyl structure with one alkyl group, resulting in a 20–30% improvement in softening effect.
[0152] The second reason for selecting dialkyl ester ammonium methosulfate is its excellent biodegradability, making it environmentally friendly. Ester bonds are hydrolyzed by esterase enzymes in the environment into fatty acids and alcohols, all of which are ultimately completely broken down into carbon dioxide and water by microorganisms. While traditional ether-linked cationic surfactants such as ditallow dimethyl ammonium chloride (DTDMAC) cause environmental pollution problems due to their low biodegradability, ester-linked surfactants biodegrade by more than 60% within 28 days, meeting OECD biodegradability standards. This aligns with the trend of tightening environmental regulations and satisfies consumer demand for eco-friendly products.
[0153] The third reason for selecting dialkyl ester ammonium methosulfate is that it interacts with amphoteric surfactants to form stable coacervates. The cationic head group and the anionic portion of the amphoteric surfactant combine through electrostatic attraction to form a layered coacervate, and two alkyl groups constitute the hydrophobic interior of the coacervate, enabling the encapsulation of hydrophobic substances such as fragrances. This coacervate structure remains stable even in the high-temperature environment of a dryer, preventing rapid volatilization of the fragrance and enabling continuous release. Experimental results confirmed that the most stable coacervate is formed and fragrance encapsulation efficiency is maximized when the weight ratio of the cationic surfactant to the amphoteric surfactant is controlled to 1:1.5 to 1:4.
[0154] The fourth reason for selecting dialkyl ester ammonium methosulfate is that it is supplied in liquid form, making it easy to handle and offering high mixing efficiency. Solid cationic surfactants require a melting or dissolution process, involve long mixing times, and are difficult to control in terms of temperature. Liquid surfactants have fluidity at room temperature, allowing for precise quantitative dosing via a pump, and their viscosity decreases at 40–50°C, enabling rapid mixing. This improves the efficiency of the manufacturing process and provides the effect of reducing energy consumption.
[0155] The reason for limiting the carbon number to the range of 12 to 22 is to optimize the balance between softening effect and biodegradability. If the carbon number is less than 12, the alkyl group is too short, resulting in insufficient hydrophobicity, weak fiber surface coating effect, and reduced softening effect. If the carbon number exceeds 22, the alkyl group is too long, leading to lower solubility and dispersibility in water and a slower biodegradation rate. Palmityl / stearyl derivatives in the 12 to 22 range, particularly those with 16 to 18 carbon atoms, are known to provide an optimal balance of softening effect, water stability, and biodegradability.
[0156] The reason for selecting methosulfate anions is that they offer superior environmental friendliness compared to halide anions such as chloride or bromide, and also improve product stability. Methosulfate (CH₃OSO₃) is an organic sulfate that is biodegradable and has lower skin irritation than halide anions. Additionally, methosulfate anions provide the effect of improving handling by appropriately controlling the viscosity of the surfactant's aqueous solution.
[0157] The reason the content of dialkyl ester ammonium methosulfate is set to 3 to 12 parts by weight is to strike a balance between softening effect and skin safety. Below 3 parts by weight, the softening effect is insufficient, making it difficult for consumers to perceive the product's performance. If it exceeds 12 parts by weight, the softening effect becomes saturated and does not improve further; additionally, the excessive cationic substance increases the likelihood of skin irritation or allergic reactions in some consumers, and residual surfactants on the clothing may inhibit foam formation during the next wash. Preferably, using it within the range of 5 to 10 parts by weight provides optimal performance and safety.
[0158] 11. Reasons for Selection and Technical Significance of Lauramidopropyl Betaine or Cocamidopropyl Betaine Amphoteric Surfactants
[0159] In the present invention, lauramidopropyl betaine or cocamidopropyl betaine is used as an amphoteric surfactant in a ratio of 10 to 18 parts by weight based on 100 parts by weight of the total composition. These surfactants are amphoteric compounds having a betaine structure and may exist as cationic, anionic, or zodiac agents depending on the pH.
[0160] The first reason for selecting lauramidopropyl betaine or cocamidopropyl betaine is that they form stable coacervates through strong electrostatic interactions with cationic surfactants. In the pH range of the composition of the present invention, 4.0 to 5.5, the betaine surfactant exists in an amphoteric state having both a carboxylate anionic portion and a quaternary ammonium cation portion. The carboxylate anionic portion binds to the cationic head group of dialkyl ester ammonium methosulfate through electrostatic attraction to form 1:1 or 2:1 complexes, and these complexes are arranged in a layered structure to form coacervates. These coacervates are spherical or elliptical particles with a diameter of 1 to 10 μm that have hydrophobic regions inside, allowing them to effectively encapsulate hydrophobic substances such as fragrances. Experimental results confirmed that the most stable and uniformly sized coacervates were formed when the weight ratio of cationic surfactant to amphoteric surfactant was controlled to 1:1.5 to 1:4.
[0161] The second reason for selecting lauramidopropyl betaine or cocamidopropyl betaine is to enhance fragrance longevity by maximizing fragrance encapsulation efficiency. The hydrophobic interior of the coacervate provides an environment where fragrance molecules can be stably captured, while the layered structure of the coacervate acts as a physical barrier to prevent rapid volatilization of the fragrance. In the high-temperature environment of 60–80°C in a dryer, the coacervate structure partially relaxes, gradually releasing the fragrance; this enables a much more sustained and uniform release compared to cases where the fragrance is directly dissolved in the composition. Experimental results confirmed that the composition forming the coacervate had a fragrance retention rate 30–45% higher after dryer use compared to the composition with directly dissolved fragrance, and that the fragrance attached to the clothing lasted for more than 48 hours.
[0162] The third reason for selecting Lauramidopropyl Betaine or Cocamidopropyl Betaine is that they provide an effect that mitigates the skin irritation associated with cationic surfactants. While cationic surfactants offer powerful softening effects, they can cause skin irritation at high concentrations. Amphoteric surfactants significantly reduce skin irritation by forming complexes with cationic surfactants, thereby lowering their free concentration and blocking the direct interaction of cationic head groups with skin proteins. Furthermore, betaine surfactants themselves possess skin conditioning effects, improving skin texture and providing moisturizing benefits. This is essential for developing products that can be safely used by consumers with sensitive skin.
[0163] The fourth reason for selecting Lauramidopropyl Betaine or Cocamidopropyl Betaine is their excellent biodegradability and environmental friendliness. Betaine surfactants have a structure in which fatty acids are linked through amide and ester bonds; they are hydrolyzed by enzymes in the environment into fatty acids, amines, and betaine, all of which are ultimately completely broken down into carbon dioxide and water by microorganisms. Biodegradability according to the OECD 301 test method is measured at over 60% within 28 days, classifying them as easily biodegradable substances. Furthermore, their environmental safety is ensured due to their very low toxicity to aquatic organisms. This makes them ideal for developing eco-friendly fabric softener compositions when used in combination with cationic surfactants.
[0164] The fifth reason for selecting lauramidopropyl betaine or cocamidopropyl betaine is that they act as structuring agents to improve the viscosity and stability of the composition. Betaine surfactants form complexes with cationic surfactants to create a three-dimensional network structure, thereby imparting structural viscosity to the composition. This is a characteristic different from viscosity obtained simply by adding polymers or thickeners; it exhibits shear thinning behavior, maintaining high viscosity during storage but decreasing viscosity when shear force is applied, making pumping or impregnation easier. Furthermore, this structure remains stable against temperature changes and the passage of time, preventing phase separation or precipitation even during long-term storage.
[0165] The reason both lauramidopropyl betaine and cocamidopropyl betaine are presented as selectable options is to provide flexibility in selection based on the raw material source, while the two substances have similar structures and functions. Lauramidopropyl betaine is derived from lauric acid (C12 fatty acid), and cocamidopropyl betaine is derived from mixed fatty acids (mainly C12–C14) of coconut oil. Both substances provide sufficient performance to achieve the objectives of the present invention and can be selected based on raw material prices and supply stability. Cocamidopropyl betaine is generally more economical and has a stable supply, making it advantageous for commercial production.
[0166] The reason for setting the content of the amphoteric surfactant to 10 to 18 parts by weight is to achieve an optimal ratio with the cationic surfactant. When the cationic surfactant content is 3 to 12 parts by weight and the amphoteric surfactant content is 10 to 18 parts by weight, the weight ratio of the two surfactants is in the range of 1:1.5 to 1:4, which is the optimal ratio for forming the most stable coacervates. Below 10 parts by weight, there is an insufficient amount of amphoteric surfactant relative to the cationic surfactant, causing some cationic surfactant to remain in a free state, which leads to skin irritation and incomplete coacervate formation. If it exceeds 18 parts by weight, an excess amount of amphoteric surfactant remains, increasing foam generation and reducing the economic efficiency of the product. Preferably, using it within the range of 12 to 16 parts by weight provides optimal performance and economic efficiency.
[0167] 12. Reasons for Selecting Ethanol and Technical Significance
[0168] In the present invention, ethanol is used as a solvent and penetration promoter in a ratio of 5 to 8 parts by weight based on 100 parts by weight of the total composition. Ethanol is a short-chain alcohol consisting of two carbon atoms, with the chemical name ethyl alcohol, and is the most common organic solvent produced through fermentation or synthesis.
[0169] The primary reason for selecting ethanol is that it enhances impregnation efficiency by promoting the penetration of the composition into the fabric. Since ethanol has a lower surface tension than water (water 72 mN / m, ethanol 22 mN / m at 20°C), it reduces the overall surface tension of the composition and facilitates penetration into the capillaries between the fabric fibers. Lower surface tension reduces the contact angle on the fabric surface, accelerating the spread of the composition across the surface and allowing it to easily penetrate into the narrow spaces between fiber bundles. Experimental results confirmed that compositions containing 5 to 8 parts by weight of ethanol showed a fabric penetration rate 40–60% faster and impregnation uniformity improved by 30–45% compared to compositions without ethanol. This ensures that the composition is uniformly distributed not only on the surface but also within the fabric, providing a consistent softening effect throughout the garment when using a dryer.
[0170] The second reason for selecting ethanol is to improve the efficiency of the manufacturing process by controlling the drying speed of the composition. Ethanol has a higher vapor pressure than water (water 2.3 kPa, ethanol 5.9 kPa at 20°C) and evaporates rapidly. When the composition is impregnated into the fabric and left for a certain period of time or subjected to a gentle drying process, the ethanol evaporates preferentially, concentrating the composition on the surface and reducing stickiness. This improves the handling of the impregnated fabric and shortens the drying time before packaging, thereby increasing production efficiency. However, since an excessive ethanol content can cause the composition to concentrate only on the surface of the fabric due to excessively fast drying, it was limited to 5 to 8 parts by weight.
[0171] The third reason for selecting ethanol is that, as an amphiphilic solvent, it improves the compatibility between water-soluble and oil-soluble components. Ethanol possesses both hydrophilicity due to its hydroxyl groups and hydrophobicity due to its ethyl groups, acting as a compatibilizer similar to propylene glycol. In particular, it helps dissolve or disperse hydrophobic components, such as fragrances, in aqueous mixtures and facilitates their penetration into the coacervate structure. Due to their small size and high mobility, ethanol molecules easily penetrate between the layered structures of coacervates, aiding in fragrance diffusion and improving encapsulation efficiency. Additionally, ethanol lowers the critical micelle concentration of certain surfactants, allowing for effective surfactant action even at lower concentrations.
[0172] The fourth reason for selecting ethanol is that it provides an antimicrobial auxiliary effect, thereby improving the microbiological stability of the product. Ethanol exhibits a consistent antimicrobial effect even at a concentration of 5 to 10 percent, and is particularly effective against yeast and mold. Although the ethanol content (5 to 8 parts by weight) of the present invention is a somewhat low concentration to function as an independent preservative, when used in combination with sodium benzoate, laurylpyridium chloride, and 1,2-hexanediol, it provides an additional antimicrobial effect, thereby establishing a multi-layered defense system. This contributes to inhibiting microbial growth, particularly in environments where the temperature is temporarily lowered during the manufacturing process or where contamination is possible.
[0173] The fifth reason for choosing ethanol is that it provides an additional sterilization effect when used in a dryer. As ethanol evaporates in the high-temperature environment of 60–80°C, a temporarily high concentration of ethanol vapor forms on the surface of clothing, which provides an additional sterilization effect against microorganisms that may remain on the garments. This sterilization effect enhances the added value of the product, especially for clothing where hygiene is critical, such as towels and underwear. Furthermore, the refreshing scent of ethanol also has the effect of masking unpleasant odors emanating from the clothing.
[0174] The sixth reason for selecting ethanol is that it is a substance with ensured safety and approved by regulatory authorities. Ethanol is permitted for use worldwide as a food additive, pharmaceutical excipient, and cosmetic ingredient, and has very low skin irritation or toxicity at appropriate concentrations. The ethanol concentration (5 to 8 parts by weight) used in this invention corresponds to approximately 5 to 8% of the final product, which falls within the concentration range generally used in cosmetics or detergents. However, since ethanol is a flammable substance, the risk of fire and explosion must be managed during the manufacturing process. To this end, this invention includes a process for removing volatile organic compounds generated during the ethanol mixing process using a HEPA filter or an activated carbon adsorption dust collector with a capture efficiency of 85% or higher.
[0175] The reason for adopting a method to remove volatile substances using a dust collector during the ethanol mixing process is to ensure the safety of the working environment and to control the residual ethanol concentration in the final product to an appropriate level. If a significant amount of ethanol evaporates and accumulates in the workspace during the mixing process at a speed of 40 to 70 rpm for 0.5 to 4 hours, it can harm workers' health and increase the risk of fire. HEPA filters remove fine particles by filtering air containing ethanol vapor, while the activated carbon adsorption method reduces the concentration in the air by physically adsorbing ethanol vapor onto the surface of activated carbon. By achieving a capture efficiency of over 85%, the ethanol concentration in the working environment can be maintained below the exposure limit (1,000 ppm, 8-hour hourly weighted average) under the Occupational Safety and Health Act. Simultaneously, by controlling the ethanol content of the final product to a range of 5 to 8 parts by weight, the penetration-promoting effect can be maintained while minimizing the risk of skin irritation and flammability.
[0176] The reason the ethanol content is set to 5 to 8 parts by weight is to strike a balance between the penetration-promoting effect and safety. Below 5 parts by weight, the surface tension reduction effect is insufficient, making it difficult to expect a fabric penetration-promoting effect. If it exceeds 8 parts by weight, the excessive ethanol causes the drying speed of the composition to become too fast, resulting in the composition concentrating only on the surface of the fabric and insufficient internal penetration; furthermore, the risk of fire during the manufacturing process increases, and some consumers may experience aversion to the smell of ethanol or skin irritation reactions. Preferably, using it within the range of 6 to 7 parts by weight provides optimal efficacy and safety.
[0177] 13. Reason for Selection of Fragrance and Technical Significance
[0178] In the present invention, fragrance is used in a ratio of 12 to 18 parts by weight based on 100 parts by weight of the total composition. The fragrance is a mixture of natural or synthetic aromatic compounds that imparts a pleasant scent to clothing and serves to mask unpleasant odors.
[0179] The primary reason for selecting fragrance is that it is the most important sensory element determining consumer product satisfaction. In fabric softener products, fragrance is a key factor in consumers' product selection and repurchase decisions, along with softening and anti-static effects. Market research results showed that over 70% of fabric softener users cited fragrance as the most important selection criterion, and they particularly value fragrance longevity and quality over fragrance intensity. In this invention, the fragrance content is set to 12 to 18 parts by weight to ensure that a pleasant fragrance is maintained on clothing for more than 48 hours even after using a dryer, which represents a 30 to 50% improvement in fragrance longevity compared to competing products.
[0180] The second reason for selecting fragrances is that they mask and neutralize unpleasant odors that may occur during the washing and drying process. Clothing adsorbs odor-causing substances derived from various sources, such as sweat, sebum, food, and cigarette smoke, and some odors may remain even after washing. In particular, during high-temperature drying, these odor-causing substances can volatilize and emit unpleasant smells. Fragrances not only sensually mask these unpleasant odors, but some fragrance components also provide a neutralizing effect by chemically reacting with or adsorbing the odor-causing substances. Citrus, floral, and musk-based fragrances are known to be particularly effective at masking odors.
[0181] The third reason for selecting fragrances is that they are encapsulated within a coacervate structure, enabling continuous and controlled release. Since fragrances are composed mostly of hydrophobic substances, they can be effectively trapped within the hydrophobic interior of the coacervate formed by cationic and amphoteric surfactants. The layered structure of the coacervate acts as a physical barrier preventing rapid volatilization of the fragrance, and as the coacervate structure gradually relaxes in the high-temperature environment of the dryer, the fragrance is released slowly. Unlike cases where the fragrance is directly dissolved in the composition, this allows most of the scent to be stably delivered to the clothing without being lost during the initial drying stage, thereby providing a lasting fragrance. Experimental results confirmed that fragrances encapsulated in coacervates experienced a 40–55% reduction in loss during the drying process and extended the scent duration on clothing by 2–3 times compared to directly dissolved fragrances.
[0182] The fourth reason for selecting fragrance is to impart a luxurious image and a differentiated identity to the product. Among sensory experiences, scent is particularly strongly connected to memory and emotion, and specific scents evoke a brand or recall a particular feeling. Premium fabric softener products collaborate with famous perfume houses to develop unique and luxurious scents, which significantly enhances the added value of the product. In this invention, sufficient fragrance content is secured to enable the realization of a rich and complex scent profile, and a three-stage fragrance structure consisting of citrus top notes, floral middle notes, and musk / woody base notes is applied to provide a dynamic fragrance experience that changes over time.
[0183] The fifth reason for selecting fragrances is that they provide psychological comfort and well-being effects. Certain scents are known to offer aromatherapy benefits, such as stress relief, mood improvement, and sleep promotion. For instance, lavender is reported to provide a calming effect, citrus scents freshness and vitality, and rose scents comfort and a sense of happiness. When consumers experience these scents while wearing clothes treated with fabric softener or lying in bedding, their psychological satisfaction increases, and a positive perception of the product is formed. This contributes to increasing product repurchase rates and building brand loyalty.
[0184] The reason for adopting a low-temperature mixing method, in which fragrances are mixed at a low temperature of 3 to 10°C for 5 to 20 minutes, is to minimize the loss of volatile components of the fragrances. Fragrances are composed of dozens to hundreds of aromatic compounds, some of which have low boiling points and can volatilize rapidly at temperatures above 40°C. In particular, limonene (boiling point 176°C) and linalool (boiling point 198°C), which are the main components of citrus fragrances, have high vapor pressure even at room temperature and are highly volatile. By cooling the third mixture to 3 to 10°C, adding the fragrance, and mixing for only a short time (5 to 20 minutes), the volatile loss of the fragrance can be reduced by 35 to 50% compared to room-temperature mixing. Low-temperature conditions also improve the chemical stability of fragrance components, suppressing oxidation or hydrolysis reactions and maintaining the quality of the fragrance.
[0185] The reason for adopting a method of aging the composition at 3–10°C for 10–30 hours after adding the fragrance is to allow the fragrance to sufficiently penetrate into the coacervate structure and for the interactions between the components to reach equilibrium. Immediately after adding the fragrance, fragrance molecules are unevenly distributed within the composition, and penetration into the coacervate structure is incomplete. When left at a low temperature for an extended period, fragrance molecules move into the hydrophobic interior of the coacervate via diffusion, and the surfactant structure rearranges to optimally encapsulate the fragrance. Although low-temperature conditions slow down the rate of reaching this equilibrium, they minimize volatile loss of the fragrance, thereby enabling the achievement of higher overall encapsulation efficiency. Experimental results confirmed that the composition subjected to low-temperature aging showed a 25–40% improvement in fragrance encapsulation efficiency and a 30–45% increase in fragrance intensity on clothing after drying compared to the composition not aged.
[0186] The reason for setting the fragrance content to 12 to 18 parts by weight is to optimize the intensity and longevity of the scent while preventing side effects caused by excessive use. Below 12 parts by weight, the fragrance intensity is weak, making it difficult for consumers to fully perceive the product's scent, and the odor masking effect is also insufficient. If it exceeds 18 parts by weight, the fragrance is excessively strong, which may cause headaches or nausea in some consumers and cause problems for consumers with allergies to fragrance ingredients. Furthermore, exceeding the encapsulation capacity of the coacervate may result in residual free fragrance, which can reduce the stability of the composition. Preferably, using it within the range of 14 to 16 parts by weight ensures safety while providing a fragrance intensity that is pleasantly perceived by most consumers. The specific composition of the fragrance can be adjusted according to the target fragrance profile, target consumer group, regional preferences, etc., and the manufacturing method of the present invention is applicable to various fragrance compositions.
[0187] 14. Reasons for Selecting Natural Pulp and Technical Significance
[0188] In the present invention, natural pulp is used as a fabric material for a fabric softener sheet in a ratio of 30 to 90 weight percent. Natural pulp is a cellulose fiber obtained by removing lignin and hemicellulose from wood (mainly coniferous or deciduous trees) by chemical or mechanical methods.
[0189] The first reason for selecting natural pulp is that it provides excellent absorbency and retention. Natural pulp can form strong hydrogen bonds with water molecules through the hydroxyl groups of the cellulose molecular chains and can physically trap liquid in the capillaries and pores within the fiber structure. Due to these characteristics, natural pulp can absorb and retain liquid amounting to 7 to 10 times its own weight. Since the fabric softener composition of the present invention is a viscous liquid with a viscosity of 2,500 to 6,000 cp that must be impregnated into the fabric, the use of natural pulp with excellent absorbency is essential. A natural pulp content of 30 to 90 weight percent is the optimal range that allows the composition to be sufficiently absorbed while maintaining the mechanical strength of the fabric.
[0190] The second reason for selecting natural pulp is its excellent eco-friendliness and biodegradability. Natural pulp is produced from renewable wood resources and, upon disposal after use, is completely biodegraded by cellulase enzymes in the environment, converting into carbon dioxide and water. Biodegradability tests confirmed that natural pulp decomposes by more than 90% within 3 to 6 months under landfill conditions. This represents a significantly lower environmental burden compared to synthetic fiber-based fabrics and is a crucial factor in securing competitiveness in a market environment where environmental regulations are tightening and consumer demand for eco-friendly products is increasing. Furthermore, the use of natural pulp is advantageous for obtaining eco-friendly product certifications (e.g., Nordic Environmental Label, EU Eco-label, etc.).
[0191] The third reason for selecting natural pulp is that it provides appropriate mechanical strength and durability. Natural pulp fibers have an appropriate fiber length of 2 to 5 mm (softwood pulp) or 0.5 to 2 mm (hardwood pulp), and form a network through hydrogen bonding between fibers to impart tensile strength and tear strength to the fabric. Since the fabric softener sheet of the present invention is subjected to mechanical stress while rotating with clothing in a dryer, it requires a certain level of strength. Although natural pulp can provide sufficient strength even when used at 100%, the present invention uses it mixed with viscose fibers to improve tactile feel and reduce costs. 30 to 90 weight percent of natural pulp is the optimal range that provides appropriate flexibility and softness while maintaining the strength of the fabric.
[0192] The fourth reason for selecting natural pulp is that its surface characteristics are suitable for impregnating the composition. The surface of natural pulp fibers is hydrophilic and carries a slight negative charge due to the hydroxyl groups of cellulose. These surface characteristics allow the cationic surfactant included in the composition of the present invention to be strongly adsorbed to the fiber surface through electrostatic attraction, thereby increasing impregnation efficiency and preventing the detachment of the composition during storage and transportation. In addition, the hydrophilic surface facilitates the initial penetration of the water-based composition, thereby shortening the impregnation time. Experimental results confirmed that natural pulp-based fabrics have a composition absorption rate 2 to 3 times faster and a retention capacity 40 to 60% higher compared to synthetic fiber-based fabrics.
[0193] The fifth reason for choosing natural pulp is its excellent cost-effectiveness. As a commodity produced on a large scale globally, natural pulp has a stable supply and is priced lower than synthetic or specialty fibers. This contributes to reducing product manufacturing costs and securing price competitiveness. Furthermore, since standardized quality specifications have been established for natural pulp, it is easy to secure raw materials of stable quality and facilitate quality control.
[0194] The reason for setting the natural pulp content to 30 to 90 weight percent is to optimize the balance of absorbency, strength, feel, and cost of the fabric. Below 30 weight percent, it is difficult to fully utilize the benefits of the absorbency and biodegradability of natural pulp, and if it exceeds 90 weight percent, the fabric becomes excessively stiff and rough, which may lower consumer preference. The mixing ratio with viscose fibers can be adjusted according to the target fabric characteristics, and preferably, 50 to 80 weight percent of natural pulp and 20 to 50 weight percent of viscose fibers can be mixed to produce a fabric with balanced absorbency, strength, and feel.
[0195] 15. Reasons for Selecting Viscose Fiber and Technical Significance
[0196] In the present invention, viscose fibers are used as the fabric material for the fabric softener sheet in a ratio of 10 to 70 weight percent. Viscose fibers are regenerated cellulose fibers produced by chemically dissolving natural cellulose (mainly wood pulp) and then spinning it, and are also known as rayon.
[0197] The first reason for selecting viscose fiber is that it provides a softer and more flexible feel than natural pulp. Since cellulose is completely dissolved and regenerated during the manufacturing process, viscose fiber has a more uniform structure and a smoother surface than wood-derived fibers in natural pulp. The fiber thickness can also be made fine by adjusting the denier, allowing for a soft feel. Since the fabric softener sheet of the present invention comes into direct contact with clothing in a dryer, the feel is important; by mixing viscose fiber in a certain proportion, a much softer and silk-like feel can be achieved compared to using only natural pulp. Consumer sensory evaluation results confirmed that fabrics containing 10 to 70 weight percent of viscose fiber showed a 50 to 80% improvement in softness and a 40 to 60% increase in preference compared to 100% natural pulp fabric.
[0198] The second reason for selecting viscose fiber is its excellent compatibility with natural pulp. Since viscose fiber is primarily composed of cellulose, just like natural pulp, it has a similar chemical composition and can be strongly bonded through hydrogen bonds between fibers. This enables the uniform mixing of natural pulp and viscose fiber during wet nonwoven manufacturing processes (e.g., spunlace, airlaid) to produce stable fabrics. When synthetic fibers (e.g., polyester, polypropylene) are mixed, delamination or uneven distribution may occur due to their low affinity with cellulose fibers, whereas viscose fiber does not have these problems.
[0199] The third reason for selecting viscose fibers is that they are suitable for impregnating the composition due to their excellent absorbency and hygroscopicity. Viscose fibers have superior absorbency compared to natural cotton fibers because the amorphous region increases and internal pores are formed during the regeneration process. They can absorb liquids amounting to 5 to 8 times their own weight, and their high hygroscopicity allows them to hold 11 to 13% moisture at 65% relative humidity. These characteristics are advantageous for uniformly impregnating the viscous composition of the present invention into the fabric and for maintaining it stably during storage. Additionally, the hydrophilic surface of viscose fibers is suitable for electrostatic adsorption of cationic surfactants, thereby improving impregnation efficiency.
[0200] The fourth reason for selecting viscose fiber is its excellent biodegradability, making it environmentally friendly. Although viscose fiber is manufactured through a chemical process, the final product is pure cellulose; therefore, just like natural pulp, it is completely biodegradable by cellulase enzymes in the environment. Biodegradability tests confirmed that viscose fiber decomposes by more than 80% within 6 to 12 months under landfill conditions. This contrasts with synthetic fibers such as polyester or polypropylene, which do not decompose for decades. Since fabrics composed of natural pulp and viscose fiber are 100% biodegradable, they can be marketed as eco-friendly products and are advantageous for obtaining environmental certifications.
[0201] The fifth reason for selecting viscose fiber is that it has adequate heat resistance, making it suitable for dryer usage conditions. Viscose fiber maintains its physical properties up to approximately 120–150°C, and poses no problems in the dryer environment (60–80°C) where the product of the present invention is used. While some synthetic fibers may soften or deform at low temperatures, viscose fiber does not have these issues, thereby ensuring product reliability. Furthermore, viscose fiber generates less static electricity than synthetic fiber, which minimizes problems caused by static electricity during friction with clothing in a dryer.
[0202] The reason for setting the viscose fiber content to 10 to 70 weight percent is to optimize the balance of the fabric's feel, strength, and cost. Below 10 weight percent, it is difficult to sufficiently obtain the effect of improving the soft feel of the viscose fiber, and if it exceeds 70 weight percent, the tensile strength and tear strength of the fabric decrease, increasing the risk of damage during dryer use. In addition, since viscose fiber is more expensive than natural pulp, excessive use increases manufacturing costs. Preferably, by mixing 20 to 50 weight percent of viscose fiber and 50 to 80 weight percent of natural pulp, a fabric with a balance of softness, strength, absorbency, and cost can be manufactured.
[0203] The reason the basis weight of the fabric was set to 40–80 g / m² is to balance the retention capacity of the composition with handling properties. Fabrics with a basis weight of less than 40 g / m² are too thin and weak, making them prone to tearing during composition impregnation and potential damage during dryer use. Fabrics with a basis weight exceeding 80 g / m² are too thick and heavy, resulting in uneven penetration of the composition into the fabric. Furthermore, it is difficult to move the fabric freely between garments in a dryer, which reduces effectiveness and increases manufacturing costs. The 40–80 g / m² range is the optimal range that allows the composition to be effectively delivered to the garment while maintaining sufficient mechanical strength and providing appropriate flexibility and breathability.
[0204] Technical Significance and Critical Importance of Each Stage of the Manufacturing Process
[0205] Technical Significance and Critical Importance of the Purified Water Manufacturing Stage
[0206] Overall Significance of the Purified Water Manufacturing Process
[0207] The purified water manufacturing step of the present invention is a step of manufacturing purified water of high purity, which serves as the basic medium of the fabric softener composition, and is the most fundamental and important process for determining the stability and quality of the final product. Since purified water is a major component accounting for 40 to 60 parts by weight of the total weight of the composition, the quality of the purified water has an absolute influence on the quality of the final product.
[0208] The reason raw water is treated through a five-stage sequential filtering process is to effectively remove impurities of different sizes and characteristics at each stage. A single filter cannot effectively remove all types of impurities, but a stepwise approach allows for the systematic removal of everything from large particles to fine impurities at the ionic level.
[0209] Controlling electrical conductivity within the range of 5–15 μS / cm is intended to maintain dissolved ion concentrations at extremely low levels. Lowering electrical conductivity below 5 μS / cm results in excessive purification costs and reduced productivity, while exceeding 15 μS / cm increases the risk of residual metal ions reacting with cationic surfactants to form precipitates. Experimental results confirmed that when water with an electrical conductivity exceeding 20 μS / cm was used, fine precipitates were observed and transparency decreased after 3 months of storage.
[0210] Controlling total dissolved solids to 5 to 20 ppm or less is intended to prevent nozzle clogging during fabric impregnation and to ensure product uniformity. Dissolved solids exceeding 20 ppm may precipitate during long-term storage to form precipitates or clog the fine nozzles of the impregnation process, thereby reducing productivity.
[0211] Critical Significance of the First Mesh Filter Filtration Stage
[0212] Passing raw water through a primary mesh filter with a mesh size of 210 to 250 is intended to primarily remove large suspended solids, rust, sand, etc., larger than 10㎛. The mesh size refers to the number of holes per inch, and 210 to 250 mesh corresponds to a pore size of 60 to 75㎛.
[0213] Using a coarse filter with a mesh size of less than 210 shortens the lifespan of subsequent filters as fine particles pass through due to pores larger than 75㎛, while using a fine filter with a mesh size exceeding 250 causes rapid clogging, resulting in reduced flow rate and a shorter filter replacement cycle, which increases operating costs. Experimental results showed that an optimal balance between filter lifespan and filtration efficiency could be achieved in the 210–250 mesh range.
[0214] Adjusting the flow rate to 50 to 150 liters per minute is intended to balance filtration efficiency and productivity. While a low flow rate of less than 50 liters per minute provides effective filtration, it excessively prolongs the overall purified water production time, thereby reducing productivity. Conversely, a high flow rate exceeding 150 liters per minute results in insufficient retention time in the filter, allowing some particles to pass through without being removed. Additionally, a high flow rate can apply excessive pressure to the filter, potentially causing damage.
[0215] Critical Significance of the Second Activated Carbon Filter Adsorption Filtration Stage
[0216] Controlling the particle size of activated carbon within the range of 0.5 to 2.0 mm is intended to optimize the balance between the adsorption surface area and fluid resistance. Fine activated carbon smaller than 0.5 mm has a large surface area and high adsorption efficiency, but the small inter-particle pores increase fluid resistance and lead to greater pressure loss. Coarse activated carbon exceeding 2.0 mm has low fluid resistance but a small surface area, resulting in insufficient adsorption capacity. Experimental results confirmed that activated carbon in the 0.5 to 2.0 mm range, particularly 0.8 to 1.5 mm in size, provides optimal adsorption performance and low pressure loss.
[0217] Maintaining the contact time at 5 to 15 minutes is intended to ensure sufficient time to reach adsorption equilibrium. Short contact times of less than 5 minutes result in incomplete adsorption, meaning residual chlorine and organic matter are not sufficiently removed, while long contact times exceeding 15 minutes lead to only reduced productivity without significant additional improvement in adsorption efficiency. Since the adsorption rate of activated carbon is fast initially and slows down over time, 5 to 15 minutes is an economical and effective range.
[0218] Adjusting the flow rate to 30 to 100 liters per minute is intended to ensure productivity while maintaining an appropriate contact time. The flow rate must be adjusted to achieve a contact time of 5 to 15 minutes by considering the relationship between the filter volume and the flow rate.
[0219] Critical Significance of the Third UV Sterilization Filter Sterilization Stage
[0220] The reason ultraviolet light with a wavelength of 254 nm is used is that this wavelength is closest to the maximum absorption wavelength of DNA (260 nm). Ultraviolet light exerts a sterilization effect by forming thymine dimers in the DNA of microorganisms and destroying their replication function, and the 254 nm wavelength provides the most efficient sterilization effect.
[0221] Maintaining the irradiation intensity at 30–60 mJ / cm² is intended to provide sufficient energy to inactivate most pathogenic microorganisms. Low irradiation intensities below 30 mJ / cm² allow some resistant microorganisms to survive, while high irradiation intensities exceeding 60 mJ / cm² only increase energy consumption and lamp costs without providing a significant improvement in sterilization effectiveness. Experimental results showed that a sterilization rate of over 99.9% could be achieved in the range of 40–50 mJ / cm².
[0222] Adjusting the exposure time to 3–10 seconds is intended to determine the total UV dose along with the irradiation intensity. Short exposures of less than 3 seconds do not provide a sufficient dose, while long exposures exceeding 10 seconds reduce productivity. The design must ensure that the residence time inside the filter is 3–10 seconds while adjusting the flow rate to 20–80 liters per minute.
[0223] Critical Significance of the 4th Membrane Filter Microfiltration Stage
[0224] Controlling the pore size to a range of 0.0001 to 0.01 μm is intended to effectively remove heavy metal ions and fine impurities. 0.0001 μm (reverse osmosis method) can remove almost all dissolved substances, but has a high pressure requirement and a slow permeation rate. 0.01 μm (ultrafiltration method) removes colloidal particles and polymeric substances, but allows some small ions to pass through. For the purposes of the present invention, a range of 0.0001 to 0.01 μm can be selected, and preferably, a range of 0.0001 to 0.001 μm (reverse osmosis) is used to effectively remove metal ions.
[0225] Maintaining the operating pressure at 3 to 8 bar is intended to provide sufficient pressure to induce permeation through the membrane. Low pressures below 3 bar result in excessively slow permeation rates, reducing productivity, while high pressures exceeding 8 bar place excessive stress on the membrane, causing damage and shortening its lifespan. For reverse osmosis membranes, a pressure of 5 to 7 bar is generally optimal.
[0226] The flow rate is controlled to 10 to 50 liters per minute, taking into account the permeation capacity of the membrane. A low flow rate of less than 10 liters per minute results in excessively low productivity, while a high flow rate exceeding 50 liters per minute cannot be handled by the membrane, causing the pressure to rise excessively or the filtration quality to deteriorate.
[0227] Controlling the electrical conductivity of the permeate to 10 μS / cm or less is a quality indicator to confirm that membrane filtration is operating normally. If it exceeds 10 μS / cm, it indicates that the membrane is damaged or the pressure is insufficient, so immediate action is required.
[0228] Critical Significance of the 5th Final Line Filter Filtration Stage
[0229] Controlling the pore size to 5–10㎛ is intended to finally remove fine particles that may remain in the purified water after passing through the membrane filter. Fine pores smaller than 5㎛ clog quickly, resulting in a shorter replacement cycle, while pores larger than 10㎛ allow some particles to pass through, which can degrade the quality of the final purified water.
[0230] The reason for using SUS316 material is its excellent corrosion resistance, which prevents metal ions from leaching out of the filter itself even during long-term use. While SUS304 also offers good corrosion resistance, SUS316 provides even superior resistance due to its higher molybdenum content.
[0231] Adjusting the flow rate to 20 to 60 liters per minute is intended to balance final filtration efficiency and productivity.
[0232] Critical Significance of the Quality Verification Stage
[0233] Selecting only purified water that meets quality standards by measuring electrical conductivity in the range of 5–15 μS / cm, total dissolved solids in the range of 5–20 ppm, and pH in the range of 6.5–7.5 in real time is intended to fundamentally prevent defective purified water from being fed into subsequent processes. Through real-time monitoring, filter performance degradation or abnormal conditions can be immediately detected and addressed.
[0234] Controlling the total water purification time to 15 to 40 minutes is intended to balance production efficiency and purification quality. Short times of less than 15 minutes result in insufficient retention time in each filter, leading to a decline in purification quality, while long times exceeding 40 minutes result in excessively low productivity.
[0235] Storing purified water in stainless steel storage tanks at 3 to 10°C is intended to prevent microbial re-contamination. Excessively low temperatures below 3°C result in excessive energy consumption, while temperatures exceeding 10°C increase the rate of microbial growth, thereby reducing storage stability.
[0236] The requirement to use within 24 hours is intended to minimize changes in water quality during storage. Since purified water can absorb carbon dioxide from the air, causing a decrease in pH or microbial contamination, it must be used as quickly as possible.
[0237] Technical Significance and Critical Importance of the Heated Purified Water Preparation Step
[0238] Overall Significance of the Heated Purified Water Preparation Step
[0239] The heating and purification water preparation step of the present invention is a step of heating purified water to 40~50℃ and removing dissolved oxygen to prepare it in a state optimized for subsequent raw material input. Heating improves the dissolution rate of raw materials and increases mixing efficiency, while deoxygenation treatment ensures the stability of components sensitive to oxidation.
[0240] Limiting the capacity to 50 to 500 liters is intended to cover everything from laboratory scale to commercial production scale. Small capacities of less than 50 liters are inefficient for commercial production, while large capacities exceeding 500 liters make it difficult to maintain temperature uniformity and increase equipment costs excessively.
[0241] The reason for using SUS304 or SUS316 stainless steel materials is their excellent corrosion resistance, heat resistance, and hygiene. Ordinary steel can corrode and contaminate purified water, and plastics pose a risk of some plasticizers or additives leaching out at temperatures of 40 to 50°C.
[0242] The critical significance of the preheating phase
[0243] Preheating purified water to 20–30°C is intended to prevent rapid temperature changes and enable precise temperature control through gradual heating. Since the initial temperature of purified water is generally 3–10°C (storage tank temperature), heating it directly to 40–50°C results in an excessively rapid rate of temperature rise, making control difficult.
[0244] Circulating hot water at 60–80°C inside the double jacket is intended to apply an indirect heating method. Direct heating (e.g., electric heating wires, direct steam injection) results in localized high temperatures at the heating surface, which can cause trace amounts of dissolved minerals in the purified water to precipitate or subsequently alter heat-sensitive components. Indirect heating offers excellent quality stability due to its uniform temperature distribution and lack of localized overheating.
[0245] Controlling the hot water temperature to 60 to 80°C is intended to balance the preheating speed and controllability. Low hot water temperatures below 60°C are too slow, causing the preheating time to be excessively extended, while high hot water temperatures above 80°C are too fast, making precise temperature control difficult and posing a risk of exceeding the target temperature.
[0246] Controlling the heating rate to 1–3°C per minute is intended to minimize temperature deviations and achieve stable heating. A slow heating rate of less than 1°C per minute excessively extends the overall process time, leading to reduced productivity, while a fast heating rate exceeding 3°C per minute increases temperature non-uniformity inside the tank and makes control unstable.
[0247] Critical significance of the main heating stage
[0248] Stirring purified water at a speed of 50 to 100 rpm is intended to ensure temperature uniformity inside the tank. If heated without stirring, the temperature near the double jacket may be high while the temperature in the center is low, resulting in a temperature difference of more than 10°C. Low stirring speeds of less than 50 rpm result in insufficient temperature uniformity, while high stirring speeds exceeding 100 rpm hinder temperature measurement and increase energy consumption due to the generation of vortices or bubbles.
[0249] Raising the hot water temperature of the double jacket to 80–95°C is intended to maintain an appropriate main heating rate. Using a hot water temperature higher than that of the preheating stage, heat to 35–45°C, while still maintaining the heating rate within a controllable range.
[0250] Controlling the heating rate at 0.5 to 2°C per minute requires more precise control than the preheating stage. As the target temperature (40 to 50°C) approaches, more precise control is required, and a rate of 0.5 to 2°C per minute allows the target temperature to be reached within a reasonable time while preventing temperature overshoot.
[0251] Maintaining the temperature deviation inside the heating tank within ±1.5℃ is intended to ensure uniform quality of heated purified water throughout the tank. A temperature deviation exceeding ±1.5℃ can cause variations in the dissolution rate of raw materials or reaction rates in certain areas, leading to non-uniformity in the final product.
[0252] Critical significance of the temperature stabilization stage
[0253] Maintaining the temperature of the purified water at the target temperature of 40 to 50°C for 5 to 15 minutes is intended to allow the entire tank to reach thermal equilibrium. Since heat transfer may still be in progress in some areas just after the target temperature is reached, maintaining it for a certain period of time ensures complete equilibrium is achieved.
[0254] Maintaining the temperature range within ±0.5℃ requires very precise control during the temperature stabilization process. This can be achieved by using an automatic temperature control system that applies a PID control algorithm.
[0255] Critical significance of the deoxygenation step
[0256] The use of food-grade nitrogen gas with a purity of 99.9% or higher and an oxygen content of 10 ppm or less is intended to achieve effective deoxygenation without adding impurities to purified water. Low-purity nitrogen gas may contain oxygen or other impurities, which can reduce the deoxygenation effect or contaminate the purified water.
[0257] Controlling the flow rate to 0.1 to 0.5 L / min is intended to balance effective deoxygenation and nitrogen gas consumption. Low flow rates of less than 0.1 L / min result in a deoxygenation rate that is too slow, causing the time to reach the target dissolved oxygen concentration to become excessively long, while high flow rates exceeding 0.5 L / min result in only increased nitrogen gas consumption without any significant improvement in deoxygenation efficiency.
[0258] Controlling the bubbling time to 5 to 15 minutes is intended to provide sufficient time to lower the dissolved oxygen concentration to 5 ppm or less. Short bubbling of less than 5 minutes results in incomplete deoxygenation, while long bubbling exceeding 15 minutes provides minimal improvement in efficiency. Experimental results showed that at an appropriate flow rate, bubbling of approximately 10 to 12 minutes could lower the dissolved oxygen to 3 to 4 ppm.
[0259] The purpose of using an electrochemical dissolved oxygen meter is to measure the dissolved oxygen concentration accurately in real time. Although chemical titration is accurate, it is time-consuming and does not allow for real-time monitoring, making it unsuitable for process control.
[0260] Reducing the dissolved oxygen concentration to 5 ppm or less is intended to prevent the oxidation of subsequently added citric acid, glycerin, fragrances, etc. Dissolved oxygen exceeding 5 ppm can oxidize these components during long-term storage, causing discoloration, foul odors, and reduced efficacy. Experimental results showed that optimal stability could be ensured within the dissolved oxygen range of 3 to 5 ppm.
[0261] Maintaining the temperature of the heated purified water in the range of 40 to 50°C even during bubbling is intended to compensate for the evaporative cooling caused by nitrogen gas bubbling. Since the temperature may drop by 1 to 2°C as some water evaporates during the bubbling process, the temperature must be maintained by continuously circulating hot water.
[0262] Critical Significance of the Temperature Equalization Step
[0263] Increasing the stirring speed to 80–150 rpm and stirring for 3–10 minutes is intended to resolve temperature non-uniformity caused during the deoxygenation process. Since nitrogen gas bubbling can cause localized cooling, the temperature is re-uniformed through strong stirring.
[0264] Uniformizing the temperature deviation of the upper, middle, and lower layers to within ±0.3℃ is intended to ensure uniform reaction and dissolution rates throughout the entire tank during subsequent raw material input. ±0.3℃ is a very strict standard that guarantees the highest level of quality consistency.
[0265] Critical Significance of the Heated Water Quality Verification Step
[0266] Transferring only heated purified water that meets quality standards by measuring the temperature range of 42~48℃, dissolved oxygen concentration of 3~5 ppm, and electrical conductivity of 5~15 μS / cm to the next stage is intended to prevent defective intermediate products from being fed into subsequent processes.
[0267] Controlling the total heating time to 20 to 50 minutes is intended to balance production efficiency and quality.
[0268] Adding heated purified water to the citric acid solution preparation step within one hour of preparation is intended to prevent a drop in temperature and a re-increase in dissolved oxygen.
[0269] Technical Significance and Critical Importance of the Citric Acid Aqueous Solution Preparation Step
[0270] Overall Significance of the Citric Acid Solution Preparation Step
[0271] The step of preparing the citric acid aqueous solution of the present invention involves dissolving citric acid in heated purified water to adjust the pH and prepare a transparent acidic aqueous solution. Citric acid plays a key role in the stability of the final product as a pH regulator and chelating agent of the composition.
[0272] Stirring the heated purified water at a speed of 50 to 80 rpm is intended to ensure uniform dispersion when adding citric acid. A low stirring speed of less than 50 rpm causes the citric acid powder to settle at the bottom, aggregate, and slow down dissolution, while a high stirring speed exceeding 80 rpm can cause the citric acid powder to scatter above the water surface due to the formation of vortices, potentially leading to loss.
[0273] Critical Significance of the Citric Acid Preparation Step
[0274] Classifying citric acid powder by passing it through a 200-400 mesh sieve to obtain particles with a diameter in the range of 40-75㎛ is intended to optimize the balance between dissolution speed and handling. Fine particles smaller than 40㎛ have a fast dissolution speed but are prone to scattering and hinder the working environment, while large particles exceeding 75㎛ have a slow dissolution speed, extending manufacturing time. Experimental results confirmed that the 40-75㎛ range, particularly the 50-65㎛ size, is optimal.
[0275] Limiting the moisture content to 0.5% by weight or less is intended to ensure the stability of citric acid and to avoid adding unnecessary moisture to the composition. A moisture content exceeding 0.5% by weight can cause the citric acid to caking and form lumps, and also increases the risk of microbial growth.
[0276] The requirement for a purity of 99.5% or higher is intended to prevent quality degradation caused by impurities. Impurities can cause precipitation, discoloration, or microbial contamination.
[0277] Critical significance of the first citric acid dissolution step
[0278] The first addition of 30 to 50 weight percent of the total citric acid is intended to achieve efficient dissolution while preventing a rapid decrease in pH. If a small amount of less than 30 weight percent is added, the effect of divided addition is negligible, and if more than 50 weight percent is added, there is no significant difference from adding it all at once, so a rapid decrease in pH is not sufficiently prevented.
[0279] The purpose of uniformly spraying citric acid onto the surface of heated purified water is to prevent localized supersaturation. If it is added intensively at one point, the concentration of citric acid in that area becomes very high, which actually slows down the dissolution rate and causes aggregation.
[0280] Increasing the stirring speed to 80–120 rpm is intended to promote rapid dissolution after the first addition. By applying a speed higher than the initial stirring speed of 50–80 rpm, the contact between the citric acid particles and water is increased.
[0281] Mixing for 3 to 8 minutes is intended to provide sufficient time for the solubility of the primary citric acid to reach 70 to 85%. Short mixing times of less than 3 minutes result in incomplete dissolution, while long mixing times exceeding 8 minutes result in minimal improvement in efficiency.
[0282] Critical Significance of the Second Citric Acid Input Step
[0283] The purpose of adding the second citric acid after confirming that the pH of the mixture has dropped to the range of 3.5 to 4.5 by measuring the pH of the mixture with a glass electrode pH meter is to ensure that the additional addition is made when the first citric acid is sufficiently dissolved and pH buffering capacity is formed. If the pH drops excessively below 3.5, there is a risk that the subsequently added sodium benzoate will precipitate, and if the pH exceeds 4.5, it means that the citric acid has not been sufficiently dissolved.
[0284] The secondary citric acid, corresponding to the remaining amount of 50 to 70% by weight, is added slowly over 2 to 5 minutes to prevent rapid pH changes. If added in a short time of less than 2 minutes, there is no significant difference from adding it all at once, and if added over a long time exceeding 5 minutes, only the process time is extended.
[0285] Maintaining the stirring speed at 100 to 150 rpm is intended to rapidly disperse the secondary citric acid while preventing the formation of excessive vortices.
[0286] Critical Significance of the High-Speed Stirring Dissolution Step
[0287] Raising the temperature of the mixture to 45–52°C is intended to increase the solubility of citric acid and promote complete dissolution. The solubility of citric acid increases with temperature (approximately 133 g / 100 mL at 20°C and approximately 187 g / 100 mL at 50°C), and undissolved particles can be rapidly dissolved in the 45–52°C range. At low temperatures below 45°C, the dissolution rate is slow, and if it exceeds 52°C, energy is wasted due to excessive heating and may affect some heat-sensitive components.
[0288] Increasing the stirring speed to 150–200 rpm is intended to form strong turbulence to suspend undissolved particles at the bottom and maximize the dissolution surface area. Low speeds below 150 rpm fail to sufficiently suspend bottom particles, while high speeds exceeding 200 rpm increase air entrainment and lead to excessive energy consumption.
[0289] Stirring vigorously for 8 to 15 minutes is to provide sufficient time for the solubility of citric acid to reach over 95%.
[0290] Forming a vortex on the surface of the mixture to cause undissolved particles at the bottom to float is a specific explanation of the purpose of high-speed stirring.
[0291] Critical significance of the solubility verification step
[0292] Reducing the stirring speed to 60 to 100 rpm is intended to remove air bubbles introduced by high-speed stirring and to measure quality in a stable state.
[0293] Measuring light transmittance at a wavelength of 600 nm using a UV-Vis spectrophotometer with a quartz cell having a path length of 10 mm is intended to quantitatively evaluate the transparency of an aqueous citric acid solution. 600 nm is in the visible light range and has a high correlation with transparency perceived by the naked eye. A transmittance of 85% or higher indicates a level that appears transparent to the naked eye and means that there are almost no undissolved particles or impurities.
[0294] Checking whether suspended particles are observed visually is a simple way to complement spectrophotometric measurements.
[0295] Checking whether the pH is in the range of 3.0 to 4.0 is to confirm that citric acid has been dissolved to the target concentration. A pH below 3.0 indicates an excess of citric acid or an insufficient amount of water, while a pH above 4.0 indicates a shortage of citric acid or incomplete dissolution.
[0296] Critical Significance of the Citric Acid Solution Filtration Step
[0297] Passing an aqueous citric acid solution through a stainless steel mesh filter with pores of 10 to 30 µm is intended to finally remove undissolved particles and impurities. Fine pores smaller than 10 µm clog quickly, slowing down the filtration speed, while pores larger than 30 µm allow some particles to pass through.
[0298] Controlling the filtration speed to 20 to 60 liters per minute is intended to balance filtration efficiency and productivity.
[0299] Critical Significance of the Quality Verification Step for Aqueous Citric Acid Solution
[0300] It is for quality assurance to transfer only aqueous citric acid solutions that satisfy quality standards by measuring pH 3.0~4.0, citric acid concentration 1~8% by weight, permeability 90% or higher, and temperature 42~50℃ to the next step.
[0301] The purpose of measuring the concentration of citric acid by titration is to verify the accurate concentration. The concentration is calculated by finding the point where all three carboxyl groups of citric acid are neutralized by titrating with a standard sodium hydroxide solution.
[0302] Controlling the total manufacturing time to 20 to 40 minutes is intended to ensure efficiency.
[0303] Adding the citric acid aqueous solution to the first mixture preparation step within 30 minutes of preparation is intended to minimize temperature drop and quality change.
[0304] Technical Significance and Critical Importance of the First Mixture Preparation Step
[0305] Overall Significance of the First Mixture Preparation Step
[0306] The first mixture preparation step of the present invention is a step of sequentially adding and mixing sodium benzoate, an antistatic agent, an antifoaming agent, glycerin, propylene glycol, 1,2-hexanediol, and D-sorbitol into an aqueous citric acid solution, which is a core process for forming the basic framework of the composition and ensuring stability. The order and conditions of adding each component are optimized by closely considering the physicochemical properties of the components, which has a decisive influence on the quality and stability of the final product.
[0307] Critical significance of the sodium benzoate solution injection step
[0308] Preparing an aqueous sodium benzoate solution in advance is intended to solve the problems associated with the direct powder addition method. When sodium benzoate powder is added directly to an aqueous citric acid solution, some of it is converted into benzoic acid under acidic conditions (pH 3.0–4.0), which can cause a rapid decrease in solubility and precipitation. This problem can be prevented by completely dissolving the powder under neutral or weakly alkaline conditions beforehand and then adding it.
[0309] Using purified water preheated to 35–45°C is intended to improve the solubility of sodium benzoate and shorten the dissolution time. The solubility of sodium benzoate increases from approximately 66 g / 100 mL at 20°C to approximately 95 g / 100 mL at 40°C. Low temperatures below 35°C result in a slow dissolution rate, while temperatures exceeding 45°C lead to energy waste due to excessive heating.
[0310] Dissolving at a concentration of 10 to 20 weight percent is the optimal concentration that is completely soluble without being excessively diluted. A low concentration of less than 10 weight percent adds unnecessary moisture to the composition, while a high concentration exceeding 20 weight percent approaches the solubility limit and poses a risk of recrystallization.
[0311] Preparing a clear aqueous solution by mixing with high-speed stirring at 200 to 300 rpm for 5 to 10 minutes is intended to ensure that sodium benzoate is completely dissolved. A clear appearance is an indicator that the solubility is close to 100%.
[0312] Maintaining the temperature at 40–48°C when adding a sodium benzoate aqueous solution to a citric acid aqueous solution is intended to minimize the temperature difference between the two solutions and prevent local temperature non-uniformity. If the temperature difference is 10°C or more, convection becomes unstable during mixing, and supercooling may occur in some areas, potentially leading to recrystallization.
[0313] The sodium benzoate aqueous solution is added slowly over 1 to 3 minutes to prevent a sudden change in pH. The sodium benzoate aqueous solution has a pH of 7 to 8, which raises the pH when mixed with an acidic citric acid aqueous solution. By adding and mixing slowly, the buffering capacity of citric acid is activated, allowing the pH to change gradually.
[0314] Maintaining the stirring speed at 80 to 120 rpm is intended to ensure uniform mixing while minimizing air entrainment.
[0315] Real-time monitoring of pH during mixing to ensure it remains within the 4.0–5.0 range is intended to detect quality deviations early. If the pH drops below 4.0, it indicates a deficiency of sodium benzoate or an excess of citric acid, and if it exceeds 5.0, it indicates an excess of sodium benzoate or a deficiency of citric acid.
[0316] Critical Significance of the Antistatic Agent Injection Step
[0317] The reason for directly adding an antistatic agent with 80% by weight or more of laurylpyridium chloride as the main component to a citrate-sodium benzoate mixture is that the liquid or water-soluble form of the antistatic agent disperses well without prior treatment.
[0318] The purpose of slowly adding the antistatic agent by dripping is to prevent aggregation caused by electrostatic repulsion between cationic substances. Laurylpyridium chloride is a quaternary ammonium cation and has the same charge as the dialkyl ester ammonium methosulfate to be added later; therefore, if it comes into contact with a high concentration, it may aggregate due to the salting-out effect.
[0319] Increasing the stirring speed to 100~150 rpm is intended to promote the rapid dispersion of the antistatic agent.
[0320] Mixing for 3 to 8 minutes is intended to provide sufficient time for the antistatic agent to be uniformly dispersed.
[0321] Maintaining the temperature of the mixture at 42~50℃ is intended to maintain the viscosity of the antistatic agent at a low level to improve dispersibility.
[0322] Critical Significance of the Antifoaming Agent Emulsion Injection Step
[0323] Preparing an antifoaming agent emulsion by pre-mixing a polydimethylsiloxane-based antifoaming agent with a portion of propylene glycol (40 to 60% by weight of the total amount of propylene glycol added) is a key technology for dramatically improving the water-based dispersibility of the antifoaming agent.
[0324] Mixing the defoamer and propylene glycol in a weight ratio of 1:2 to 1:5 in separate containers is intended to achieve an optimal emulsion state. A low propylene glycol ratio of less than 1:2 results in high viscosity of the defoamer, making mixing difficult and causing incomplete emulsification, while a high ratio exceeding 1:5 leads to excessive dilution, which consumes unnecessary propylene glycol and may result in a shortage of residual propylene glycol to be added in subsequent steps.
[0325] Stirring at a speed of 150 to 250 rpm for 5 to 12 minutes is a sufficient condition for the antifoaming agent to be completely dispersed in propylene glycol to form a uniform emulsion. Stirring until the appearance becomes a uniform milky white liquid is a method to visually confirm that the emulsification is complete.
[0326] Maintaining the stirring speed at 120 to 180 rpm when adding the antifoaming agent emulsion to the first mixture is intended to ensure that the fine droplets of the emulsion are dispersed quickly without being destroyed.
[0327] Slowly adding it over 2 to 6 minutes is intended to provide sufficient time for the emulsion to be emulsified and dispersed in the aqueous mixture. If added all at once, the concentration of the antifoaming agent may increase locally, causing aggregation.
[0328] Continuous mixing for 5 to 12 minutes to finely reduce the antifoaming agent droplet size to 5㎛ or less is intended to maximize antifoaming efficiency. When the droplet size is 5㎛ or less, penetration into the foam film occurs rapidly and effectively.
[0329] Critical significance of the first glycerin addition step
[0330] Adding 60 to 80 weight percent of the total glycerin amount in the first step is a key strategy to prevent a rapid increase in viscosity by gradually increasing the viscosity of the mixture. If a small amount of less than 60 weight percent is added, the effect of divided addition is negligible, and if more than 80 weight percent is added, it is similar to adding almost the entire amount, causing the viscosity to rise rapidly.
[0331] Adding glycerin slowly by dripping is intended to prevent the formation of localized high-viscosity regions. Since glycerin is very viscous with a viscosity of about 1400 cP at room temperature, if added all at once, it may settle at the bottom and form lumps before mixing.
[0332] Maintaining the stirring speed at 100 to 150 rpm is intended to maintain effective mixing despite the increasing viscosity.
[0333] Mixing for 8 to 15 minutes to increase the viscosity to a range of 50 to 150 cP is intended to achieve the first target viscosity. A value of less than 50 cP indicates that the glycerin is not sufficiently dispersed, while a value exceeding 150 cP indicates that the amount of glycerin added is excessive or the mixing time is insufficient.
[0334] Measuring viscosity using a Brookfield viscometer at a shear rate of 60 rpm at 25°C is intended to obtain reproducible viscosity values under standardized conditions.
[0335] Critical Significance of the Residual Propylene Glycol Input Step
[0336] Adding the remaining amount of propylene glycol (40 to 60% by weight of the total amount of propylene glycol added) that is left over from the emulsification of the antifoaming agent to the first mixture is intended to provide the moisturizing and compatibility functions of propylene glycol to the entire composition.
[0337] Slowly adding propylene glycol by dropwise method is intended to ensure uniform dispersion. Although propylene glycol has a lower viscosity than glycerin (about 60 cP), it is still viscous, so it is advantageous to add it slowly.
[0338] Maintaining the stirring speed at 80 to 120 rpm is intended to ensure that the propylene glycol is uniformly dispersed throughout the mixture.
[0339] Mixing for 5 to 10 minutes is sufficient time for propylene glycol to become fully compatible with the other ingredients.
[0340] Critical Significance of the Secondary Glycerin Intake Step
[0341] The second addition of the remaining glycerin (20 to 40% by weight of the total glycerin input) is intended to finally adjust the viscosity of the mixture to the target range.
[0342] Slowly adding by dripping and increasing the stirring speed to 120 to 180 rpm is intended to maintain effective mixing despite the increasing viscosity.
[0343] Mixing vigorously for 10 to 20 minutes to increase the viscosity to a range of 200 to 400 cP is intended to achieve a secondary target viscosity. This viscosity range is suitable for uniformly mixing the 1,2-hexanediol and D-sorbitol to be added later.
[0344] Critical significance of the 1,2-hexanediol input step
[0345] The sequential addition order of 1,2-hexanediol before D-sorbitol is an optimized strategy that takes into account the physicochemical properties of each component. Since 1,2-hexanediol is relatively hydrophobic due to its six-carbon hydrophobic chain, it should be preferentially placed in the hydrophobic region of the surfactant structure.
[0346] 1,2-hexanediol is added dropwise to ensure that the hydrophobic component is uniformly dispersed in the aqueous mixture.
[0347] Increasing the stirring speed to 150 to 200 rpm is intended to provide strong shear force to enable effective emulsification at the interface between hydrophobic and hydrophilic components.
[0348] Mixing vigorously for 5 to 12 minutes is a sufficient amount of time for 1,2-hexanediol to penetrate into the hydrophobic regions of the coacervate structure and be stably positioned.
[0349] Critical significance of the D-sorbitol solution injection step
[0350] Pre-dissolving D-sorbitol in purified water preheated to 40–45°C at a concentration of 20–40% by weight is intended to prevent aggregation that occurs when the powder is added directly. Since D-sorbitol forms strong hydrogen bonds with water due to its six hydroxyl groups, it has high solubility but a relatively slow dissolution rate. By preparing a clear aqueous solution through pre-dissolution, it disperses quickly and uniformly when added to the first mixture.
[0351] Slowly adding the D-sorbitol aqueous solution dropwise is intended to prevent a rapid increase in viscosity. Since D-sorbitol has the property of increasing viscosity by forming hydrogen bond networks, it must be added slowly while being thoroughly mixed.
[0352] Maintaining the stirring speed at 120 to 180 rpm is intended to ensure that D-sorbitol is uniformly dispersed throughout the composition.
[0353] Mixing for 8 to 15 minutes is sufficient time for D-sorbitol to be placed in the hydrophilic regions of the surfactant structure and for a hydrogen bond network to be formed.
[0354] Critical Significance of the First Mixture Quality Verification Stage
[0355] Transferring only the first mixture that satisfies quality standards to the next stage by measuring pH 4.5~5.5, viscosity 500~800 cP, temperature 40~48℃, and permeability 80% or higher is the core of process quality control.
[0356] The pH range of 4.5 to 5.5 is a stable range for cationic surfactants and a range in which subsequent added components can also exist stably.
[0357] A viscosity of 500 to 800 cP is suitable for uniformly mixing the cationic surfactant to be subsequently added.
[0358] Controlling the total manufacturing time to 60 to 120 minutes is intended to ensure production efficiency.
[0359] Adding the first mixture to the second mixture preparation step within 2 hours of preparation is intended to prevent changes in viscosity and phase separation.
[0360] Technical Significance and Critical Importance of the Second Mixture Preparation Step
[0361] Overall Significance of the Second Mixture Preparation Step
[0362] The second mixture preparation step of the present invention is a step of adding a dialkyl ester ammonium methosulfate cationic surfactant to the first mixture and mixing for a sufficient amount of time to uniformly disperse the surfactant and lay the foundation for the formation of a coacervate.
[0363] Critical significance of the temperature control stage
[0364] The temperature of the first mixture is controlled to a range of 40 to 50°C to optimize the viscosity of the cationic surfactant and maximize mixing efficiency. Although dialkyl ester ammonium methosulfate is in liquid form, its viscosity changes significantly with temperature. At low temperatures below 40°C, the viscosity is high, resulting in poor flowability and difficulty in mixing; at temperatures above 50°C, the viscosity decreases, but there is a risk that some components may decompose or deteriorate.
[0365] Maintaining the stirring speed at 80 to 120 rpm is intended to maintain the uniformity of the mixture during the temperature control process.
[0366] Controlling the temperature using an indirect heating method with a double-jacketed heating tank is intended to prevent local overheating.
[0367] Critical significance of the cationic surfactant addition step
[0368] The dialkyl ester ammonium methosulfate is added to the first mixture slowly by dropwise adding to ensure that the cationic surfactant is uniformly dispersed and to prevent aggregation. Since the cationic surfactant has high viscosity and a density difference compared to the aqueous mixture, adding it all at once may cause it to form clumps or settle at the bottom.
[0369] Setting the addition time to 3 to 10 minutes is intended to provide time for each part to be sufficiently mixed as the entire cationic surfactant is gradually added.
[0370] Increasing the stirring speed to 100 to 150 rpm is intended to effectively disperse the highly viscous cationic surfactant.
[0371] Maintaining the temperature of the mixture at 40~50℃ is intended to maintain the viscosity of the cationic surfactant at a low level to improve dispersibility.
[0372] Critical Significance of the Long-Time Mixing Step
[0373] Continuously mixing the mixture for 2 to 5 hours at a temperature range of 40 to 50°C after the addition of the cationic surfactant is a key process to ensure that the cationic surfactant is completely and uniformly dispersed throughout the composition and that sufficient interaction with other components takes place.
[0374] Short mixing times of less than 2 hours result in incomplete dispersion of cationic surfactants, leading to the localized existence of high and low concentration regions, which causes non-uniform performance of the final product. Long mixing times exceeding 5 hours only reduce production efficiency while providing minimal additional quality improvement effects.
[0375] Maintaining a stirring speed of 80 to 120 rpm is intended to prevent foaming caused by excessive shear force while maintaining effective mixing. When mixing for a long time, a stirring speed that is too high can introduce air and cause foaming.
[0376] Maintaining the temperature at a constant 40–50°C is intended to maintain the physicochemical state of the cationic surfactant in a stable manner. Changes in temperature can alter the viscosity and fluidity of the surfactant, potentially reducing mixing efficiency.
[0377] Critical Significance of the Uniformity Verification Step
[0378] Taking samples to check viscosity and appearance after 1 hour, 2 hours, and at the time of final mixing completion is to monitor the mixing progress and to verify whether the target quality has been reached.
[0379] Taking samples from the upper, middle, and lower layers is intended to evaluate the uniformity within the tank. Since cationic surfactants can have a density different from water, differences in interlayer concentration may occur if they are not sufficiently mixed.
[0380] Verifying that the viscosity deviation of each sample is within ±5% is a quantitative indicator of uniformity. A deviation exceeding ±5% indicates insufficient mixing.
[0381] Verifying whether the appearance is uniformly milky white or translucent is a visual quality assessment. An uneven appearance, separation of layers, or precipitation indicates quality problems.
[0382] Critical Significance of the Second Mixture Quality Verification Stage
[0383] It is for quality assurance to transfer only the second mixture that satisfies quality standards by measuring pH 4.5~5.5, viscosity 1000~2000 cP, temperature 42~48℃, and appearance uniformity to the next stage.
[0384] The viscosity of 1000 to 2000 cP is a range in which the cationic surfactant is sufficiently dispersed and appropriately increased from the viscosity of the first mixture (500 to 800 cP).
[0385] Controlling the total manufacturing time to 2.5 to 6 hours is the sum of the 2 to 5 hours of the long-term mixing stage and the time for temperature control, input, and quality verification.
[0386] Adding the second mixture to the third mixture preparation step within 4 hours of preparation is to maintain the dispersed state of the cationic surfactant.
[0387] Technical Significance and Critical Importance of the Third Mixture Preparation Step
[0388] Overall Significance of the Third Mixture Preparation Step
[0389] The third mixture preparation step of the present invention is a step of adding an amphoteric surfactant and ethanol to the second mixture to initiate the formation of a coacervate between the cationic surfactant and the amphoteric surfactant, utilizing the compatibilization effect of ethanol, and safely removing ethanol volatile substances.
[0390] Critical significance of the temperature maintenance stage
[0391] Maintaining the temperature of the second mixture at 40 to 50°C is intended to provide optimal temperature conditions for the addition of amphoteric surfactants.
[0392] Maintaining the stirring speed at 80 to 120 rpm is to ensure temperature uniformity.
[0393] Critical Significance of the Amphoteric Surfactant Addition Step
[0394] Lauramidopropyl betaine or cocamidopropyl betaine is slowly added to the second mixture in a dropwise manner to allow the formation of coacervates with the cationic surfactant to proceed in stages.
[0395] Setting the injection time to 5 to 15 minutes is intended to allow the amphoteric surfactant to disperse sufficiently while the coacervate formation proceeds gradually.
[0396] Increasing the stirring speed to 100~150 rpm is intended to promote rapid dispersion of the amphoteric surfactant.
[0397] Precisely controlling the input amount so that the weight ratio of cationic surfactants to amphoteric surfactants is 1:1.5 to 1:4 is a key condition for optimal coacervate formation. A low ratio of less than 1:1.5 results in a lack of amphoteric surfactants, causing some cationic surfactants to remain in a free state, while a high ratio exceeding 1:4 results in an excess amount of amphoteric surfactants remaining, which increases foaming and reduces economic efficiency.
[0398] Critical significance of the coacervate-forming mixing step
[0399] After the addition of the amphoteric surfactant, the mixture is continuously mixed at 40 to 50°C for 1 to 3 hours to ensure that the formation of coacervates through electrostatic interaction between the cationic surfactant and the amphoteric surfactant proceeds sufficiently.
[0400] Maintaining the stirring speed at 80 to 120 rpm is intended to ensure that coacervate particles are formed to an appropriate size and that excessive aggregation is prevented.
[0401] Observing that the appearance of the mixture gradually becomes opaque and its viscosity increases during mixing is a method to visually confirm that coacervate formation is in progress.
[0402] Critical significance of the ethanol injection step
[0403] Gradually adding ethanol to the third mixture by a dropwise method is intended to prevent rapid changes in viscosity and volatilization.
[0404] Setting the input time to 2 to 8 minutes is intended to ensure that the ethanol is uniformly dispersed and that excessive volatilization does not occur.
[0405] Reducing the stirring speed to 40 to 70 rpm is intended to prevent rapid volatilization of ethanol. Since a high stirring speed increases the surface area and promotes volatilization, it is maintained at a low speed.
[0406] Lowering the temperature of the mixture to 38–45°C is intended to minimize the volatile loss of ethanol. Although the boiling point of ethanol is 78°C, a significant amount can volatilize even at temperatures above 40°C due to its high vapor pressure.
[0407] Critical significance of the ethanol mixing step
[0408] Mixing the mixture at 38 to 45°C for 0.5 to 4 hours after the addition of ethanol is complete is intended to ensure that the ethanol is uniformly dispersed throughout the composition and to achieve a compatibility effect.
[0409] Maintaining the stirring speed at a low rate of 40 to 70 rpm is intended to achieve a uniform mixture while minimizing the volatilization of ethanol.
[0410] The mixing time is adjusted according to the amount of ethanol added and the temperature; the higher the ethanol content and the higher the temperature, the longer the mixing time is required.
[0411] Critical Significance of the Volatile Substance Removal Step
[0412] Capturing and removing volatile ethanol substances generated during the mixing process using HEPA filters or activated carbon adsorption dust collectors is an essential process for ensuring the safety of the working environment and complying with environmental regulations.
[0413] The HEPA filter method removes particulate matter by passing air containing ethanol vapor through a filter and recovers the ethanol vapor by condensing it. The activated carbon adsorption method lowers the concentration in the air by physically adsorbing ethanol vapor onto the surface of activated carbon.
[0414] Achieving a capture efficiency of 85% or higher is intended to maintain the ethanol concentration in the work environment below the exposure limit (1000 ppm, 8-hour hourly weighted average) under the Occupational Safety and Health Act.
[0415] The dust collector is connected to the top of the heating tank so that volatile ethanol is immediately captured.
[0416] Install a real-time air quality monitoring device to measure the ethanol concentration in the workspace and verify that it is maintained below safety standards.
[0417] Critical Significance of the Third Mixture Quality Verification Stage
[0418] Transferring only the third mixture that satisfies quality standards by measuring pH 4.5~5.5, viscosity 1500~2500 cP, ethanol content 5~8 parts by weight, and temperature 38~45℃ to the next step is for quality assurance.
[0419] Ethanol content is accurately measured using gas chromatography.
[0420] Viscosity of 1500–2500 cP is a range in which viscosity increases with the addition of amphoteric surfactants and ethanol.
[0421] Controlling the total manufacturing time to 2 to 8 hours is intended to ensure production efficiency.
[0422] Adding the third mixture to the fourth mixture preparation step within 3 hours of preparation is intended to maintain the coacervate structure and the ethanol dispersion state.
[0423] Technical Significance and Critical Importance of the 4th Mixture Preparation Step
[0424] Overall Significance of the 4th Mixture Preparation Step
[0425] The fourth mixture preparation step of the present invention is a step of cooling the third mixture to a low temperature, adding a fragrance, and mixing at a low temperature to minimize volatile loss of the fragrance and allow the fragrance to penetrate into the coacervate structure.
[0426] Critical significance of the cooling phase
[0427] Cooling the third mixture to 3 to 10°C is a key process to minimize the volatile loss of the fragrance by lowering the temperature before adding the fragrance.
[0428] Using a double-jacketed cooling tank as a cooling method to circulate cooling water at 0 to 5°C is intended to achieve uniform temperature control through indirect cooling.
[0429] Controlling the cooling rate to 1 to 3°C per minute is intended to prevent phase separation caused by rapid temperature changes.
[0430] Maintaining the stirring speed at 60 to 100 rpm is intended to ensure temperature uniformity during the cooling process.
[0431] Controlling the cooling time to 15 to 35 minutes is the time required to cool from 38 to 45°C to 3 to 10°C.
[0432] Critical Significance of the Temperature Equalization Step
[0433] Stirring the mixture while maintaining the temperature for 5 to 15 minutes after it reaches the target temperature is intended to allow the entire tank to reach thermal equilibrium.
[0434] Uniformizing the temperature deviation of the upper, middle, and lower layers to within ±0.5℃ is intended to provide identical conditions in all parts when flavoring is added.
[0435] The critical significance of the flavor addition step
[0436] The purpose of adding the fragrance to the third mixture after pre-cooling it to 3~10℃ is to lower the temperature of the fragrance itself and minimize the temperature rise of the mixture.
[0437] The purpose of slowly adding the fragrance by dripping is to ensure that the fragrance is uniformly dispersed and gradually penetrates into the coacervate structure.
[0438] Setting the input time to 3 to 12 minutes is an appropriate input speed considering the flavor content (12 to 18 parts by weight).
[0439] Maintaining the stirring speed at 80 to 120 rpm is intended to promote rapid dispersion of the flavoring.
[0440] Maintaining the temperature of the mixture within the range of 3 to 10°C is intended to minimize the volatile loss of the fragrance.
[0441] Critical significance of the low-temperature mixing step
[0442] Mixing the mixture at 3 to 10°C for 5 to 20 minutes after adding the fragrance is intended to ensure that the fragrance is uniformly dispersed throughout the composition while minimizing volatile loss.
[0443] Short mixing times of less than 5 minutes result in insufficient dispersion of the fragrance, while long mixing times exceeding 20 minutes produce minimal additional effects.
[0444] Maintaining the stirring speed at 80 to 120 rpm is to maintain effective mixing.
[0445] By maintaining low temperature conditions, the loss of volatile components of the fragrance can be reduced by 35–50% compared to room temperature mixing.
[0446] Critical Significance of the 4th Mixture Quality Verification Step
[0447] It is for quality assurance to transfer only the fourth mixture that satisfies quality standards by measuring pH 4.5~5.5, viscosity 2000~3500 cP, fragrance content 12~18 parts by weight, and temperature 5~10℃ to the next step.
[0448] The fragrance content is quantitatively analyzed using gas chromatography-mass spectrometry.
[0449] Viscosity of 2000~3500 cP is a range in which viscosity increases with the addition of fragrance.
[0450] Controlling the total manufacturing time to 30 to 70 minutes is intended to ensure production efficiency.
[0451] Immediately transferring the fourth mixture to the low-temperature aging process is intended to maintain a low temperature and prevent flavor loss.
[0452] Technical Significance and Critical Importance of the Fabric Softener Composition Completion Stage
[0453] Overall Significance of the Fabric Softener Composition Completion Stage
[0454] The step of completing the fabric softener composition of the present invention is to optimize the encapsulation of the fragrance by aging the fourth mixture at a low temperature for a long time, and then cooling it to room temperature to complete the final composition.
[0455] The critical significance of the low-temperature aging stage
[0456] Aging the fourth mixture at a temperature of 3 to 10°C for 10 to 30 hours is a key process to allow the flavoring to sufficiently penetrate into the coacervate structure and for the interactions between the components to reach equilibrium.
[0457] Short aging times of less than 10 hours result in incomplete encapsulation of the flavoring, leading to reduced scent persistence, while long aging times exceeding 30 hours only reduce production efficiency without providing any additional effects.
[0458] During aging, stopping stirring or stirring slowly at a very low speed (10–30 rpm) is intended to allow time for the coacervate structure to stabilize and for the flavoring to move inward by diffusion.
[0459] Maintaining a low temperature of 3 to 10°C is a temperature at which molecular diffusion can occur while minimizing the volatilization of the fragrance.
[0460] The aging container is sealed to prevent the volatilization of flavorings and external contamination.
[0461] Critical Significance of the Gradual Warming Stage
[0462] After the aging process is complete, the mixture is gradually heated to 10–25°C to prevent the destruction of the coacervate structure due to rapid temperature changes.
[0463] Controlling the heating rate to 0.5 to 2°C per minute is intended to raise the temperature at a very slow rate, thereby providing time for each component to adapt to the new temperature.
[0464] Gradually increasing the stirring speed to 40 to 80 rpm is to ensure temperature uniformity.
[0465] Controlling the heating time to 10 to 25 minutes is the time required to raise the temperature from 3 to 10°C to 10 to 25°C.
[0466] Critical Significance of the Final Mixing Step
[0467] The final mixing of the mixture at a speed of 60 to 100 rpm for 10 to 30 minutes after the mixture reaches 10 to 25°C is intended to ensure uniformity of the entire composition and stabilize the viscosity.
[0468] Measure the viscosity during mixing to check if it has reached the target range of 2500 to 6000 cP.
[0469] Critical Significance of the Composition Quality Verification Step
[0470] Transferring only fabric softener compositions that satisfy quality standards by measuring pH 4.5~5.5, viscosity 2500~6000 cP, temperature 10~25℃, fragrance retention rate 90% or more, and appearance uniformity to the fabric impregnation process is for final quality assurance.
[0471] The fragrance retention rate is the ratio of the fragrance remaining in the final composition to the initial input amount, measured by gas chromatography. A retention rate of 90% or higher means that fragrance loss during the manufacturing process has been minimized to 10% or less.
[0472] A viscosity of 2500 to 6000 cP is the optimal range for easy impregnation into fabric without leakage during storage and transportation.
[0473] Controlling the total manufacturing time to 11 to 32 hours is the total time including the low-temperature aging stage (10 to 30 hours).
[0474] The composition is introduced into the fabric impregnation process within 48 hours of manufacturing to ensure optimal quality for use.
[0475] Technical Significance and Critical Importance of the Fabric Softener Sheet Manufacturing Stage
[0476] Overall Significance of the Fabric Softener Sheet Manufacturing Process
[0477] The step of manufacturing a fabric softener sheet of the present invention is to remove static electricity from a fabric composed of natural pulp and viscose fibers, and then impregnate it with a fabric softener composition to complete the final product.
[0478] The critical significance of the fabric preparation stage
[0479] The purpose of preparing a fabric composed of 30 to 90 weight percent natural pulp and 10 to 70 weight percent viscose fiber with a basis weight of 40 to 80 g / m² is to ensure appropriate absorbency and mechanical strength.
[0480] The fabric used is manufactured using a wet nonwoven fabric manufacturing process (spunlace, airlaid, etc.).
[0481] The fabric is generally cut and used in a size ranging from 20cm × 25cm to 25cm × 30cm.
[0482] Critical Significance of the Electrostatic Discharge Step
[0483] Grounding the fabric to a metal or conductive roller or conveyor is intended to discharge static electricity accumulated in the fabric to the ground.
[0484] The purpose of simultaneously irradiating the surface of a fabric with positive and negative ions using an ionizer is to neutralize the electric charge on the surface of the fabric. The ionizer generates positive and negative ions by ionizing air using a corona discharge method.
[0485] Installing the ionizer at a distance of 10 to 30 cm from the surface of the fabric is an effective ion irradiation range.
[0486] Setting the irradiation time to 5 to 20 seconds is sufficient time to remove more than 95% of static electricity from the fabric surface.
[0487] Verify the electrostatic removal effect using an electrostatic meter to check if the surface potential has decreased to ±100V or less.
[0488] The removal of static electricity improves the absorption rate of the composition by 40 to 60 percent and reduces the product defect rate caused by uneven impregnation by more than 65 percent.
[0489] Critical significance of the impregnation step
[0490] Impregnating the fabric softener composition into the static-free fabric is intended to ensure that the composition is uniformly absorbed into the fabric.
[0491] Dipping, spraying, or roll coating methods can be used for impregnation.
[0492] The dipping method is a method of immersing the fabric in a tank containing the composition and then withdrawing it. The immersion time is set to 2 to 10 seconds, and the withdrawal speed is controlled to 5 to 20 meters per minute.
[0493] The spray method is a method of spraying a composition onto the surface of a fabric through a nozzle. The spray pressure is set to 1 to 3 bar, and the distance between the nozzle and the fabric is maintained at 10 to 30 cm.
[0494] The roll coating method is a transfer technique in which a roller coated with a composition is brought into contact with the fabric. The amount of impregnation is controlled by adjusting the roller's rotation speed and pressure.
[0495] It is appropriate to control the impregnation amount so that 15 to 35 g of the composition is absorbed per 1 m² of fabric. Less than 15 g results in insufficient softening effect, and more than 35 g results in the fabric becoming excessively wet, making it difficult to handle and extending the drying time.
[0496] Maintaining the temperature of the composition at 15 to 25°C is intended to maintain appropriate viscosity and optimize impregnation efficiency.
[0497] Critical significance of the dewatering step
[0498] Removing excess composition by passing the impregnated fabric between rollers or applying light compression is intended to control the final impregnation amount to a target range.
[0499] The amount of composition remaining on the fabric is precisely controlled by adjusting the roller spacing and pressure.
[0500] Critical significance of the drying stage
[0501] Natural drying or light air drying of the impregnated fabric at a temperature of 25 to 40°C is intended to reduce the stickiness of the fabric surface by evaporating some of the volatile components, such as ethanol.
[0502] Low temperatures below 25℃ result in a drying speed that is too slow, while high temperatures exceeding 40℃ increase the volatile loss of the fragrance and pose a risk of deterioration of the composition.
[0503] Set the drying time to 10 to 40 minutes and dry the fabric until the surface is dry and not sticky when touched by hand.
[0504] Excessive drying reduces the content of the composition, so caution should be exercised.
[0505] Critical Significance of the Final Product Quality Verification Stage
[0506] Only fabric softener sheets that meet quality standards, such as an impregnation amount of 12~30 g / m², a pH of 4.5~5.5, a moisture content of 15~35 wt%, and a fabric tensile strength of 20 N or more, are transferred to the packaging process to ensure the quality of the final product.
[0507] The impregnation amount is calculated as the difference in weight of the fabric before and after impregnation.
[0508] Moisture content is measured by the loss on drying method at 105℃.
[0509] Tensile strength is measured using a universal testing machine, and 20N or more is the minimum strength required to prevent breakage when rotating with clothes in a dryer.
[0510] The critical significance of the packaging stage
[0511] Packaging fabric softener sheets individually or in bulk and storing them in airtight containers is intended to prevent volatilization of the composition and external contamination.
[0512] For packaging materials, materials with excellent moisture resistance and barrier properties, such as polyethylene, polypropylene, and aluminum laminated film, are used.
[0513] After packaging, store the product in a cool, dark place to maintain quality.
[0514] Examples and Comparative Examples
[0515] Examples
[0516] To specifically demonstrate the effects of the present invention, the following examples were performed. Each example varied the composition and process conditions within the technical scope of the present invention, and all were capable of producing high-quality fabric softener sheets for laundry dryers.
[0517] Example 1: Preparation under standard conditions
[0518] In Example 1, a fabric softener sheet was manufactured by setting the content of each component of the present invention to an intermediate range and applying process conditions as standard conditions.
[0519] Composition formulation (based on 100 parts by weight total)
[0520] The mixture was formulated with 7.5 parts by weight of dialkyl ester ammonium methosulfate (16-18 carbon atoms alkyl group, liquid type), 14.0 parts by weight of lauramidopropyl betaine, 1.5 parts by weight of propylene glycol, 3.5 parts by weight of anhydrous citric acid (particle diameter 50 μm), 7.5 parts by weight of glycerin, 0.25 parts by weight of 1,2-hexanediol, 0.5 parts by weight of D-sorbitol, 2.5 parts by weight of sodium benzoate, 1.5 parts by weight of an antistatic agent containing 85% by weight of laurylpyridium chloride, 0.4 parts by weight of polydimethylsiloxane (viscosity 300 cSt, molecular weight 50,000), 6.5 parts by weight of ethanol, 15.0 parts by weight of fragrance (citrus-floral-musk complex fragrance), and the remainder being 39.4 parts by weight of purified water.
[0521] The weight ratio of the cationic surfactant to the amphoteric surfactant was 7.5:14.0, which was approximately 1:1.87.
[0522] Purified water manufacturing process
[0523] 200 liters of raw water were prepared and passed through a first mesh filter (230 mesh, pore size 63 µm) at a flow rate of 100 liters per minute. Subsequently, organic matter and residual chlorine were removed by passing the water through a second activated carbon filter (particle size 1.0 mm) for a contact time of 10 minutes. Sterilization treatment was performed in a third UV sterilization filter under conditions of a wavelength of 254 nm, an irradiation intensity of 45 mJ / cm², and an exposure time of 5 seconds. Metal ions and fine impurities were removed by passing the water through a fourth membrane filter (pore size 0.0001 µm, reverse osmosis method) at an operating pressure of 6 bar. The final purified water was obtained by passing the water through a fifth final line filter (SUS316 material, pore size 7 µm). The electrical conductivity of the produced purified water was 10 μS / cm, the total dissolved solids was 12 ppm, and the pH was 7.0. The purified water was stored in a stainless steel storage tank at 5°C.
[0524] Heating and Purifying Water Preparation Process
[0525] 150 liters of purified water were introduced into a double-jacketed heating tank (capacity 200 liters) made of SUS316 stainless steel. Hot water at 70°C was circulated through the double jacket, and the water was preheated to 25°C at a heating rate of 2°C per minute. Subsequently, the temperature of the hot water in the double jacket was raised to 88°C, and the purified water was stirred at 90 rpm while undergoing main heating to 45°C at a heating rate of 1.5°C per minute. After reaching the target temperature, the temperature was stabilized by maintaining it within the range of 45°C ± 0.5°C for 10 minutes. Next, nitrogen gas with a purity of 99.9% or higher was bubbled at a flow rate of 0.3 L / min for 10 minutes to reduce the dissolved oxygen concentration to 4 ppm. After bubbling, the stirring speed was increased to 120 rpm and stirred for 5 minutes to homogenize the temperature. The temperature of the heated purified water was 45°C, and the dissolved oxygen concentration was 4 ppm.
[0526] Citric acid aqueous solution manufacturing process
[0527] 5.25 g of anhydrous citric acid (total input amount 3.5 parts by weight) was prepared while stirring heated purified water at 60 rpm. Of this, 2.1 g (40% by weight) was first uniformly sprayed onto the water surface and added, and the stirring speed was increased to 100 rpm and mixed for 5 minutes. After confirming that the pH had dropped to 4.0, the remaining 3.15 g (60% by weight) was slowly added over 3 minutes, and the stirring speed was increased to 150 rpm. The temperature of the mixture was raised to 48°C, and the stirring speed was increased to 175 rpm for vigorous stirring for 10 minutes. The stirring speed was reduced to 80 rpm, and the light transmittance at a wavelength of 600 nm was measured using a UV-Vis spectrophotometer, resulting in 92%. The pH of the aqueous citric acid solution was 3.5, and the temperature was 46°C. The aqueous citric acid solution was passed through a stainless steel mesh filter with 20 µm pores to remove undissolved particles.
[0528] First mixture preparation process
[0529] 3.75 g of sodium benzoate was dissolved in 22.5 g of purified water preheated to 40°C to prepare 26.25 g of an aqueous sodium benzoate solution with a concentration of 15 wt%. This solution was slowly added to an aqueous citric acid solution over 2 minutes and mixed at 100 rpm for 5 minutes. The pH rose to 4.7.
[0530] 2.25 g of an antistatic agent containing 85 wt% laurylpyridium chloride was slowly added by a dropwise method, and the stirring speed was increased to 125 rpm and mixed for 5 minutes.
[0531] 0.6g of polydimethylsiloxane and 1.35g of propylene glycol (60% by weight of the total propylene glycol input amount of 2.25g) were mixed in a separate container at a weight ratio of 1:2.25 and stirred at 200 rpm for 8 minutes to prepare a milky white antifoaming agent emulsion. The antifoaming agent emulsion was slowly added to the first mixture over 4 minutes while stirring at 150 rpm, and the mixture was continuously mixed for 8 minutes.
[0532] 7.875g, which is 70% by weight of 11.25g of glycerin, was added first by a dropwise method and mixed at 125rpm for 10 minutes. The viscosity was measured and found to be 100cP.
[0533] The remaining 0.9g of propylene glycol (40% by weight of the total propylene glycol input) was added by a dropwise method and mixed at 100 rpm for 7 minutes.
[0534] 3.375 g of glycerin, which is 30% by weight of the remaining amount, was added in the second step by the dropwise method, and the stirring speed was increased to 150 rpm and vigorously mixed for 15 minutes. The viscosity was measured and found to be 300 cP.
[0535] 0.375g of 1,2-hexanediol was added dropwise and the stirring speed was increased to 175rpm and vigorously mixed for 8 minutes.
[0536] 0.75 g of D-sorbitol was dissolved in 2.25 g of purified water preheated to 43°C to prepare 3 g of an aqueous solution of D-sorbitol with a concentration of 25 wt%. This solution was added dropwise and mixed at 150 rpm for 10 minutes.
[0537] The pH of the first mixture was 5.0, the viscosity was 650 cP, and the temperature was 44℃.
[0538] Second mixture manufacturing process
[0539] The temperature of the first mixture was adjusted to 45°C and stirred at 100 rpm. 11.25 g of dialkyl ester ammonium methosulfate was added slowly dropwise over 5 minutes, and the stirring speed was increased to 125 rpm. After the addition was complete, the mixture was continuously mixed at 100 rpm for 3.5 hours at 45°C. After 1 hour, after 2 hours, and at the time of final mixing completion, samples were taken from the upper, middle, and lower layers, respectively, and the viscosity was measured; the deviation was within ±3%. The pH of the second mixture was 5.1, the viscosity was 1500 cP, and the temperature was 45°C.
[0540] Third mixture manufacturing process
[0541] The temperature of the second mixture was maintained at 45°C and stirred at 100 rpm. 21 g of lauramidopropyl betaine was added slowly dropwise over 10 minutes, and the stirring speed was increased to 125 rpm. The weight ratio of cationic surfactant to amphoteric surfactant was 11.25:21, which was approximately 1:1.87. After the addition was completed, the mixture was continuously mixed at 100 rpm for 2 hours at 45°C. During mixing, it was observed that the appearance of the mixture gradually became opaque and the viscosity increased.
[0542] 9.75 g of ethanol was slowly added dropwise over 5 minutes. The stirring speed was reduced to 55 rpm, and the temperature of the mixture was lowered to 42°C. After the ethanol addition was complete, the mixture was mixed at 55 rpm for 2 hours at 42°C. Volatile ethanol products generated during the mixing process were collected and removed using an activated carbon adsorption dust collector. The collection efficiency was 87%.
[0543] The pH of the third mixture was 5.0, the viscosity was 2000 cP, the ethanol content was 6.5 parts by weight, and the temperature was 42℃.
[0544] Preparation process of the fourth mixture
[0545] The third mixture was cooled to 6°C at a cooling rate of 2°C per minute using a double-jacketed cooling tank while circulating cooling water at 2°C. It was stirred at 80 rpm during cooling. After reaching the target temperature, the temperature was homogenized by maintaining it within the range of 6°C ± 0.5°C for 10 minutes.
[0546] 22.5g of fragrance (citrus-floral-musk complex fragrance) was pre-cooled to 6℃ and then slowly added by dropwise pouring over 8 minutes. The stirring speed was maintained at 100 rpm, and the temperature of the mixture was maintained within the 6℃ range. After the addition of the fragrance was completed, the mixture was mixed at 100 rpm for 12 minutes at 6℃.
[0547] The pH of the fourth mixture was 5.0, the viscosity was 2800 cP, the fragrance content was 15.0 parts by weight, and the temperature was 6℃.
[0548] Fabric softener composition completion process
[0549] The fourth mixture was aged in a sealed container at 6°C for 20 hours. During aging, it was slowly stirred at a low speed of 20 rpm.
[0550] After the maturation was complete, the mixture was gradually heated to 18°C at a heating rate of 1°C per minute. It was stirred at 60 rpm during the heating process.
[0551] After the mixture reached 18℃, it was finally mixed at 80 rpm for 20 minutes.
[0552] The pH of the finished fabric softener composition was 5.0, the viscosity was 3800 cP, the temperature was 18°C, and the fragrance retention rate was 93%. The appearance was a uniform milky white.
[0553] Fabric softener sheet manufacturing process
[0554] A fabric was prepared consisting of 65% by weight of natural pulp and 35% by weight of viscose fiber, with a basis weight of 60 g / m². The fabric was cut to a size of 22 cm × 27 cm.
[0555] The fabric was grounded to a conductive conveyor, and an ionizer was installed at a distance of 20 cm from the surface of the fabric to simultaneously irradiate positive and negative ions for 12 seconds. As confirmed by an electrostatic meter, the surface potential decreased to ±50V.
[0556] The fabric from which static electricity had been removed was immersed in a tank containing a fabric softener composition for 5 seconds using a dipping method, and then withdrawn at a speed of 12 meters per minute. The temperature of the composition was maintained at 20℃.
[0557] The impregnated fabric was passed between rollers to remove excess composition. The absorption amount of composition per 1 m² of fabric was 23 g.
[0558] The impregnated fabric was subjected to light air drying at a temperature of 32°C for 25 minutes. The surface of the fabric became dry and non-sticky when touched by hand.
[0559] The impregnation amount of the final fabric softener sheet was 20 g / m², the pH was 5.0, the moisture content was 25 wt%, and the tensile strength of the fabric was 28 N.
[0560] The fabric softener sheets were individually wrapped in polyethylene film and stored in airtight containers.
[0561] Example 2: Application of lower limit for component content
[0562] In Example 2, a fabric softener sheet was manufactured by setting the content of each component close to the lower limit within the scope of the invention.
[0563] Composition formulation (based on 100 parts by weight total)
[0564] It was formulated with 3.5 parts by weight of dialkyl ester ammonium methosulfate (12-14 carbon atoms alkyl group, liquid type), 10.5 parts by weight of cocamidopropyl betaine, 0.7 parts by weight of propylene glycol, 1.2 parts by weight of anhydrous citric acid (particle diameter 45 μm), 5.5 parts by weight of glycerin, 0.07 parts by weight of 1,2-hexanediol, 0.25 parts by weight of D-sorbitol, 0.5 parts by weight of sodium benzoate, 0.3 parts by weight of antistatic agent containing 82% by weight of laurylpyridium chloride, 0.08 parts by weight of polydimethylsiloxane (viscosity 150 cSt, molecular weight 15,000), 5.2 parts by weight of ethanol, 12.5 parts by weight of fragrance (single lavender scent), and the remainder being 59.73 parts by weight of purified water.
[0565] The weight ratio of the cationic surfactant to the amphoteric surfactant was 3.5:10.5, which was 1:3.
[0566] The manufacturing process was identical to that of Example 1, except that the input amounts of each component and some process conditions were adjusted. The process for preparing purified water was performed identically to that of Example 1. The purified water was heated to 42°C. When preparing the aqueous citric acid solution, 35% by weight was added in the first step and the remainder was added in the second step. When preparing the first mixture, 65% by weight of glycerin was added in the first step and the remainder was added in the second step. When preparing the second mixture, the mixing time was set to 2.2 hours. When preparing the third mixture, the ethanol mixing time was set to 1 hour. When preparing the fourth mixture, the cooling temperature was set to 5°C and the fragrance mixing time was set to 7 minutes. The low-temperature aging time was set to 12 hours. The viscosity of the final composition was 2700 cP.
[0567] The fabric used consisted of 85% by weight of natural pulp and 15% by weight of viscose fiber, with a basis weight of 45 g / m². The impregnation amount was 16 g / m².
[0568] Example 3: Application of upper limit for ingredient content
[0569] In Example 3, a fabric softener sheet was manufactured by setting the content of each component close to the upper limit within the scope of the invention.
[0570] Composition formulation (based on 100 parts by weight total)
[0571] It was formulated with 11.5 parts by weight of dialkyl ester ammonium methosulfate (20-22 carbon atoms alkyl group, liquid type), 17.5 parts by weight of lauramidopropyl betaine, 2.3 parts by weight of propylene glycol, 5.8 parts by weight of anhydrous citric acid (particle diameter 70 μm), 9.8 parts by weight of glycerin, 0.45 parts by weight of 1,2-hexanediol, 0.75 parts by weight of D-sorbitol, 4.8 parts by weight of sodium benzoate, 2.8 parts by weight of antistatic agent containing 88% by weight of laurylpyridium chloride, 0.75 parts by weight of polydimethylsiloxane (viscosity 900 cSt, molecular weight 90,000), 7.8 parts by weight of ethanol, 17.5 parts by weight of fragrance (woody-musk complex fragrance), and the remainder being 18.32 parts by weight of purified water.
[0572] The weight ratio of the cationic surfactant to the amphoteric surfactant was 11.5:17.5, which is approximately 1:1.52.
[0573] The manufacturing process was identical to that of Example 1, except that the input amounts of each component and some process conditions were adjusted. The process for preparing purified water was performed identically to that of Example 1. The purified water was heated to 48°C. When preparing the aqueous citric acid solution, 48% by weight was added in the first step and the remainder was added in the second step. When preparing the first mixture, 78% by weight of glycerin was added in the first step and the remainder was added in the second step. When preparing the second mixture, the mixing time was set to 4.8 hours. When preparing the third mixture, the ethanol mixing time was set to 3.5 hours. When preparing the fourth mixture, the cooling temperature was set to 8°C and the fragrance mixing time was set to 18 minutes. The low-temperature aging time was set to 28 hours. The viscosity of the final composition was 5800 cP.
[0574] The fabric used consisted of 32% by weight of natural pulp and 68% by weight of viscose fiber, with a basis weight of 78 g / m². The impregnation amount was 32 g / m².
[0575] Example 4: Intermediate condition variation
[0576] In Example 4, a fabric softener sheet was prepared by setting the component content and process conditions with a different combination from Example 1.
[0577] Composition formulation (based on 100 parts by weight total)
[0578] It was formulated with 9.0 parts by weight of dialkyl ester ammonium methosulfate (16-18 carbon atoms alkyl group, liquid type), 15.0 parts by weight of cocamidopropyl betaine, 1.8 parts by weight of propylene glycol, 4.2 parts by weight of anhydrous citric acid (particle diameter 55 μm), 8.5 parts by weight of glycerin, 0.35 parts by weight of 1,2-hexanediol, 0.6 parts by weight of D-sorbitol, 3.5 parts by weight of sodium benzoate, 2.0 parts by weight of antistatic agent containing 86% by weight of laurylpyridium chloride, 0.55 parts by weight of polydimethylsiloxane (viscosity 500 cSt, molecular weight 65,000), 7.0 parts by weight of ethanol, 16.0 parts by weight of fragrance (floral-fruit complex fragrance), and the remainder being 31.5 parts by weight of purified water.
[0579] The weight ratio of the cationic surfactant to the amphoteric surfactant was 9.0:15.0, which was approximately 1:1.67.
[0580] The manufacturing process was performed similarly to Example 1, but the temperature of the heated purified water was set to 47°C, the first input ratio of citric acid was set to 45% by weight, and the first input ratio of glycerin was set to 75% by weight. The mixing time for the second mixture was set to 4.0 hours, the mixing time for the third mixture (ethanol) was set to 2.5 hours, and the low-temperature aging time was set to 24 hours. The viscosity of the final composition was 4500 cP.
[0581] The fabric used consisted of 55% by weight of natural pulp and 45% by weight of viscose fiber, with a basis weight of 65 g / m². The impregnation amount was 25 g / m².
[0582] Comparative example
[0583] In order to clarify the technical significance of the present invention, the following comparative examples were performed in which important process steps were omitted or outside the scope of the invention were omitted.
[0584] Comparative Example 1: Use of regular tap water
[0585] In Comparative Example 1, a fabric softener sheet was prepared using ordinary tap water instead of purified water.
[0586] Composition and Process
[0587] The composition formulation was the same as in Example 1, but tap water was used directly without undergoing a five-step purified water manufacturing process. The electrical conductivity of the tap water used was 350 μS / cm, the total dissolved solids were 180 ppm, and the pH was 7.5. The tap water contained 45 ppm of calcium ions, 18 ppm of magnesium ions, and 0.8 ppm of iron.
[0588] After heating tap water to 45°C and performing nitrogen gas bubbling, the process of preparing an aqueous citric acid solution, preparing a first mixture, preparing a second mixture, preparing a third mixture, preparing a fourth mixture, completing the composition, and manufacturing a fabric softener sheet was carried out in the same manner as in Example 1.
[0589] Immediately after manufacturing, the appearance was similar to Example 1, but after one week of storage, fine white precipitates began to be observed, and after one month of storage, precipitates that were clearly identifiable with the naked eye had settled at the bottom. Transparency decreased significantly, and viscosity also changed unevenly.
[0590] Comparative Example 2: Bulk input of citric acid
[0591] In Comparative Example 2, a fabric softener sheet was manufactured by adding the entire amount of citric acid at once instead of adding it in two stages.
[0592] Composition and Process
[0593] The composition formulation was the same as in Example 1. The process for manufacturing purified water and the process for preparing heated purified water were performed in the same way as in Example 1.
[0594] When preparing the aqueous citric acid solution, the entire 5.25g of anhydrous citric acid was added to heated purified water all at once and stirred at 100 rpm. Some of the citric acid powder settled at the bottom and formed clumps, and the pH of the mixture rapidly dropped to 2.8. The stirring speed was increased to 175 rpm and the temperature raised to 48°C, and vigorous stirring was performed for 12 minutes, but complete dissolution did not occur. The light transmittance was 68%, which was significantly lower than the 92% of Example 1. Fine suspended particles were observed upon visual inspection.
[0595] The subsequent process was carried out in the same manner as in Example 1, but when the sodium benzoate aqueous solution was added, the pH remained low at 3.8, and some sodium benzoate was converted to benzoic acid, forming a fine white precipitate. The appearance of the final composition was opaque, and a precipitate was observed.
[0596] Comparative Example 3: Batch input of glycerin
[0597] In Comparative Example 3, a fabric softener sheet was manufactured by adding the entire amount of glycerin at once instead of adding it in two stages.
[0598] Composition and Process
[0599] The composition formulation was the same as in Example 1. The processes for preparing purified water, preparing heated purified water, and preparing the aqueous citric acid solution were carried out in the same way as in Example 1.
[0600] When preparing the first mixture, an aqueous sodium benzoate solution, an antistatic agent, and an antifoaming agent emulsion were added, and then the entire 11.25g of glycerin was added all at once. Due to its high viscosity, the glycerin sank to the bottom, and it was difficult to achieve uniform mixing at a stirring speed of 125 rpm. The stirring speed was increased to 200 rpm and vigorous stirring was performed for 25 minutes, but an uneven condition persisted in which localized high-viscosity and low-viscosity regions coexisted. The viscosity was measured to be 550 cP, but the difference in viscosity between the upper and lower layers was ±25%, indicating very low uniformity.
[0601] Subsequently, propylene glycol, 1,2-hexanediol, and D-sorbitol were added to complete the first mixture, but the non-uniformity was not resolved. Subsequently, the process was carried out in the same manner as in Example 1, but the final composition also showed poor uniformity with a high interlayer viscosity variation of ±18%.
[0602] Comparative Example 4: Omission of Antifoamer Pre-emulsification
[0603] In Comparative Example 4, a fabric softener sheet was prepared by directly adding a polydimethylsiloxane defoamer without pre-emulsifying it with propylene glycol.
[0604] Composition and Process
[0605] The composition formulation was the same as in Example 1. The processes for preparing purified water, preparing heated purified water, and preparing the aqueous citric acid solution were carried out in the same way as in Example 1.
[0606] When preparing the first mixture, an aqueous sodium benzoate solution and an antistatic agent were added, and then 0.6 g of polydimethylsiloxane was directly added dropwise to the mixture. The defoamer did not mix with water and floated to the surface of the mixture in the form of large droplets (diameter 50–200 μm). The stirring speed was increased to 200 rpm and vigorously stirred for 15 minutes, but the size of the defoamer droplets did not decrease and an oil film formed on the surface. The entire amount of 2.25 g of propylene glycol was added and stirring continued, but the dispersibility of the defoamer did not improve significantly.
[0607] The subsequent process was carried out in the same manner as in Example 1. In the final composition, the defoaming agent was unevenly distributed and excessively concentrated in some areas. Foam generation during the manufacturing process was higher compared to Example 1, and the defoaming efficiency was low.
[0608] Comparative Example 5: Omission of low-temperature aging
[0609] In Comparative Example 5, the low-temperature aging process was omitted after adding the fragrance, and the temperature was immediately raised to room temperature to produce a fabric softener sheet.
[0610] Composition and Process
[0611] The composition formulation was the same as in Example 1. The processes for preparing purified water, preparing heated purified water, preparing an aqueous citric acid solution, preparing a first mixture, preparing a second mixture, preparing a third mixture, and preparing a fourth mixture were performed in the same way as in Example 1.
[0612] After the preparation of the fourth mixture was completed, the low-temperature aging step was omitted, and the temperature was immediately raised to 18°C at a heating rate of 3°C per minute. Subsequently, the composition was completed by final mixing at 80 rpm for 20 minutes.
[0613] The pH of the finished composition was 5.0, the viscosity was 3200 cP, and the temperature was 18°C, but the fragrance retention rate was 82%, which was 11% lower than the 93% of Example 1. This is believed to be because the fragrance could not sufficiently penetrate into the coacervate structure due to the immediate increase in temperature without a low-temperature aging process, and remained dispersed on the surface of the composition before being lost through volatilization during the temperature increase process.
[0614] Comparative Example 6: Electrostatic removal omitted
[0615] In Comparative Example 6, the process of removing static electricity from the fabric was omitted, and a fabric softener sheet was manufactured by impregnating it with a composition.
[0616] Composition and Process
[0617] The composition formulation and manufacturing process were carried out in the same manner as in Example 1 to complete the fabric softener composition.
[0618] When manufacturing a fabric softener sheet, a fabric was prepared consisting of 65% by weight of natural pulp and 35% by weight of viscose fiber, with a basis weight of 60 g / m². The fabric was cut to a size of 22 cm × 27 cm.
[0619] The electrostatic removal process was omitted, and the fabric was immersed in a tank containing the composition for 5 seconds using a direct dipping method, followed by withdrawal at a speed of 12 meters per minute. Due to static electricity on the surface of the fabric, an uneven impregnation state was observed in which the composition was excessively absorbed in certain areas and insufficiently absorbed in other areas. The average absorption amount of the composition per 1 m² of fabric was 18 g, which was lower than the 23 g in Example 1, and the deviation in absorption amount was very high at ±35%.
[0620] The impregnated fabric was passed between rollers and dried at 32°C for 25 minutes to complete the fabric softener sheet. The impregnation amount of the final fabric softener sheet was an average of 15 g / m², but the variation in the impregnation amount within the sheet was very non-uniform with ±40%.
[0621] Comparative Example 7: Excessive cationic surfactant
[0622] In Comparative Example 7, a fabric softener sheet was manufactured by using an excessive amount of cationic surfactant beyond the scope of the invention and setting the weight ratio with amphoteric surfactant to deviate from the scope of the invention.
[0623] Composition and Process
[0624] 15.0 parts by weight of dialkyl ester ammonium methosulfate and 12.0 parts by weight of lauramidopropyl betaine were combined to set the weight ratio of the cationic surfactant to the amphoteric surfactant to 15.0:12.0, which is approximately 1:0.8. This falls outside the scope of the invention, which is 1:1.5 to 1:4. Other ingredients were combined in a ratio similar to that of Example 1, but the amount of purified water was adjusted to the extent that the cationic surfactant increased and the amphoteric surfactant decreased.
[0625] The manufacturing process was performed similarly to Example 1, but when preparing the third mixture, it was observed that the appearance of the mixture became opaque and aggregates formed in some areas after the amphoteric surfactant was added. It is determined that the aggregation occurred because an excess amount of cationic surfactant remained in a free state due to an insufficient amount of amphoteric surfactant.
[0626] The final composition exhibited poor uniformity, and precipitates were observed. Additionally, there is a concern that the excessive amount of cationic surfactant may increase irritation.
[0627] Comparative Example 8: Insufficient flavor content
[0628] In Comparative Example 8, a fabric softener sheet was prepared using a fragrance content less than that of the invention.
[0629] Composition and Process
[0630] The fragrance content was set to 8.0 parts by weight, which is lower than the range of 12 to 18 parts by weight of the invention. Other ingredients were mixed in a ratio similar to that of Example 1, but the amount of purified water was increased by the amount of fragrance reduced.
[0631] The manufacturing process was carried out in the same manner as in Example 1. Although the quality of the final composition was good, the fragrance intensity was weak, so the scent could hardly be perceived on the clothes after using a dryer. The odor masking effect was also insufficient due to the low fragrance content.
[0632] Summary table of results for examples and comparative examples
[0633] The table below summarizes the main compositions and process conditions of Examples 1 to 4 and Comparative Examples 1 to 8.
[0634] Comparison of compositions of examples and comparative examples division Cationic surfactant (parts by weight) Amphoteric surfactant (parts by weight) weight ratio Propylene glycol (parts by weight) Citric acid (parts by weight) Glycerin (parts by weight) 1,2-Hexanediol (parts by weight) D-sorbitol (parts by weight) Sodium benzoate (parts by weight) Antistatic agent (parts by weight) Antifoaming agent (parts by weight) Ethanol (parts by weight) Flavoring (parts by weight) Purified water (parts by weight) Example 1 7.5 14.0 1:1.87 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 15.0 39.4 Example 2 3.5 10.5 1:3.0 0.7 1.2 5.5 0.07 0.25 0.5 0.3 0.08 5.2 12.5 59.73 Example 3 11.5 17.5 1:1.52 2.3 5.8 9.8 0.45 0.75 4.8 2.8 0.75 7.8 17.5 18.32 Example 4 9.0 15.0 1:1.67 1.8 4.2 8.5 0.35 0.6 3.5 2.0 0.55 7.0 16.0 31.5 Comparative Example 1 7.5 14.0 1:1.87 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 15.0 39.4* Comparative Example 2 7.5 14.0 1:1.87 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 15.0 39.4 Comparative Example 3 7.5 14.0 1:1.87 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 15.0 39.4 Comparative Example 4 7.5 14.0 1:1.87 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 15.0 39.4 Comparative Example 5 7.5 14.0 1:1.87 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 15.0 39.4 Comparative Example 6 7.5 14.0 1:1.87 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 15.0 39.4 Comparative Example 7 15.0 12.0 1:0.8** 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 15.0 adjustment Comparative Example 8 7.5 14.0 1:1.87 1.5 3.5 7.5 0.25 0.5 2.5 1.5 0.4 6.5 8.0*** adjustment
[0635] *Comparative Example 1 used ordinary tap water (electrical conductivity 350 μS / cm, total dissolved solids 180 ppm) instead of purified water.
[0636] **Comparative Example 7 has a cationic / amphitropic surfactant weight ratio outside the inventive range (1:1.5~1:4)
[0637] ***Comparative Example 8 has a fragrance content outside the inventive range (12 to 18 parts by weight).
[0638] Comparison of major process conditions between examples and comparative examples division Purified water production Heating temperature (°C) Add citric acid Add glycerin Antifoaming emulsion Cationic surfactant mixture (time) Ethanol mixture (time) Low temperature aging (time) static electricity removal Example 1 Step 5 45 2-step split 2-step split practice 3.5 2.0 20 practice Example 2 Step 5 42 2-step split 2-step split practice 2.2 1.0 12 practice Example 3 Step 5 48 2-step split 2-step split practice 4.8 3.5 28 practice Example 4 Step 5 47 2-step split 2-step split practice 4.0 2.5 24 practice Comparative Example 1 omission* 45 2-step split 2-step split practice 3.5 2.0 20 practice Comparative Example 2 Step 5 45 Bulk input** 2-step split practice 3.5 2.0 20 practice Comparative Example 3 Step 5 45 2-step split Batch input*** practice 3.5 2.0 20 practice Comparative Example 4 Step 5 45 2-step split 2-step split omission**** 3.5 2.0 20 practice Comparative Example 5 Step 5 45 2-step split 2-step split practice 3.5 2.0 omission***** practice Comparative Example 6 Step 5 45 2-step split 2-step split practice 3.5 2.0 20 omission****** Comparative Example 7 Step 5 45 2-step split 2-step split practice 3.5 2.0 20 practice Comparative Example 8 Step 5 45 2-step split 2-step split practice 3.5 2.0 20 practice
[0639] Comparative Example 1 omits the 5-step purified water manufacturing process and uses ordinary tap water.
[0640] **Comparative Example 2 involves adding the entire amount of citric acid at once.
[0641] ***Comparative Example 3 involves adding the entire amount of glycerin at once.
[0642] Comparative Example 4 involves directly adding the antifoaming agent without pre-emulsifying it with propylene glycol.
[0643] *****Comparative Example 5 omits the low-temperature aging process
[0644] ******Comparative Example 6 omits the fabric static electricity removal process.
[0645] Comparison of final composition characteristics of examples and comparative examples division pH Viscosity (cP, 25℃) Fragrance Residue (%) appearance transparency uniformity Stability (after 1 month of storage) Example 1 5.0 3800 93 uniform milky white Good excellence No precipitation, no phase separation Example 2 4.8 2700 91 uniform milky white Good excellence No precipitation, no phase separation Example 3 5.2 5800 94 uniform milky white Good excellence No precipitation, no phase separation Example 4 5.1 4500 92 uniform milky white Good excellence No precipitation, no phase separation Comparative Example 1 4.9 3700 - Good initial Good initial - Large amount of precipitate, discoloration Comparative Example 2 3.8 3600 - Opaque, sediment Defective (68%) error Increase in sediment Comparative Example 3 5.0 3500 - Inter-floor non-uniformity Good Defective (±18% deviation) Phase separation occurs Comparative Example 4 5.0 3900 - formation of an oil film error Defective (uneven defoaming agent) Antifoamer separation Comparative Example 5 5.0 3200 82 uniform milky white Good Good No sedimentation Comparative Example 6 5.0 3800 93 uniform milky white Good excellence No sedimentation Comparative Example 7 4.8 4200 - Observation of aggregates error error Sedimentation Comparative Example 8 5.0 3600 90 uniform milky white Good excellence No sedimentation
[0646] Comparison of characteristics of fabric softener sheets in examples and comparative examples division Fabric composition (natural pulp:viscose) Basis weight (g / m²) Impregnation amount (g / m²) impregnation uniformity Moisture content (weight%) Tensile strength (N) Example 1 65:35 60 20 Excellent (deviation ±5%) 25 28 Example 2 85:15 45 16 Excellent (deviation ±6%) 22 24 Example 3 32:68 78 32 Excellent (deviation ±7%) 32 35 Example 4 55:45 65 25 Excellent (deviation ±5%) 28 31 Comparative Example 1 65:35 60 20 excellence 25 28 Comparative Example 2 65:35 60 19 Poor quality (contains sediment) 26 27 Comparative Example 3 65:35 60 20 Defect (inter-layer deviation) 25 28 Comparative Example 4 65:35 60 20 Defective (uneven defoaming agent) 25 28 Comparative Example 5 65:35 60 20 excellence 25 28 Comparative Example 6 65:35 60 15 Defective (deviation ±40%) 20 26 Comparative Example 7 65:35 60 20 Defective (contains coagulants) 25 28 Comparative Example 8 65:35 60 20 excellence 25 28
[0647] Analysis of Examples and Comparative Examples
[0648] Analysis of Examples 1 to 4
[0649] Examples 1 to 4 varied the content of each component and process conditions of the present invention within the scope of the invention, and all were able to produce high-quality fabric softener sheets.
[0650] Example 1 was prepared by setting the content of each component to an intermediate range and applying standard process conditions, resulting in a final composition with a pH of 5.0, a viscosity of 3800 cP, a fragrance retention rate of 93%, and a uniform milky white appearance. It exhibited excellent long-term stability, with no precipitation or phase separation occurring even after storage for one month. The impregnation uniformity of the fabric softener sheet was also excellent, with a deviation of within ±5%.
[0651] Example 2 was formulated by setting the content of each component close to the lower limit, using 3.5 parts by weight of cationic surfactant and 10.5 parts by weight of amphoteric surfactant in a weight ratio of 1:3. The fragrance content was lowered to 12.5 parts by weight, and the purified water content was increased to 59.73 parts by weight. The viscosity of the final composition was 2700 cP, which was lower than that of Example 1 but still within the range of the invention, 2500 to 6000 cP. The fragrance retention rate was 91%, similar to Example 1. The fabric improved economic efficiency by increasing the natural pulp content to 85% by weight and lowering the basis weight to 45 g / m², and was able to provide a minimal softening effect with an impregnation amount of 16 g / m².
[0652] Example 3 was formulated by setting the content of each component close to the upper limit, using 11.5 parts by weight of cationic surfactant and 17.5 parts by weight of amphoteric surfactant in a weight ratio of approximately 1:1.52. The fragrance content was increased to 17.5 parts by weight to provide a strong scent. The viscosity of the final composition was high at 5800 cP, but it was within the scope of the invention. The fragrance retention rate was highest at 94%, which is attributed to the effect of the long low-temperature aging time (28 hours). The fabric provided a soft touch and high strength by increasing the viscose fiber content to 68% by weight and the basis weight to 78 g / m².
[0653] Example 4 was prepared by setting the component content and process conditions with a different combination from Example 1, using 9.0 parts by weight of cationic surfactant and 15.0 parts by weight of amphoteric surfactant in a weight ratio of approximately 1:1.67. The viscosity of the final composition was 4500 cP, and the fragrance retention rate was 92%. As with Examples 1 to 3, a product of excellent quality could be manufactured.
[0654] From the results of Examples 1 to 4, it was confirmed that the content range of each component and the process condition range of the present invention were appropriately set, and it was found that various combinations are possible within this range.
[0655] Analysis of Comparative Example 1
[0656] Comparative Example 1 is a case where the five-step purified water manufacturing process was omitted and ordinary tap water was used. Immediately after manufacturing, it exhibited an appearance and characteristics similar to Example 1; however, fine precipitates began to be observed after one week of storage, and after one month of storage, a large amount of precipitates clearly identifiable with the naked eye were formed. This is attributed to metal ions contained in the tap water, such as calcium ions (45 ppm), magnesium ions (18 ppm), and iron (0.8 ppm), reacting with the cationic surfactant to form insoluble salts. Additionally, transparency significantly decreased, and some discoloration was observed. These results clearly demonstrate that the use of high-purity purified water is essential for ensuring the long-term stability of the product.
[0657] Analysis of Comparative Example 2
[0658] Comparative Example 2 is a case where the entire amount of citric acid was added at once without being added in two stages; as a result, some of the citric acid powder settled at the bottom to form clumps, and the pH of the mixture rapidly dropped to 2.8. Although vigorous stirring was performed, complete dissolution did not occur, resulting in a low light transmittance of 68% and the observation of fine suspended particles. Furthermore, due to the low pH, some of the subsequently added sodium benzoate was converted into benzoic acid, forming a white precipitate. These results demonstrate that the two-stage addition of citric acid is essential for complete dissolution and proper pH control.
[0659] Analysis of Comparative Example 3
[0660] Comparative Example 3 is a case where the entire amount of glycerin was added at once without being added in two stages; due to the high viscosity of the glycerin, it sank to the bottom, making uniform mixing very difficult. Although vigorous stirring was performed for 25 minutes, an uneven condition persisted in which localized high-viscosity and low-viscosity regions coexisted, and the viscosity difference between the upper and lower layers was very high at ±25%. The final composition also showed poor uniformity, with a high interlayer viscosity deviation of ±18%. These results demonstrate that the two-stage addition of glycerin is essential for stepwise control of viscosity and uniform mixing.
[0661] Analysis of Comparative Example 4
[0662] Comparative Example 4 is a case where a polydimethylsiloxane defoamer was directly added without prior emulsification with propylene glycol; the defoamer did not mix with water and floated to the surface of the mixture in the form of large droplets (diameter 50–200 μm). Although vigorous stirring was performed, the size of the defoamer droplets did not decrease, and an oil film formed on the surface. The defoamer was unevenly distributed in the final composition, and there was a high amount of foam generation and low defoaming efficiency during the manufacturing process. These results demonstrate that prior emulsification of the defoamer is essential for improving water-based dispersibility and increasing defoaming efficiency.
[0663] Analysis of Comparative Example 5
[0664] Comparative Example 5 is a case where the low-temperature aging process was omitted after the addition of flavoring, and the flavor retention rate of the final composition was 82%, which is 11% lower than the 93% of Example 1. This is believed to be because the flavoring did not sufficiently penetrate into the coacervate structure due to the immediate increase in temperature without the low-temperature aging process, remained dispersed on the surface of the composition, and was lost through volatilization during the heating process. These results demonstrate that the low-temperature aging process is essential for improving the encapsulation efficiency of flavoring and minimizing volatilization loss.
[0665] Analysis of Comparative Example 6
[0666] Comparative Example 6 is a case where the electrostatic removal process of the fabric was omitted, resulting in an uneven impregnation state where the composition was excessively absorbed in specific areas due to static electricity on the fabric surface, while absorption was insufficient in other areas. The average absorption amount of the composition per 1 m² of fabric was 18 g, which was lower than the 23 g of Example 1, and the variation in absorption amount was very high at ±35%. The impregnation amount of the final fabric softener sheet was also low at an average of 15 g / m², and the variation in impregnation amount within the sheet was very uneven at ±40%. These results demonstrate that the electrostatic removal process is essential for improving the absorption rate of the composition and ensuring impregnation uniformity.
[0667] Analysis of Comparative Example 7
[0668] Comparative Example 7 is a case in which the content of the cationic surfactant was excessively used at 15.0 parts by weight and the weight ratio with the amphoteric surfactant was set to 1:0.8, deviating from the scope of the invention of 1:1.5 to 1:4; as a result, aggregates were observed to form in some areas after the addition of the amphoteric surfactant. It is determined that the aggregation occurred because an excess amount of the cationic surfactant remained in a free state due to the insufficient amount of the amphoteric surfactant. The final composition exhibited poor uniformity and precipitates were observed, and the amount of precipitates increased after one month of storage. Furthermore, there is a concern that the excessive cationic surfactant may increase irritation. These results demonstrate that stable coacervate formation and product stability can only be ensured if the weight ratio of the cationic surfactant to the amphoteric surfactant remains within the scope of the invention.
[0669] Analysis of Comparative Example 8
[0670] Comparative Example 8 is a case where the fragrance content was set to 8.0 parts by weight, which is lower than the range of the invention (12 to 18 parts by weight). Although the quality of the final composition was good, the fragrance intensity was weak, so the fragrance could hardly be perceived on the clothes after using a dryer. In addition, the odor masking effect was insufficient due to the low fragrance content. These results demonstrate that the fragrance content must be within the range of the invention to provide sufficient fragrance intensity and odor masking effect.
[0671] Experimental Example - Quantitative Verification of Claim Effect
[0672] To quantitatively demonstrate the technical effects of the present invention, the following additional experimental examples were performed. Each experimental example was designed to objectively evaluate the influence of specific process conditions or component ranges on the performance of the final product.
[0673] Experimental Example 1: Comparison of dissolution rate and permeability according to citric acid injection method
[0674] In this experimental example, the effect of the citric acid addition method on the dissolution rate and the permeability of the citric acid aqueous solution was quantitatively evaluated.
[0675] Experimental Example 1-1: 2-stage divided input (present invention)
[0676] Citric acid was added in two stages using the same composition and process as in Example 1. In the first stage, 40% by weight of the total amount was added and mixed for 5 minutes, and then in the second stage, the remaining 60% by weight was slowly added over 3 minutes, and the stirring speed was increased to 150 rpm and vigorously stirred for 10 minutes. The total mixing time was 18 minutes. The light transmittance at a wavelength of 600 nm was measured to be 92%, and a completely transparent aqueous solution was obtained when observed with the naked eye.
[0677] Experimental Example 1-2: Batch Input
[0678] In the same manner as Comparative Example 2, the entire 5.25g of citric acid was added to heated purified water at once and stirred at 100 rpm. Some of the citric acid powder settled at the bottom and formed lumps, so the stirring speed was increased to 175 rpm and the temperature was raised to 48℃ and vigorously stirred for 15 minutes. Although the total mixing time was 15 minutes, the light transmittance at a wavelength of 600 nm was only 68%, and fine suspended particles were observed upon visual inspection.
[0679] Experimental Example 1-3: 3-stage divided input
[0680] A method of adding citric acid in three separate stages was tested. 30% by weight was added in the first stage, 35% by weight in the second stage, and 35% by weight in the third stage, respectively, and mixed for 5 minutes at each stage. The total mixing time was 22 minutes. The light transmittance at a wavelength of 600 nm was 93%, which was similar to Experimental Example 1-1.
[0681] Experimental Example 1-4: Slow, continuous injection
[0682] The entire amount of citric acid was added very slowly and continuously over 10 minutes, stirred at 150 rpm, and then vigorously stirred for an additional 8 minutes. The total mixing time was 18 minutes. The light transmittance at a wavelength of 600 nm was 89%.
[0683] Comparison of dissolution characteristics according to citric acid addition method Experimental Example Input method Total mixing time (minutes) Transmittance (%, 600nm) Visual evaluation pH Dissolution rate improvement rate* 1-1 (The present invention) 2-step split (40% + 60%) 18 92 completely transparent 3.5 standard 1-2 Batch input 15 68 Observation of fine particles 2.8 -17% 1-3 3-step split (30% + 35% + 35%) 22 93 completely transparent 3.6 -22% 1-4 Gradually continuous input 18 89 Almost transparent 3.4 0%
[0684] The dissolution rate improvement rate is calculated by converting it into the standard time to achieve an equivalent transmittance of 90% or higher.
[0685] Analysis: The two-stage split injection method of Experimental Example 1-1 showed a 35% improvement in permeability compared to the batch injection (1-2), and the dissolution speed was calculated to be approximately 23% improved when calculated based on the time required to achieve the same permeability. The three-stage split injection (1-3) was inefficient as the process time increased by 22%, although the permeability was similar, and the gradual continuous injection (1-4) showed a somewhat lower permeability. It was confirmed that the two-stage split injection provides an optimal balance between dissolution efficiency and process efficiency.
[0686] Experimental Example 2: Comparison of Viscosity Uniformity According to Glycerin Addition Method
[0687] In this experimental example, the effect of the glycerin addition method on the viscosity uniformity of the mixture was quantitatively evaluated.
[0688] Experimental Example 2-1: Two-stage divided input (present invention)
[0689] Glycerin was added in two stages using the same composition and process as in Example 1. In the first stage, 70% by weight of the total amount was added and mixed for 10 minutes, and in the second stage, the remaining 30% by weight was added and vigorously mixed for 15 minutes. After the final mixing was completed, samples were taken from the upper, middle, and lower layers, respectively, and the viscosity was measured. The viscosity was measured as 640 cP for the upper layer, 650 cP for the middle layer, and 660 cP for the lower layer, with an average of 650 cP and a deviation of ±1.5% (±10 cP).
[0690] Experimental Example 2-2: Batch Input
[0691] As in Comparative Example 3, the entire amount of 11.25g of glycerin was added all at once and mixed at 125 rpm for 10 minutes, then increased to 200 rpm and vigorously stirred for 25 minutes. After a total mixing time of 35 minutes, samples were taken from the upper, middle, and lower layers, respectively, and the viscosity was measured. The viscosity was measured as 480 cP for the upper layer, 620 cP for the middle layer, and 780 cP for the lower layer, with an average of 627 cP and a deviation of ±24% (±150 cP).
[0692] Experimental Example 2-3: 3-Stage Split Input
[0693] Glycerin was added in three stages. 50% by weight in the first stage, 30% by weight in the second stage, and 20% by weight in the third stage were added, and each stage was mixed for 8 minutes. After a total mixing time of 24 minutes, samples were taken and viscosity was measured. The results showed 630 cP in the upper layer, 645 cP in the middle layer, and 665 cP in the lower layer, with an average of 647 cP and a deviation of ±2.7% (±17 cP).
[0694] Experimental Example 2-4: Slow, continuous injection
[0695] The entire amount of glycerin was added very slowly and continuously over 15 minutes, stirred at 150 rpm, and then mixed for an additional 10 minutes. After a total mixing time of 25 minutes, samples were taken and viscosity was measured, with the upper layer measuring 625 cP, the middle layer 655 cP, and the lower layer 675 cP, resulting in an average of 652 cP and a deviation of ±3.8% (±25 cP).
[0696] Comparison of viscosity uniformity according to glycerin addition method Experimental Example Input method Total mixing time (minutes) Average viscosity (cP) Upper layer (cP) Middle layer (cP) lower layer (cP) Deviation (%) Uniformity Improvement Rate* 2-1 (The present invention) 2-step split (70% + 30%) 25 650 640 650 660 ±1.5 standard 2-2 Batch input 35 627 480 620 780 ±24 -93% 2-3 3-step split (50% + 30% + 20%) 24 647 630 645 665 ±2.7 -44% 2-4 Gradually continuous input 25 652 625 655 675 ±3.8 -60%
[0697] The uniformity improvement rate is calculated as the deviation reduction rate (e.g., 2-2 improves by 93% when improved from ±24% to ±1.5%)
[0698] Analysis: The two-stage split feeding method of Experimental Example 2-1 reduced the viscosity deviation from ±24% to ±1.5% by 93% compared to the batch feeding method (2-2), thereby dramatically improving uniformity. This sufficiently demonstrates the effect of "reducing the mixing defect rate by more than 70%" claimed in the claim. In addition, the two-stage split feeding method reduced the process time by 29%, from 35 minutes to 25 minutes.
[0699] Experimental Example 3: Comparison of Dispersibility According to Antifoamer Emulsification Method
[0700] In this experimental example, the effect of pre-emulsification treatment of a polydimethylsiloxane antifoaming agent on dispersibility in an aqueous mixture was evaluated.
[0701] Experimental Example 3-1: Pre-emulsification with propylene glycol (present invention)
[0702] In the same manner as in Example 1, 0.6 g of polydimethylsiloxane and 1.35 g of propylene glycol were mixed in a weight ratio of 1:2.25 in a separate container and stirred at 200 rpm for 8 minutes to prepare a milky white antifoaming agent emulsion. Observation under an optical microscope revealed that the droplet size ranged from 2 to 5 µm. After adding this emulsion to the first mixture and mixing for 8 minutes, the final mixture was observed under a microscope, revealing that the antifoaming agent droplets were finely and uniformly dispersed with a size of 1 to 4 µm.
[0703] Experimental Example 3-2: Direct Injection
[0704] In the same manner as Comparative Example 4, 0.6 g of polydimethylsiloxane was directly added to the first mixture without prior emulsification and vigorously stirred at 200 rpm for 15 minutes. Microscopic observation revealed that the size of the defoaming agent droplets was 50–200 µm, which were large and unevenly distributed, and some formed an oil film on the surface.
[0705] Experimental Example 3-3: Ethanol and Pre-emulsification
[0706] 0.6g of polydimethylsiloxane and 1.2g of ethanol were mixed in a weight ratio of 1:2, stirred at 200 rpm for 8 minutes, and then added to the first mixture. Microscopic observation showed that the size of the defoaming agent droplets was 8–15㎛, which was larger than that of Experimental Example 3-1 but smaller than that of 3-2.
[0707] Experimental Example 3-4: Surfactant and Pre-emulsion
[0708] 0.6g of polydimethylsiloxane and 0.3g of lauramidopropyl betaine were mixed and emulsified, then added to the first mixture. Microscopic observation revealed that the size of the defoaming agent droplets was 3–8㎛.
[0709] Comparison of dispersibility according to antifoaming agent emulsification method Experimental Example oil painting method Droplet size (㎛) Dispersion uniformity Surface oil film formation Dispersion improvement rate* 3-1 (The present invention) Pre-emulsify with propylene glycol (1:2.25) 1~4 excellence doesn't exist Standard (3.5 times) 3-2 Direct input 50~200 error is available 1x (standard) 3-3 Ethanol and pre-emulsification (1:2) 8~15 commonly a little 2.1 times 3-4 Surfactants and pre-emulsification 3~8 Good doesn't exist 2.8 times
[0710] The dispersibility improvement rate is calculated as the reciprocal ratio of the average droplet size (e.g., average 2.5㎛ in 3-1 vs. average 125㎛ in 3-2 = 50 times, 3.5 times based on surface area)
[0711] Analysis: The propylene glycol and pre-emulsification method of Experimental Example 3-1 reduced the droplet size to 1 / 50th compared to direct addition (3-2), achieving an improvement in dispersibility of approximately 3.5 times based on surface area. This demonstrates the effect of "2 to 4 times improvement in water-based dispersibility of the defoaming agent" claimed in the claim. It was confirmed that propylene glycol has a superior emulsifying effect compared to ethanol or surfactants.
[0712] Experimental Example 4: Comparison of Flavor Encapsulation Efficiency According to Low-Temperature Aging
[0713] In this experimental example, the effect of the low-temperature aging process on the encapsulation efficiency and fragrance persistence of the flavoring was evaluated.
[0714] Experimental Example 4-1: Low-temperature aging for 20 hours (present invention)
[0715] The fourth mixture was aged at a low temperature of 6°C for 20 hours, in the same manner as in Example 1. The fragrance retention rate before and after aging was measured by gas chromatography, and the results showed 95% before aging and 93% after aging, with a loss rate of only 2%. After manufacturing the final fabric softener sheet, it was used in a dryer (70°C, 60 minutes), and the fragrance intensity on the clothing was evaluated by sensory evaluation (out of 10 points). The result was 7.8 points, 6.5 points after 24 hours, and 5.2 points after 48 hours, indicating that the fragrance was maintained continuously.
[0716] Experimental Example 4-2: Omission of low-temperature aging
[0717] As in Comparative Example 5, low-temperature aging was omitted, and the temperature was raised immediately after the preparation of the fourth mixture. During the temperature raising process, the fragrance loss rate increased to 13%, and the final remaining rate was 82%. After using a dryer, the fragrance intensity in the clothing was 5.8 points, and it decreased rapidly to 4.2 points after 24 hours and 2.8 points after 48 hours.
[0718] Experimental Example 4-3: Low-temperature aging for 10 hours
[0719] The fourth mixture was aged at 6°C for 10 hours. The fragrance retention rate was 89%. The fragrance intensity on the clothing after using a dryer was 7.0 points, 5.8 points after 24 hours, and 4.5 points after 48 hours.
[0720] Experimental Example 4-4: Low-temperature aging for 30 hours
[0721] The fourth mixture was aged at 6°C for 30 hours. The fragrance retention rate was 94%. The fragrance intensity on the clothing after using a dryer was 8.0 points, 6.7 points after 24 hours, and 5.4 points after 48 hours.
[0722] Experimental Example 4-5: Room temperature aging for 20 hours
[0723] The fourth mixture was aged at 20°C for 20 hours. The fragrance retention rate was 85%, indicating an increase in volatile loss. The fragrance intensity in the clothing after using a dryer was 6.5 points, 5.0 points after 24 hours, and 3.5 points after 48 hours.
[0724] Comparison of Flavor Encapsulation Efficiency According to Low-Temperature Aging Conditions Experimental Example Aging conditions Fragrance Residue (%) Fragrance loss rate (%) Initial scent intensity (points) 24 hours later (point) 48 hours later (point) Scent longevity index* Scent longevity improvement rate** 4-1 (The present invention) 6℃, 20 hours 93 2 7.8 6.5 5.2 6.5 Standard (43%) 4-2 omission 82 13 5.8 4.2 2.8 4.3 1x (standard) 4-3 6℃, 10 hours 89 6 7.0 5.8 4.5 5.8 35% 4-4 6℃, 30 hours 94 1 8.0 6.7 5.4 6.7 56% 4-5 20℃, 20 hours 85 10 6.5 5.0 3.5 5.0 16%
[0725] *Fragrance longevity index = (Initial fragrance intensity + after 24 hours + after 48 hours) / 3 **Fragrance longevity improvement rate is the improvement rate compared to Experimental Example 4-2
[0726] Analysis: The 20 hours of low-temperature aging in Experimental Example 4-1 improved the fragrance retention rate by 13% and increased the fragrance persistence by 43% compared to the omission of aging (4-2). This confirms the effect of "30-50% improvement in fragrance persistence" claimed in the claim. Although the effect increases with longer aging times, the improvement range is small at 30 hours, confirming that 20 hours is an efficient condition. It was confirmed that low-temperature conditions significantly reduce volatile loss compared to room temperature.
[0727] Experimental Example 5: Comparison of impregnation efficiency according to electrostatic removal
[0728] In this experimental example, the effect of the anti-static treatment of the fabric on the absorption rate and impregnation uniformity of the composition was evaluated.
[0729] Experimental Example 5-1: Electrostatic removal performed (present invention)
[0730] In the same manner as in Example 1, the fabric was ground and treated with an ionizer for 12 seconds to reduce the surface potential to ±50V, after which the composition was impregnated. The absorption amount of the composition per 1 m² of the fabric was 23 g, and when 10 sheets were sampled and the impregnation amount was measured, the results showed excellent uniformity with an average of 20 g / m², a standard deviation of 0.8 g / m², and a coefficient of variation of 4%.
[0731] Experimental Example 5-2: Electrostatic Removal Omitted
[0732] In the same manner as Comparative Example 6, the electrostatic removal treatment was omitted and the composition was impregnated. The surface potential of the fabric was ±1500V. The absorption amount of the composition per 1 m² of fabric was 18 g, and when 10 sheets were sampled and the impregnation amount was measured, the results showed an average of 15 g / m², a standard deviation of 6 g / m², and a coefficient of variation of 40%, indicating very poor uniformity. Some sheets were only 8 g / m², while others reached 22 g / m², showing a large deviation.
[0733] Experimental Example 5-3: Removal of electrostatic portion
[0734] The fabric was folded without ionizer treatment to reduce the surface potential to ±400V, after which the composition was impregnated. The absorption amount of the composition per 1 m² of fabric was 20 g, and it showed a moderate level of uniformity with an average of 17 g / m², a standard deviation of 2.5 g / m², and a coefficient of variation of 15%.
[0735] Experimental Example 5-4: Using only the ionizer
[0736] The surface potential was reduced to ±200V using only an ionizer without grounding, and then the composition was impregnated. The absorption amount of the composition per 1 m² of fabric was 21 g, showing good uniformity with an average of 18 g / m², a standard deviation of 1.8 g / m², and a coefficient of variation of 10%.
[0737] Comparison of impregnation efficiency according to electrostatic removal method Experimental Example Method to remove static electricity Surface potential (V) Absorption amount (g / m²) Average impregnation amount (g / m²) Standard deviation (g / m²) Coefficient of variation (%) Absorption rate improvement rate* Uniformity Improvement Rate** 5-1 (The present invention) Grounding + Ionizer ±50 23 20 0.8 4 Standard (53%) Standard (90%) 5-2 omission ±1500 18 15 6 40 1x (standard) 1x (standard) 5-3 Fold only ±400 20 17 2.5 15 27% 63% 5-4 Ionizerman ±200 21 18 1.8 10 40% 75%
[0738] *Absorption Rate Improvement Rate = (Absorption Amount of Experimental Example - Absorption Amount of 5-2) / Absorption Amount of 5-2 × 100 **Uniformity Improvement Rate = (Coefficient of Variation of 5-2 - Coefficient of Variation of Experimental Example) / Coefficient of Variation of 5-2 × 100
[0739] Analysis: The combined grounding and ionizer treatment of Experimental Example 5-1 improved the absorption rate by 53% and the uniformity by 90% compared to the omission of electrostatic removal (5-2). This demonstrates the effects claimed in the claims of "40-60% improvement in the absorption rate of the composition" and "a 65% or greater reduction in the product defect rate due to uneven impregnation." It was confirmed that combining grounding and ionizer is the most effective.
[0740] Experimental Example 6: Evaluation of Manufacturing Process Time and Efficiency
[0741] In this experimental example, the effect of the manufacturing method of the present invention on the total process time was evaluated.
[0742] Experimental Example 6-1: Method of the present invention (Example 1)
[0743] The time required for each step in the manufacturing process of Example 1 was measured in detail.
[0744] Purified water preparation: 25 minutes
[0745] Preparation of heated purified water: 35 minutes
[0746] Preparation of citric acid solution: 28 minutes
[0747] Preparation of Mixture 1: 85 minutes
[0748] Preparation of 2nd mixture: 220 minutes (3.67 hours)
[0749] Preparation of 3rd mixture: 170 minutes (2.83 hours)
[0750] Preparation of 4th Mixture: 50 minutes
[0751] Low-temperature aging and composition completion: 1230 minutes (20.5 hours)
[0752] Fabric softener sheet production: 40 minutes
[0753] Total manufacturing time: 1883 minutes (approx. 31.4 hours)
[0754] However, since low-temperature aging is an unmanned process, the actual working time was 653 minutes (approximately 10.9 hours).
[0755] Experimental Example 6-2: Conventional method (combination of comparative examples)
[0756] The time required for each step was measured when applying conventional methods such as batch input of citric acid, batch input of glycerin, direct input of antifoaming agent, and omission of low-temperature aging.
[0757] Purified water preparation: Omitted (Use tap water)
[0758] Preparation of heated purified water: 35 minutes
[0759] Preparation of citric acid solution: 35 minutes (Time actually increased due to batch input)
[0760] Preparation of Mixture 1: 115 minutes (Time increased due to batch glycerin addition)
[0761] Preparation of 2nd mixture: 220 minutes
[0762] Preparation of 3rd mixture: 170 minutes
[0763] Preparation of 4th Mixture: 50 minutes
[0764] Composition complete: 30 minutes (cold aging omitted)
[0765] Fabric softener sheet preparation: 40 minutes (static removal omitted)
[0766] Total manufacturing time: 695 minutes (approx. 11.6 hours)
[0767] The actual work time was 695 minutes.
[0768] Experimental Example 6-3: Defect Rate Measurement
[0769] 100 fabric softener sheets were prepared using Experimental Example 6-1 (the present invention) and 6-2 (conventional method), respectively, and the defect rate was measured.
[0770] Experimental Example 6-1 Defective Items:
[0771] Insufficient or excessive impregnation amount: 2
[0772] Impregnation non-uniformity: 1 piece
[0773] Exterior defects: 0
[0774] Total defects: 3 (Defect rate 3%)
[0775] Experimental Example 6-2 Defective Items:
[0776] Insufficient or excessive impregnation amount: 18
[0777] Impregnation non-uniformity: 23
[0778] Appearance defects (sediment, discolo...
Claims
Claim 1 A method for manufacturing a fabric softener sheet composition for a laundry dryer, comprising: a. a step of producing purified water by sequentially passing raw water through a first mesh filter with a mesh size of 210 or larger, a second activated carbon filter with an activated carbon particle size of 0.5 to 2.0 mm, a third ultraviolet sterilization filter emitting ultraviolet rays of a wavelength of 254 nm, a fourth membrane filter with a pore size of 0.0001 to 0.01 μm, and a fifth final line filter made of SUS316 material with a pore size of 5 to 10 μm, thereby producing purified water having an electrical conductivity of 5 to 15 μS / cm and a total dissolved solid content of 5 to 20 ppm or less as measured at 25°C; b. A step of preparing heated purified water, wherein the purified water is introduced into a double-jacketed heating tank made of SUS304 or SUS316 stainless steel with a capacity of 50 to 500 liters, and the purified water is heated to 40 to 50°C by an indirect heating method by circulating hot water at 60 to 95°C through the double jacket, and then nitrogen gas with a purity of 99.9% or higher and an oxygen content of 10 ppm or less is bubbled at a flow rate of 0.1 to 0.5 L / min for 5 to 15 minutes to prepare heated purified water with a dissolved oxygen concentration of 5 ppm or less as measured by an electrochemical dissolved oxygen meter; c. A step for preparing an aqueous citric acid solution, wherein the above-mentioned heated purified water is stirred at a speed of 50 to 80 rpm and classified into particles with a diameter in the range of 40 to 75 μm using a 200 to 400 mesh sieve, and anhydrous crystalline citric acid powder having a moisture content of 0.5 wt% or less and a purity of 99.5% or more is added in two stages, wherein in the first stage, 30 to 50 wt% of the total amount of citric acid to be added is added and mixed for 3 to 8 minutes, and in the second stage, the remaining citric acid is slowly added over 2 to 5 minutes and mixed for 8 to 15 minutes while increasing the stirring speed to 100 to 200 rpm to produce an aqueous citric acid solution having a light transmittance of 85% or more at a wavelength of 600 nm measured by a UV-Vis spectrophotometer using a quartz cell with a path length of 10 mm and a pH in the range of 3.0 to 4.0; d.While stirring the above aqueous citric acid solution at a speed of 40 to 60 rpm, (d-1) a sodium benzoate solution dissolved at a concentration of 10 to 20 wt% in purified water preheated to 35 to 45°C is added to the above aqueous citric acid solution over a period of 2 to 8 minutes, (d-2) an antistatic agent having 80 wt% or more of laurylpyridium chloride as a main component is added to the above mixture, (d-3) a defoaming agent emulsion, in which a polydimethylsiloxane-based defoaming agent having a viscosity of 100 to 1,000 cSt measured at 25°C and a molecular weight of 10,000 to 100,000 is pre-emulsified with propylene glycol in a weight ratio of 1:2 to 1:5 is added to the above mixture, (d-4) 60 to 80 wt% of the total amount of glycerin added is added to the above mixture as a first step, (d-5) the remaining amount of propylene glycol is added to the above mixture, and then (d-6) a first mixture preparation step in which the remaining amount of glycerin is added to the mixture a second time, (d-7) 1,2-hexanediol is added to the mixture, and (d-8) a D-sorbitol solution dissolved at a concentration of 20-40 wt% in purified water preheated to 40-45°C is added to the mixture, thereby preparing a first mixture having a viscosity of 300-600 cp and a pH in the range of 4.0-5.5, measured at 25°C with a Brookfield viscometer at a shear rate of 60 rpm; e. a second mixture preparation step in which a liquid-phase dialkyl ester ammonium methosulfate cationic surfactant having two alkyl groups having 12-22 carbon atoms is added to the first mixture and mixed at 40-50°C for 2-5 hours to prepare a second mixture; f. A third mixture preparation step, wherein an amphoteric surfactant, such as lauramidopropyl betaine or cocamidopropyl betaine, is added to the second mixture, followed by the addition of ethanol and mixing at a speed of 40 to 70 rpm for 0.5 to 4 hours, wherein ethanol volatile substances generated during the mixing process are removed with a collection efficiency of 85% or higher using a HEPA filter or an activated carbon adsorption type dust collector to produce a third mixture; g.A fourth mixture preparation step of adding a fragrance to the third mixture and mixing at low temperature at 3 to 10°C for 5 to 20 minutes to prepare a fourth mixture; h. Aging and cooling step of preparing a fabric softener composition having a viscosity of 2,500 to 6,000 cp measured at a shear rate of 60 rpm using a Brookfield viscometer at 25°C by aging the fourth mixture at 3 to 10°C for 10 to 30 hours and then cooling at 0 to 5°C for 2 to 6 hours; and i. A fabric impregnation step comprising: grounding a fabric composed of 30-90% by weight of natural pulp and 10-70% by weight of viscose fiber, having a basis weight of 40-80 g / m², removing static electricity with an ionizer, applying the fabric softener composition to a thickness of 0.05-2 mm to the surface of the fabric from which static electricity has been removed, and then impregnating it by pressing using a roll laminating method; wherein, based on 100 parts by weight of the total composition, the fabric softener composition comprises 3-12 parts by weight of a liquid dialkyl ester ammonium methosulfate cationic surfactant having two alkyl groups having 12-22 carbon atoms, 10-18 parts by weight of an amphoteric surfactant being lauramidopropyl betaine or cocamidopropyl betaine, 0.5-2.5 parts by weight of propylene glycol, 1-6 parts by weight of citric anhydride, 5-10 parts by weight of glycerin, and 1,2-hexanediol A method for manufacturing a fabric softener sheet composition for a laundry dryer, characterized by comprising a total of 100 parts by weight including 0.05 to 0.5 parts by weight of D-sorbitol, 0.2 to 0.8 parts by weight of sodium benzoate, 0.3 to 5 parts by weight of an antistatic agent having 80% or more by weight of laurylpyridium chloride as the main component, 0.05 to 0.8 parts by weight of a polydimethylsiloxane-based defoamer having a viscosity of 100 to 1,000 cSt measured at 25°C, 5 to 8 parts by weight of ethanol, 12 to 18 parts by weight of a fragrance, and the remainder being purified water, wherein the weight ratio of the cationic surfactant to the amphoteric surfactant is 1:1.5 to 1:
4. Claim 2 In claim 1, the above a. purified water manufacturing step comprises: a1. a first filtration step of passing raw water through a first mesh filter with a pore size of 60 to 75 μm corresponding to 210 to 250 mesh (number of teeth / inch) at a flow rate of 50 to 150 liters per minute to remove suspended solids, rust, and sand larger than 10 μm; a2. a second adsorption filtration step of passing the water that has undergone the first filtration step through a second activated carbon filter with an activated carbon particle size of 0.5 to 2.0 mm to adsorb and remove residual chlorine, organic compounds, odor substances, and color substances, wherein the contact time in the second activated carbon filter is maintained at 5 to 15 minutes and the flow rate is adjusted to 30 to 100 liters per minute; a3. a4. A third sterilization step in which the water obtained from the second adsorption filtration step is passed through a third ultraviolet sterilization filter emitting ultraviolet rays of a wavelength of 254 nm to sterilize bacteria, viruses, and microorganisms, wherein the irradiation intensity of the third ultraviolet sterilization filter is maintained at 30~60 mJ / cm², the exposure time is controlled to 3~10 seconds, and the flow rate is controlled to 20~80 liters per minute; a5. A fourth precision filtration step in which the water obtained from the third sterilization step is passed through a fourth membrane filter of a reverse osmosis or ultrafiltration method with a pore size of 0.0001~0.01 μm to remove heavy metal ions, fine impurities, and dissolved solids, wherein the operating pressure of the fourth membrane filter is maintained at 3~8 bar, the flow rate is controlled to 10~50 liters per minute, and the electrical conductivity of the permeate measured at 25°C is 10 μS / cm or less; a6. A fifth final filtration step in which the water that has undergone the above fourth precision filtration step is passed through a fifth final line filter composed of SUS316 material with pores of 5 to 10 μm to finally remove residual fine particles, while controlling the flow rate to 20 to 60 liters per minute; and a6. The electrical conductivity of the purified water that has undergone the above fifth final filtration step, measured at 25°C, is in the range of 5 to 15 μS / cm, the total dissolved solids are 5 to 20 ppm or less, and the pH is 6.5 to 7.A method for manufacturing a fabric softener sheet composition for a laundry dryer, comprising: a quality verification step of selecting only purified water that satisfies quality standards by measuring in real-time whether it is within the 5 range; wherein the total manufacturing time of the purified water from the first mesh filter to the fifth final line filter is 15 to 40 minutes, and the purified water is stored in a stainless steel storage tank at 3 to 10℃ after manufacturing and then introduced into the b. heated purified water preparation step within 24 hours. Claim 3 In claim 1, the b. step of preparing heated purified water comprises: b1. a preheating step of introducing the purified water into a double-jacketed heating tank made of SUS304 or SUS316 stainless steel with a capacity of 50 to 500 liters, and preheating the purified water to 20 to 30°C by circulating hot water at 60 to 80°C inside the double jacket using an indirect heating method, while controlling the heating speed at 1 to 3°C per minute; b2. a main heating step of stirring the purified water that has undergone the preheating step with a stirrer at a speed of 50 to 100 rpm while raising the temperature of the hot water in the double jacket to 80 to 95°C to main heat the purified water to 35 to 45°C, while controlling the heating speed at 0.5 to 2°C per minute and maintaining the temperature deviation inside the heating tank within ±1.5°C; b3. b4. A temperature stabilization step in which the purified water that has undergone the above-mentioned main heating step is continuously stirred while finely adjusting the hot water temperature of the above-mentioned double jacket to reach a target temperature of 40~50℃, and then the temperature of the above-mentioned target temperature range is maintained within ±0.5℃ for 5~15 minutes; b5. A deoxygenation step in which food-grade nitrogen gas with a purity of 99.9% or higher and an oxygen content of 10 ppm or less is bubbled into the heated purified water that has undergone the above-mentioned temperature stabilization step at a flow rate of 0.1~0.5 L / min for 5~15 minutes to reduce the dissolved oxygen concentration measured by an electrochemical dissolved oxygen meter to 5 ppm or less, while maintaining the temperature of the heated purified water within the range of 40~50℃ even during the bubbling; A temperature equalization step in which the heated purified water that has undergone the above deoxygenation step is stirred with the above stirrer at a speed of 80 to 150 rpm for 3 to 10 minutes to equalize the temperature difference of the upper, middle, and lower layers inside the heating tank to within ±0.3℃; and b6.A method for manufacturing a fabric softener sheet composition for a laundry dryer, comprising: a heating water quality verification step in which only heating purified water satisfying quality standards is transferred to the next step by measuring whether the temperature of the heating purified water that has undergone the temperature homogenization step is in the range of 42 to 48°C, the dissolved oxygen concentration measured by an electrochemical dissolved oxygen meter is in the range of 3 to 5 ppm, and the electrical conductivity measured at 25°C is in the range of 5 to 15 μS / cm; wherein the total heating time from the preheating step to the heating water quality verification step is 20 to 50 minutes, and the heating purified water is introduced into the c. citric acid aqueous solution manufacturing step within 1 hour after manufacturing; wherein the indirect heating method prevents local overheating of the purified water compared to the direct heating method to suppress the precipitation of dissolved minerals, and the deoxygenation treatment by nitrogen gas bubbling prevents oxidation of the subsequently introduced citric acid, glycerin, and fragrance to improve product stability.
Citation Information
Patent Citations
Sheet type fabric softener and manufacturing method
KR1020230147814A
Fabric softener sheet for dryer and manufacturing method thereof
KR102249682B1
Fabric softener composition manufacturing method for dryer
KR102252198B1
Fabric softener composition for dryer and manufacturing method thereof
KR102379862B1
